Solid composition containing starch and method for producing the same

By performing high-temperature and strong kneading of bean starch under pressurized conditions and increasing the intermediate molecular weight fraction, the problem of difficulty in both elasticity and low viscosity when retention of water when heated under water under water-containing conditions is solved, and the preferred water-retaining performance is achieved.

CN117460424BActive Publication Date: 2025-03-11MIZKAN HOLDINGS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180050136.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-09
Filing Date
2021-08-06
Publication Date
2025-03-11
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

The prior art is difficult to heat under water-containing conditions, and has both elasticity and low viscosity of the starch solid composition when it is heated under water-containing conditions.

Method used

By performing high-temperature and strong kneading of bean starch under pressurized conditions, intermediate molecular weight fractions are added to form a composition that has both elasticity when heated under water and low viscosity when retaining water when heated under water.

Benefits of technology

When heating under water-containing conditions, the elasticity of the starch solid composition is preferably used for water retention and low viscosity when retaining water, and the problem of the rising viscosity of the starch composition after heating and absorbing water in the prior art is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BPA0000334657380000541
    Figure BPA0000334657380000541
  • Figure BPA0000334657380000901
    Figure BPA0000334657380000901
  • Figure BPA0000334657380000911
    Figure BPA0000334657380000911
Patent Text Reader

Abstract

A solid starch-containing composition having both preferred elasticity when retaining water and low viscosity when retaining water when heated under water-containing conditions is provided. Such a composition satisfies all of the following (1) to (4). (1) The starch content in the composition is 20% by mass or more, calculated as dry mass. (2) The following (a) and / or (b) are satisfied. (a) When a 6% suspension of a crushed product of the composition is observed, the number of visible starch granules is 300 granules / mm 2 Below. (b) The gelatinization peak temperature when a 14% by mass aqueous slurry of the crushed composition is measured by heating the temperature from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer is lower than 120°C. (3) The degree of gelatinization of the starch in the composition is 50% by mass or more. (4) The following [value α] of the composition is 60% or less, and the following [value β] is 35% or more. [Value α] is the ratio of the area under the curve of the interval where the molecular weight logarithm is 5.0 or more and less than 6.5 relative to the total area under the curve of the molecular weight distribution curve, wherein the molecular weight distribution curve is obtained by analyzing purified starch under [condition A], wherein the purified starch is obtained by heat-treating the composition in 40 times the amount of water at 90°C for 15 minutes and then treating it through [step a]. [Value β] is the ratio of the area under the curve of the interval where the molecular weight logarithm is 6.5 or more and less than 8.0 relative to the total area under the curve of the above-mentioned molecular weight distribution curve. (Wherein, [step a] and [condition A] are as described in the specification.)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid composition containing starch and a method for producing the same. Background Art

[0002] At present, when a solid composition mainly composed of starch is heated under water-containing conditions, the elasticity of the composition increases as it absorbs water, but as it absorbs water during heating, the viscosity of a part of the starch in the composition increases, making it difficult to process. As a method for solving such a problem, there is known a method for producing noodles with improved moderate hardness and elasticity by adding polyoxyethylene sorbitan fatty acid ester alone or in combination with an existing noodle modifier to suppress the adhesion of noodles to each other (Patent Document 1: Japanese Patent Publication No. 2004-215543).

[0003] However, the currently known method is a method of adding a modifier such as polysorbate, which is not a generally applicable method because of the unpleasant flavor imparted by the modifier or the safety concerns of recent consumers. That is, there is currently no method for providing a solid composition containing starch as a main component that has both the preferred elasticity when retaining water and the low viscosity when retaining water when heated under water-containing conditions.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-215543. Summary of the invention

[0007] Problems to be solved by the invention

[0008] The present invention has been made in view of the above problems, and an object of the present invention is to provide a starch-containing solid composition having both preferable elasticity when retaining water and low viscosity when retaining water when heated under water-containing conditions.

[0009] Means of solving problems

[0010] The present inventors have conducted intensive studies on starches from various plants and processing conditions thereof, and as a result, have found that by subjecting starch derived from beans to a high-temperature, intensive kneading process mainly under pressurized conditions, the intermediate molecular weight fraction in the composition is increased, and a composition having the preferred physical properties of both elasticity when retaining water and low viscosity when retaining water is formed when heated under water-containing conditions, thereby completing the present invention.

[0011] That is, the gist of the present invention relates to, for example, the following contents.

[0012] [Item 1] A solid composition containing starch, wherein the composition satisfies all of the following (1) to (4):

[0013] (1) the content of starch in the composition is 20% by weight or more on a dry basis;

[0014] (2) Satisfy the following (a) and / or (b):

[0015] (a) When a 6% suspension of the pulverized product of the composition is observed, the starch granule structure visible is 300 granules / mm 2 the following,

[0016] (b) the gelatinization peak temperature when a 14 mass % aqueous slurry of the pulverized composition is heated from 50° C. to 140° C. at a heating rate of 12.5° C. / min using a rapid viscosity analyzer is lower than 120° C.;

[0017] (3) The degree of gelatinization of the starch in the composition is 50% by mass or more;

[0018] (4) The following [value α] of the composition is 60% or less, and the following [value β] is 35% or more:

[0019] [Value α] The ratio of the area under the curve of the interval where the molecular weight logarithm is 5.0 or more and less than 6.5 relative to the total area under the curve of the molecular weight distribution curve, wherein the molecular weight distribution curve is obtained by analyzing the purified starch under the following [Condition A], wherein the purified starch is obtained by isothermal treating the composition in 40 times the amount of water at 90° C. for 15 minutes and then treating it by the following [Step a];

[0020] [Value β] The ratio of the area under the curve of the interval where the logarithm of the molecular weight is 6.5 or more and less than 8.0 to the total area under the curve of the molecular weight distribution curve;

[0021] [Step a] pulverizing a 2.5% aqueous dispersion of the composition and treating it with a proteolytic enzyme to obtain an ethanol-insoluble and dimethyl sulfoxide-soluble component as purified starch;

[0022] [Condition A] 0.10 mass % of purified starch was dissolved in a 1M sodium hydroxide aqueous solution, and after standing at 37°C for 30 minutes, an equal amount of water and an equal amount of eluent were added, and 5 mL of the filtrate obtained by filtering through a 5 μm filter was subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm greater than 5.0 and less than 9.5.

[0023] [Item 2] The composition according to Item 1, wherein a ratio (β / α) of the [value β] to the [value α] is 0.5 or more.

[0024] [Item 3] The composition according to Item 1 or 2, wherein the following [value γ] is 30% or less:

[0025] [Value γ] is the ratio of the area under the curve in the region where the logarithm of the molecular weight is 8.0 or more and less than 9.5, relative to the total area under the curve of the molecular weight distribution curve.

[0026] [Item 4] The composition according to any one of Items 1 to 3, wherein the ratio (β / γ) of the [value β] to the [value γ] is 10 or more.

[0027] [Item 5] The composition of any one of Items 1 to 4, wherein the logarithm of the mass average molecular weight obtained by analyzing the purified starch under the [Condition A] is 6.0 or more, and the purified starch is obtained by the treatment in the [Step a].

[0028] [Item 6] The composition according to any one of Items 1 to 5, wherein the amylolytic enzyme activity of the composition is 30.0 U / g or less on a dry mass basis.

[0029] [Item 7] The composition of any one of Items 1 to 6, wherein the absorbance at 660 nm when 1 part by mass of the sample is stained with 9 parts by mass of an iodine solution (0.25 mM) is 0.80 or less, and the sample is obtained by adding the composition to 40 times the amount of water and then rapidly treating it through the [step a] to obtain purified starch, and separating and recovering the separated fraction having a molecular weight logarithm of 5.0 or more and less than 6.5 under the [condition A], and adjusting the pH to 7.0.

[0030] [Item 8] The composition according to any one of Items 1 to 7, wherein the protein content of the composition is 3.0% by mass or more on a dry mass basis.

[0031] [Item 9] The composition according to any one of Items 1 to 8, wherein the composition has a PDI (protein dispersibility index) value of less than 55% by mass.

[0032] [Item 10] The composition of any one of Items 1 to 9, wherein the composition is subjected to starch-protein decomposition treatment in the following [step b], and then subjected to ultrasonic treatment and the particle size distribution is measured. 50 and / or 90 Below 450μm:

[0033] [Step b]

[0034] A 6 mass % aqueous suspension of the composition was treated with 0.4 volume % of protease and 0.02 mass % of α-amylase at 20° C. for 3 days.

[0035] [Item 11] The composition according to any one of Items 1 to 10, wherein the insoluble dietary fiber content of the composition is 2.0% by mass or more on a dry mass basis.

[0036] [Item 12] The composition according to any one of Items 1 to 11, wherein the total fat and oil content of the composition is less than 17% by mass on a dry mass basis.

[0037] [Item 13] The composition according to any one of Items 1 to 12, wherein the composition has a dry basis moisture content of 60% by mass or less.

[0038] [Item 14] The composition according to any one of Items 1 to 13, wherein the composition contains beans.

[0039] [Item 15] The composition described in Item 14, wherein the beans have a dry basis moisture content of less than 15% by mass.

[0040] [Item 16] The composition described in Item 14 or 15, wherein the beans are mature beans.

[0041] [Item 17] The composition according to any one of Items 14 to 16, wherein the legume is one or more legumes selected from the genera Pisum, Phaseolus, Cajanus, Vigna, Vicia, Garbanzo, Glycine max, and Lentil.

[0042] [Item 18] The composition described in any one of Items 14 to 17, wherein the beans have a particle size of d 90 Morphology of pulse powders below 500 μm.

[0043] [Item 19] The composition according to any one of Items 14 to 18, wherein the content of beans is 50% by mass or more on a dry mass basis.

[0044] [Item 20] The composition according to any one of Items 14 to 19, wherein the content ratio of the starch blended in a state contained in beans relative to the total starch content of the composition is 30% by mass or more.

[0045] [Item 21] The composition according to any one of Items 14 to 20, wherein the content ratio of the protein blended in a state contained in beans relative to the total protein content of the composition is 10% by mass or more.

[0046] [Item 22] The composition according to any one of Items 1 to 21, which is not a puffed product.

[0047] [Item 23] A pulverized composition, the composition being obtained by pulverizing the composition according to any one of Items 1 to 22.

[0048] [Item 24] A pulverized composition agglomerate, wherein the pulverized composition according to Item 23 is agglomerated.

[0049] [Item 25] A method for producing a solid composition containing starch according to any one of Items 1 to 22, the method comprising the following steps (i) and (ii):

[0050] (i) a stage of preparing a composition having a starch content of 10.0% by mass or more on a wet basis and a moisture content of more than 40% by mass on a dry basis,

[0051] (ii) kneading the composition prepared in step (i) at a temperature of 100° C. to 190° C. at a SME value of 400 kJ / kg or more until the composition satisfies all of the following conditions (1) to (4):

[0052] (1) The composition satisfies the following (a) and / or (b):

[0053] (a) The starch granule structure of the composition is 300 granules / mm 2 the following,

[0054] (b) the gelatinization peak temperature when a 14 mass % aqueous slurry of the pulverized composition is heated from 50° C. to 140° C. at a heating rate of 12.5° C. / min using a rapid viscosity analyzer is lower than 120° C.;

[0055] (2) the gelatinization degree of the composition is 50% by mass or more;

[0056] (3) the [value α] of the composition is 60% or less;

[0057] (4) The [value β] of the composition is 35% or more.

[0058] [Item 26] The method of manufacturing described in Item 25, further comprising: (iii) cooling the kneaded composition of step (ii) to a temperature below 100°C.

[0059] [Item 27] ​​The production method described in Item 25 or 26, further comprising: (iv) a step of reducing the dry basis moisture content of the composition to less than 25% by mass.

[0060] [Item 28] The method of Item 27, wherein after the step (ii), the time required from when the temperature of the composition is reduced to below 80°C until the dry basis moisture content of the composition is less than 25% by mass is 10 minutes or more.

[0061] [Item 29] The production method according to any one of Items 25 to 28, wherein the time required for the dry basis moisture content of the composition to be adjusted to less than 25% by mass is adjusted by adding water in a stage after stage (iii).

[0062] [Item 30] The production method according to any one of Items 25 to 29, which includes a stage after stage (ii) in which the difference in gelatinization degree decreases by 1% by mass or more.

[0063] [Item 31] The method according to any one of Items 25 to 30, further comprising: (v) at least after the step (ii), crushing the obtained composition to produce a crushed composition.

[0064] [Item 32] The production method described in Item 31, further comprising: (vi) after the step (v), agglomerating the obtained pulverized composition to form an agglomerate of the pulverized composition.

[0065] [Item 33] The production method according to any one of Items 25 to 32, wherein the step (ii) is carried out using an extruder.

[0066] [Item 34] The production method described in Item 33, wherein the preparation of the composition in stage (i) includes adding water to the raw materials before being fed into the extruder.

[0067] [Item 35] The manufacturing method described in Item 33 or 34, wherein the preparation of the composition in stage (i) includes adding water to the raw materials in the extruder after the raw materials are fed into the extruder.

[0068] [Item 36] The production method described in Item 35, wherein in step (i), the raw material in the extruder is not exposed to a high temperature of 90°C or more in a state where the raw material has a dry basis moisture content of less than 25% by mass.

[0069] [Item 37] A method for producing a product as described in any one of Items 33 to 36, wherein 50% by mass or more of the total amount of water blended in stages (i) and (ii) is mixed with other raw materials during production before the internal temperature of the extruder rises to 90°C or higher.

[0070] [Item 38] The production method according to any one of Items 33 to 37, wherein the composition after stage (iii) is placed on a mesh conveyor having a part or the whole of the placement surface having ventilation properties.

[0071] [Item 39] The production method described in Item 38, wherein there is a step of adding water to the composition at any stage before or after placing the composition on the mesh conveyor.

[0072] [Item 40] The manufacturing method described in Item 38 or 39, which includes: lowering the temperature of the composition by sending air to the composition from the upper part and / or the lower part of the mesh conveyor belt.

[0073] [Item 41] The production method according to Item 40, wherein the difference in decrease in gelatinization degree before and after air supply is 1% by mass.

[0074] [Item 42] The production method according to any one of Items 33 to 41, wherein the length of the flight screw relative to the total length of the screw of the extruder is 95% or less.

[0075] [Item 43] The method according to any one of Items 25 to 42, wherein in the step (ii), (c) or (d) is also satisfied:

[0076] (c) when a 6% suspension of the pulverized product of the composition is observed, the structure of the starch granules visible before and after stage (ii) is reduced by more than 5%;

[0077] (d) When a 14 mass % aqueous slurry of the pulverized composition is heated from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer, the gelatinization peak temperature decreases by 1°C or more before and after stage (ii).

[0078] [Item 44] The method of any one of Items 25 to 43, wherein after subjecting the composition in the stage (i) to starch-protein degradation treatment in the [step b], the particle size distribution is measured after ultrasonic treatment. 50 and / or 90 Less than 450μm.

[0079] [Item 45] The production method described in any one of Items 25 to 44, wherein the content ratio of the starch mixed in a state contained in the heat-treated beans relative to the total starch content of the composition in the stage (i) is 30% by mass or more.

[0080] [Item 46] The production method according to any one of Items 25 to 45, wherein the amylolytic enzyme activity (U / g) decreases by 20% or more before and after stage (ii).

[0081] [Item 47] The method according to any one of Items 25 to 46, wherein the absorbance at 660 nm when 1 part by mass of the sample is stained with 9 parts by mass of an iodine solution (0.25 mM) is 0.80 or less, and the sample is obtained by adjusting the pH of the separated fraction having a molecular weight logarithm of not less than 5.0 and not more than 6.5, wherein the purified starch obtained by adding the composition in the stage (i) into 40 times the amount of water and then rapidly treating it through the [step a] is separated and recovered under the [condition A].

[0082] [Item 48] The method according to any one of Items 25 to 47, wherein the ratio of the absorbance (660 nm) of a separated fraction having a logarithm of molecular weight of not less than 6.5 and not more than 8.0 when stained by the same method to the absorbance (660 nm) of 1 part by mass of the sample stained with 9 parts by mass of an iodine solution (0.25 mM) is 0.003 or more, and the sample is obtained by adjusting the pH of the separated fraction having a logarithm of molecular weight of not less than 5.0 and not more than 6.5 to 7.0, after the purified starch obtained by adding the composition in the stage (i) to 40 times the amount of water and then rapidly treating it by the [step a] is separated and recovered under the [condition A].

[0083] [Item 49] The production method according to any one of Items 25 to 48, wherein the PDI value of the composition in the step (i) is less than 90% by mass.

[0084] Effects of the Invention

[0085] The starch-containing solid composition of the present invention has both preferable elasticity when retaining water and low viscosity when retaining water when heated under water-containing conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] [ Figure 1 ] Figure 1 This is a graph of molecular weight distribution obtained by analyzing purified starch under the following [Condition A], wherein the purified starch is obtained by thermostatically treating the composition of the test example in 40 times the amount of water at 90°C for 15 minutes and then treating it by the following [Step a]. DETAILED DESCRIPTION

[0087] Hereinafter, the present invention will be described in detail based on specific embodiments. However, the present invention is not limited to the following embodiments, and can be implemented in any manner without departing from the spirit of the present invention.

[0088] [I. Solid composition containing starch]

[0089] One embodiment of the present invention relates to a starch-containing solid composition having specific properties described below (hereinafter appropriately referred to as “the starch-containing solid composition of the present invention” or simply “the composition of the present invention”).

[0090] Form of the composition:

[0091] The starch-containing solid composition of the present invention has both preferred elasticity when retaining water and low viscosity when retaining water when heated under water-containing conditions, and is therefore preferably used for food. As its form, it may be a composition used directly as a food (food composition) or a composition used as a food raw material (food raw material composition). In the case of a food raw material composition, as described below, it may be a composition in a pulverized state (pulverized composition) or a composition in a state where such a pulverized composition is further agglomerated (pulverized composition agglomerate). In any case, the composition of the present invention is preferably a starch-containing composition for heating and cooking, and the composition is provided for heating and cooking in a liquid (particularly water) as a cooking environment in which the components are particularly easily dissolved. For example, when the starch-containing composition for heating and cooking is a noodle or noodle strip composition such as noodles or pasta, it has the property of being able to maintain an edible shape even after heating and cooking in water for consumption (for example, in water above 90°C for more than 5 minutes), and is therefore preferably a noodle or noodle strip composition such as noodles or pasta.

[0092] Examples of the composition of the present invention include, but are not limited to, pasta, Chinese noodles, udon noodles, Inaniwa udon noodles, kizushi noodles, hoto noodles, noodle soup, cold noodles, vegetarian noodles, buckwheat noodles, hot buckwheat cakes, rice noodles, Vietnamese noodles, cold noodles, vermicelli, oatmeal, couscous, chirashi, rice cakes, dumpling skins, and the like.

[0093] Examples of pasta include long pasta and short pasta.

[0094] Long pasta is usually a general term for long and thin pasta, but in the present invention, it is a concept that also includes udon noodles or soba noodles. As specific examples, for example, solid spaghetti (diameter: 1.6mm-1.7mm), straight spaghetti (diameter: 1.4mm-1.5mm), spaghetti (diameter: 2.0mm-2.2mm), capellini (diameter: 0.8mm-1.0mm), flat spaghetti (short diameter of about 1mm, long diameter of about 3mm), Italian flat curly noodles or ribbon noodles (a flat surface of about 7mm-8mm in width), pappardelle (a flat surface of about 10mm-30mm in width), etc. can be listed, but it is not limited to these. Since long pasta is easy to have a commodity characteristic that its shape is easily destroyed during heating and cooking, it is useful and preferred as the composition of the present invention.

[0095] Short pasta is generally a general term for short pasta, but in the present invention, it is a concept that also includes mini spherical pasta (granular pasta) or couscous, etc., which are formed and processed into smaller sizes. Specific examples include macaroni (cylindrical shape with a diameter of about 3mm to 5mm), straight penne (noodles cut at both ends of a cylinder like a pen tip), butterfly pasta (butterfly-like shape), shell pasta (shell-like shape), cat ear pasta (ear-shaped dome-shaped), etc., but are not limited to these.

[0096] Composition in dry state:

[0097] The composition of the present invention may be a composition containing relatively high water content (specifically, a dry basis water content of 25% by mass or more) or a composition containing relatively low water content (specifically, a dry basis water content of less than 25% by mass), but for the convenience of storage, a dry composition may be prepared. In particular, by preparing the composition in a dry state while performing the water retention treatment described below, it is useful because the compositions are difficult to adhere to each other.

[0098] It should be noted that in the present invention, the "dry" state refers to a state in which the dry basis moisture content is less than 25% by mass and the water activity value is less than 0.85. It should be noted that the moisture content in the composition can be measured by subjecting the dry powder to the following reduced pressure heating drying method, and the water activity value can be measured using a general water activity measuring device (e.g., "LabMaster-aw NEO" manufactured by Novasina using a resistive (electrolyte) humidity sensor) according to a conventional method.

[0099] Slender shaped compositions:

[0100] The composition of the present invention can be formed into any shape that conventional starch-containing solid compositions have, and can particularly be formed into a composition having an elongated shape such as long spaghetti.

[0101] The composition of the present invention in such an elongated shape is not particularly limited, but preferably has a diameter of generally 20 mm or less, preferably 10 mm or less, more preferably 5 mm or less, further preferably 3 mm or less, and further preferably 2 mm or less. It should be noted that the "diameter" of the composition refers to the major diameter of the cut surface when the composition is cut perpendicularly to the length direction (the maximum length of the line segment connecting any two points in the cross section). Here, if the cut surface is circular, its diameter is equivalent to the "diameter" of the composition, if it is elliptical, its major axis is equivalent to the "diameter" of the composition, and if it is rectangular (for example, in the case of a composition formed into a plate), its diagonal is equivalent to the "diameter" of the composition.

[0102] (Starch and its content)

[0103] The composition of the present invention contains starch. In particular, the composition of the present invention can easily obtain the effect of feeling elasticity as it absorbs water after heating and cooking by containing starch in a predetermined ratio or more. The reason is not clear, but through high temperature, high pressure and high kneading treatment, the fraction with a larger molecular weight in the starch in the composition forms a network structure, and as a result, it is possible to achieve the above effect. In the present invention, "heating and cooking" generally refers to a cooking method in which the temperature of the food is increased by heating the food directly or indirectly through a medium such as water or air using fire or microwaves. It generally means cooking at a heating temperature of about 70°C or more, typically about 80°C to 180°C, for example, for a time of more than 1 minute and less than 60 minutes. As such a method of heating and cooking, for example, roasting, boiling, frying, steaming, etc. can be listed, but the composition of the present invention has the characteristic that the shape is not easily deformed when heated and cooked in a liquid. In the present invention, heating and cooking is particularly preferably a composition for heating and cooking in a liquid mainly composed of water (containing more than half), and further, the composition of the present invention is particularly preferably a composition for heating and cooking in a liquid that is eaten after heating and cooking in a liquid.

[0104] Specifically, the lower limit of the starch content in the composition of the present invention is usually 20 mass % or more in terms of dry mass conversion. Wherein, preferably 25 mass % or more, particularly preferably 30 mass % or more, or 35 mass % or more, or 40 mass % or more, or 45 mass % or more, particularly preferably 50 mass % or more. On the other hand, the upper limit of the starch content in the composition of the present invention is not particularly limited, for example, converted to less than 85 mass % in terms of dry mass, wherein can be set to less than 80 mass % or less than 70 mass % or less than 60 mass %.

[0105] The source of starch in the composition of the present invention is not particularly limited. As an example, starch derived from plants or starch derived from animals can be listed, preferably starch derived from beans. Specifically, the ratio of the starch content derived from beans relative to the total starch content of the entire composition is usually 30% by mass or more, wherein, preferably 40% by mass or more, or 50% by mass or more, or 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more, particularly preferably 100% by mass. The upper limit is not particularly limited, and is generally 100% by mass or less. As starch derived from beans, starch derived from peas is particularly preferred, and starch derived from yellow peas is most preferred. Beans will be described below.

[0106] The starch in the composition of the present invention can be blended in the composition as a separated pure product, preferably in the composition in a state contained in beans. Specifically, the ratio of the starch content blended in a state contained in beans relative to the total starch content of the entire composition is usually 30% by mass or more, wherein, preferably 40% by mass or more, or 50% by mass or more, or 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more, particularly preferably 100% by mass. The upper limit is not particularly limited, and is usually 100% by mass or less.

[0107] It should be noted that in the present invention, the starch content in the composition is determined according to the Japanese Food Standard Composition Table 2015 Edition (Seventh Edition) and the method of AOAC996.11, by 80% ethanol extraction to remove soluble carbohydrates (glucose, maltose, maltodextrin, etc.) that affect the measured value.

[0108] (Starch granule structure)

[0109] The composition of the present invention preferably has a number of starch granule structures below a specified value. The reason is not clear, but it is believed that by processing the composition under the following high temperature, high pressure and strong kneading conditions in a state where the starch granule structure is destroyed, the starch is diffused in the entire composition in a matrix state, and the branched starch in the starch forms a structure that is easy to show elasticity when retaining water. Specifically, the composition of the present invention preferably satisfies the following (a) and / or (b), and more preferably satisfies (a) and (b) at the same time.

[0110] (a) When a 6% suspension of the pulverized product of the composition is observed, the starch granule structure visible is 300 granules / mm 2 the following.

[0111] (b) The gelatinization peak temperature measured by heating a 14 mass % aqueous slurry of the pulverized composition from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer was lower than 120°C.

[0112] The starch granule structure in (a) above is a structure having a circular shape with a diameter of about 1 to 50 μm in a plane image and having iodine staining properties. For example, a 6% aqueous suspension obtained by suspending the crushed material of the composition in water can be prepared and observed under a magnified field of view. Specifically, a 6% suspension of the composition powder is prepared by grading the crushed material of the composition with a sieve with a mesh of 150 μm, and suspending 3 mg of the composition powder passing through 150 μm in 50 μL of water. A microscope specimen carrying the suspension is prepared, and polarized light is observed with a phase contrast microscope, or an iodine-stained specimen is observed with an optical microscope. There is no limit to the magnification, and for example, the magnification can be set to 100 times or 200 times. In the case where the distribution of the starch granule structure in the microscope specimen is uniform, the proportion of the starch granule structure of the entire microscope specimen can be inferred by observing the representative field of view. In the case where it is seen that there is a deviation in its distribution, a limited (for example, more than 2, for example, 5 or 10) field of view is observed, and the observation results are added, which can be used as the measured value of the entire microscope specimen. The reason for this is not clear, but it is considered that the value decreases because starch particles are destroyed by subjecting the raw material and / or green dough containing starch to a high-temperature intensive kneading treatment or the like.

[0113] Specifically, the number of starch granule structures observed under the above conditions for the composition of the present invention is generally 300 / mm 2 Below, preferably 250 pieces / mm 2 Below, more preferably 200 pieces / mm 2 Below, especially preferably 150 pieces / mm 2 Below, or 100 pieces / mm 2 Below, or 50 pieces / mm 2 Below, or 30 pieces / mm 2 Below, or 10 / mm 2 Below, particularly preferably 0 pieces / mm 2 .

[0114] As the rapid viscosity analyzer (RVA) in (b) above, any device can be used as long as it can heat the object to be measured to 140°C, for example, RVA4800 manufactured by Perten can be used. Specifically, the gelatinization peak temperature when measured by RVA at a heating rate of 12.5°C / min is measured by the following steps. That is, after 3.5 g of the composition sample by dry weight is crushed (for example, crushed to pass through 100 mesh (mesh size 150 μm) and remain on 120 mesh (mesh size 125 μm)), it is measured into an aluminum cup for RVA measurement, and distilled water is added to make the total amount 28.5 g, and the 14% sample water slurry prepared in this way (sometimes referred to as "composition crushed material water slurry" or "sample water slurry") is provided for the RVA viscosity measurement in the above [step a]. For a 14 mass % aqueous slurry of the crushed composition, the measurement was started at 50°C, the rotation speed was set to 960 rpm from the start of the measurement to 10 seconds after the start of the measurement, and the rotation speed was set to 160 rpm from 10 seconds after the start of the measurement to the end of the measurement. After maintaining at 50°C for 1 minute, a heating process was started at a heating rate of 12.5°C / min from 50°C to 140°C, and the gelatinization peak temperature (°C) was measured.

[0115] In the present invention, in the composition with less starch granule structure, since the viscosity increase associated with the swelling of the starch granule structure with water is not caused or rarely caused, the gelatinization peak temperature also tends to be a relatively low temperature. Therefore, the gelatinization peak temperature measured in this way is lower than the specified temperature, and a good effect is exerted. Specifically, the temperature is lower than 120°C, preferably lower than 115°C. The reason is not yet clear, but it is believed that the value is reduced because the starch granules are destroyed by subjecting the raw materials and / or green dough containing starch to high-temperature strong mixing treatment. In the composition in which the starch granules are destroyed, there is also a situation where the gelatinization peak temperature is suspected to be presented due to the swelling of the components with water, so the lower limit is not particularly limited, and can usually be set to be higher than 80°C, or higher than 85°C, or higher than 90°C, or higher than 95°C.

[0116] The gelatinization peak temperature in the present invention is a temperature (°C) at which the viscosity turns to a decreasing trend after showing the highest viscosity (cP) within a specified temperature range in the RVA heating process, and is an indicator reflecting the heat resistance of starch granules. For example, for a composition whose viscosity is the highest at the 50°C holding stage immediately after the measurement and whose viscosity decreases thereafter, the gelatinization peak temperature is 50°C, for a composition whose viscosity is the highest at any temperature T°C (50≤T≤140) in the heating stage of 50°C to 140°C and whose viscosity decreases in the heating stage after T°C, the gelatinization peak temperature is T°C, and for a composition whose viscosity is the highest at the 140°C holding stage, the gelatinization peak temperature is 140°C.

[0117] It should be noted that, unless otherwise specified, in the present invention, "a pulverized product of a composition", "a pulverized product of a composition" or "a pulverized composition" refers to a product pulverized using a laser diffraction particle size distribution measuring apparatus so that the particle size d after ultrasonic treatment is 0.0447 W / cm3. 50 and / or 90 (Preferably particle size d 50 and d 90 The particle size d after ultrasonic treatment is about 1000 μm or less. 50 and / or 90 (Preferably particle size d 50 and d 90 The lower limits of the two) are not particularly limited, but are usually preferably 1 μm or more.

[0118] (Degree of gelatinization of starch)

[0119] One of the characteristics of the composition of the present invention is that its starch gelatinization degree is above a specified value. Specifically, the starch gelatinization degree in the composition of the present invention is usually above 50% by mass. Among them, preferably above 60% by mass, particularly preferably above 70% by mass. The upper limit of the gelatinization degree is not particularly limited, as long as it is below 100% by mass. If the gelatinization degree is too high, the starch decomposes and the composition sometimes becomes sticky and of poor quality. Therefore, the upper limit of the gelatinization degree is below 99% by mass, wherein, preferably below 95% by mass, and more preferably below 90% by mass.

[0120] It should be noted that the gelatinization degree of the composition in the present invention is measured by the glucoamylase second method (based on the method of Japan Food Research Laboratories: https: / / web.archive.org / web / 20200611054551 / https: / / www.jfrl.or.jp / storage / file / 221.pdf or https: / / www.jfrl.or.jp / storage / file / 221.pdf) which is a partial modification of the one reported by the Central Institute of Customs Analysis.

[0121] (Characteristics of Molecular Weight Distribution of Starch)

[0122] The composition of the present invention is preferably characterized in that the logarithm of the mass average molecular weight (sometimes also referred to as "weight average molecular weight") obtained from the molecular weight distribution curve obtained by analyzing the purified starch under the following [Condition A], and the ratio of the area under the curve of the range where the logarithm of the molecular weight is 5.0 or more and less than 6.5 (hereinafter referred to as "[value α]" as appropriate), the ratio of the area under the curve of the range where the logarithm of the molecular weight is 6.5 or more and less than 8.0 (hereinafter referred to as "[value β]" as appropriate), and the ratio of the area under the curve of the range where the logarithm of the molecular weight is 8.0 or more and less than 9.5 (hereinafter referred to as "[value γ]" as appropriate) to the total area under the curve of the molecular weight distribution curve (the area under the curve of the molecular weight distribution curve in the range where the logarithm of the molecular weight is 5.0 or more and less than 9.5) satisfy the prescribed conditions. The purified starch is obtained by isothermal treating the composition in 40 times the amount of water at 90°C for 15 minutes and then treating it by the following [Step a].

[0123] It should be noted that in the present invention, "molecular weight distribution" or "molecular weight distribution curve" means a distribution diagram obtained by plotting the logarithm of the molecular weight on the horizontal axis (X axis) and the percentage (%) of the measured value at each molecular weight logarithm relative to the total measured value of the RI detector in the entire measurement range on the vertical axis (Y axis). In addition, when calculating the area under the curve from the molecular weight distribution curve obtained by analyzing the purified starch under the following [condition A], the purified starch is obtained by treating the composition in 40 times the amount of water at 90°C for 15 minutes and then treating it by the following [step a], the entire curve is numerically corrected so that the lowest value in the measurement range is 0, and then the molecular weight logarithm is plotted at equal intervals on the horizontal axis (X axis) to calculate the area under the curve, thereby appropriately evaluating the low molecular weight fraction (fraction near [value α]) that has a great impact on quality but is under-evaluated in molecular weight conversion.

[0124] [Step a]:

[0125] The above-mentioned [step a] is a step of purifying starch by pulverizing the 2.5% aqueous dispersion of the composition together with the composition in the liquid, and treating it with a proteolytic enzyme to obtain a component that is insoluble in ethanol and soluble in dimethyl sulfoxide. The technical significance of such [step a] is that, while removing impurities such as proteins with relatively close molecular sizes, the starch is purified by utilizing the properties of being insoluble in ethanol and soluble in dimethyl sulfoxide, thereby preventing column clogging during gel filtration chromatography and improving the accuracy and reproducibility of analysis.

[0126] The pulverization treatment after the isothermal treatment in [step a] may be any method that can sufficiently homogenize the composition, and for example, it may be performed by using a homogenizer NS52 (manufactured by Microtech Nichion) at, for example, 25,000 rpm for 30 seconds.

[0127] The proteolytic enzyme treatment in [step a] may be any treatment that can sufficiently enzymatically hydrolyze the protein in the composition, and may be performed by adding, for example, 0.5% by mass of a proteolytic enzyme (Protease K manufactured by Takara Bio, product code 9034) to the composition that has been subjected to a pulverization treatment, and reacting the mixture at 20° C. for 16 hours.

[0128] In addition, the extraction of the ethanol-insoluble and dimethyl sulfoxide-soluble components in the [step a] is not limited, and may be performed, for example, as follows. That is, (i) 240 times the amount of 99.5% ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) is added to the composition subjected to the pulverization treatment and the protease treatment based on the composition used initially, and after mixing, centrifugation (for example, at 10,000 rpm for 5 minutes) is performed to obtain an ethanol-insoluble fraction. Next, (ii) 80 times the amount of dimethyl sulfoxide (CAS 67-68-5, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) is added to the obtained ethanol-insoluble fraction based on the composition used initially, and the mixture is treated at 90° C. for 10 minutes while stirring to dissolve the mixture, and the dissolved solution is centrifuged (10,000 rpm for 5 minutes), and the supernatant is recovered to obtain a dimethyl sulfoxide-soluble fraction dissolved in dimethyl sulfoxide. Next, (iii) to the obtained dimethyl sulfoxide-soluble fraction dissolved in dimethyl sulfoxide, 99.5% ethanol in an amount 240 times that of the composition initially used is added, mixed, and then centrifuged (10,000 rpm, 5 minutes) to recover the precipitate fraction. Then, (iv) the above (iii) is repeated three times, and the finally obtained precipitate is dried under reduced pressure to obtain a component that is insoluble in ethanol and soluble in dimethyl sulfoxide as purified starch.

[0129] ·[Condition A]:

[0130] The above-mentioned [Condition A] is a condition in which 0.10 mass % of purified starch is dissolved in a 1M sodium hydroxide aqueous solution, and after standing at 37°C for 30 minutes, an equal amount of water and an equal amount of eluent (for example, 0.05M NaOH / 0.2% NaCl) are added, and 5 mL of the filtrate obtained by filtering through a 5μm filter is subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm being greater than 5.0 and less than 9.5.

[0131] The technical significance of such [Condition A] is that insoluble coarse foreign matter can be removed from starch dissolved in water under alkaline conditions by filtering through a filter, thereby preventing column clogging during gel filtration chromatography and improving the accuracy and reproducibility of analysis.

[0132] Gel filtration chromatography:

[0133] In the present invention, for the purified starch obtained by treating the composition in 40 times the amount of water at 90°C for 15 minutes and then treating it by the above [step a], the above filtrate obtained under the above [condition A] is subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm of 5.0 or more and less than 9.5. By analyzing the molecular weight distribution curve obtained in this way after data correction so that the minimum value is 0, the mass average molecular weight logarithm and [value α] (the ratio of the area under the curve of the interval where the molecular weight logarithm is 5.0 or more and less than 6.5 relative to the total area under the curve obtained from the molecular weight distribution curve), [value β] (the ratio of the area under the curve of the interval where the molecular weight logarithm is 6.5 or more and less than 8.0 relative to the total area under the curve obtained from the molecular weight distribution curve) and [value γ] (the ratio of the area under the curve of the interval where the molecular weight logarithm is 8.0 or more and less than 9.5 relative to the total area under the curve obtained from the molecular weight distribution curve). Therefore, it is desirable that the gel filtration chromatography is appropriately set to obtain these values.

[0134] Therefore, in the present invention, as the gel filtration column of gel filtration chromatography, in the molecular weight logarithm of more than 5.0 and less than 9.5 that becomes the object of determination, particularly use the gel filtration column with the common logarithm value of the exclusion limit molecular weight (Da) in the intermediate molecular weight logarithm range (more than 6.5 and less than 8.0) and below (less than 6.5). And, use a plurality of gel filtration columns with different exclusion limit molecular weights in the above-mentioned range, they are connected in series (in series shape) from the upstream side of the analysis successively in the mode of excluding limit molecular weight from large to small. By making such a structure, starch with the molecular weight logarithm (more than 6.5 and less than 8.0) equivalent to the middle [value β], starch with the molecular weight logarithm (more than 5.0 and less than 6.5) equivalent to the smaller [value α] and / or starch with the molecular weight logarithm (more than 8.0 and less than 9.5) equivalent to the larger [value γ] can be separated, and each parameter is appropriately measured.

[0135] A specific example of such a combination of gel filtration columns is a combination of the following four columns connected in series.

[0136] TOYOPEARL HW-75S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 7.7 Da, average pore diameter of 100 nm or more, Φ2 cm×30 cm): 2 pieces.

[0137] TOYOPEARL HW-65S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 6.6 Da, average pore diameter 100 nm, Φ2 cm×30 cm); 1 piece.

[0138] TOYOPEARL HW-55S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 5.8 Da, average pore diameter 50 nm, Φ2 cm×30 cm): 1 piece.

[0139] The eluent for gel filtration chromatography is not limited, and for example, 0.05 M NaOH / 0.2% NaCl can be used.

[0140] The conditions for gel filtration chromatography are not limited, and analysis can be performed, for example, at a column oven temperature of 40° C., a flow rate of 1 mL / min, and a unit time of 0.5 seconds.

[0141] The detection device for gel filtration chromatography is not limited, and examples thereof include an RI detector (RI-8021 manufactured by TOSOH CORPORATION).

[0142] The data analysis method of gel filtration chromatography is not limited, and as a specific example, the following method can be cited. That is, among the measured values ​​obtained by the detection device, for the values ​​within the molecular weight logarithm range (5.0 or more and less than 9.5) of the measured object, after data correction is performed so that the minimum value is 0, the peak dissolution time of the two-point size exclusion chromatography linear standard amylopectin marker (such as P400 (DP2200, MW380000) and P1600 (DP9650, MW1660000) manufactured by Showa Denko Co., Ltd.) is converted into the common logarithm of the molecular weight (logarithm of molecular weight) using a calibration curve. By converting the dissolution time into the molecular weight logarithm in this way, the measured data in which the molecular weight logarithm is evenly distributed can be obtained. In addition, when the total of the measured values ​​of the detection device for each dissolution time within the molecular weight logarithm range of the measurement object (5.0 or more and less than 9.5) (more specifically, the measured values ​​obtained at a column oven temperature of 40°C and a flow rate of 1 mL / min per unit time of 0.5 seconds) is set to 100, the measured value of each dissolution time (molecular weight logarithm) is expressed as a percentage, and the molecular weight distribution of the measurement sample is calculated (X-axis: molecular weight logarithm, Y-axis: percentage (%) of the measured value at each molecular weight logarithm relative to the total of the RI detector measured values ​​in the entire measurement range), and a molecular weight distribution curve can be prepared.

[0143] ·The value of logarithm of mass average molecular weight:

[0144] The composition of the present invention is preferably a composition having excellent elasticity, which is sometimes formed by the mass average molecular weight logarithm obtained by the molecular weight distribution obtained according to the above steps being above a specified value. Specifically, the mass average molecular weight logarithm of the composition of the present invention (the common logarithm value of the mass average molecular weight) is preferably above 6.0. Among them, it is desired to be above 6.1, further desired to be above 6.2, particularly desired to be above 6.3, and particularly desired to be above 6.4. On the other hand, the upper limit of such a value is not particularly limited, and is usually below 9.0, wherein, it is preferably below 8.5, and particularly preferably below 8.0.

[0145] It should be noted that the calculation of the mass average molecular weight can be obtained according to the following steps based on the molecular weight distribution curve obtained according to the above steps. That is, for the values ​​within the molecular weight logarithm range (5.0 or more and less than 9.5) of the measurement object obtained according to the above steps, the values ​​obtained by multiplying each molecular weight converted by the dissolution time by 1 / 100 of the value of the Y axis in the above molecular weight distribution (the percentage of the measurement value at each molecular weight relative to the total of the RI detector measurement value of the entire measurement range) are accumulated to obtain the mass average molecular weight, and then the common logarithm thereof is calculated to obtain the logarithm of the mass average molecular weight. For example, when the percentage % of the measured values ​​at each molecular weight relative to the total of the measured values ​​of the RI detector in the entire measurement range at the molecular weight logarithm of 5.0 is 10%, first, the value obtained by multiplying the molecular weight 100,000 calculated from the molecular weight logarithm of 5.0 by the value of 1 / 100 of 10% (0.10) is calculated, and the same calculation is performed on the entire measurement object range (molecular weight logarithm greater than 5.0 and less than 9.5), and these values ​​are added together to obtain the mass average molecular weight, and then the common logarithm thereof is calculated to obtain the mass average molecular weight logarithm.

[0146] The logarithm of molecular weight is the ratio of the area under the curve within a specified range:

[0147] The composition of the present invention preferably satisfies the following conditions in terms of the ratio [value α] of the area under the curve in the range where the molecular weight logarithm is 5.0 or more and less than 6.5, the ratio [value β] of the area under the curve in the range where the molecular weight logarithm is 6.5 or more and less than 8.0, and the ratio [value γ] of the area under the curve in the range where the molecular weight logarithm is 8.0 or more and less than 9.5, as well as the ratio (β / α) of [value β] to [value α] and the ratio (β / γ) of [value β] to [value γ], relative to the total area under the curve (area under the curve of the molecular weight distribution curve in the range where the molecular weight logarithm is 5.0 or more and less than 9.5) obtained by analyzing the purified starch in the above step (condition A), wherein the purified starch is obtained by isothermal treating the composition in 40 times the amount of water at 90°C for 15 minutes and then treating it by the following [step a]. In addition, the values ​​of these [value α], [value β] and [value γ] are obtained by calculating the ratio of the area under the curve of the corresponding molecular weight logarithm range (for example, in the case of [value α], the range where the molecular weight logarithm is 5.0 or more and less than 6.5) to the area under the curve (total area under the curve) of the entire measurement range of the molecular weight distribution curve (molecular weight logarithm is 5.0 or more and less than 9.5).

[0148] [value α]:

[0149] One of the characteristics of the composition of the present invention is that the ratio [value α] of the area under the curve of the interval where the molecular weight logarithm is greater than 5.0 and less than 6.5 is less than a specified value. Here, [value α] can be considered to be a value representing the ratio of starch degradation products derived from amylose and higher molecular weight starch in the starch degradation products obtained by decomposing the starch in the composition according to the above steps. Specifically, [value α] is 60% or less. Among them, it is desirable to be less than 55%, more desirably less than 50%, particularly desirably less than 45%, or less than 40%, and particularly desirably less than 35%. On the other hand, the lower limit of such a ratio is not particularly limited, and from the perspective of industrial productivity, it is generally more than 10%, and more desirably more than 20%.

[0150] It should be noted that in the molecular weight distribution curve of the composition of the present invention, preferably one or more peaks are visible, and more preferably only one peak is visible, in the range of the molecular weight logarithm corresponding to the above-mentioned [value α] being 5.0 or more and less than 6.5. The composition of the present invention is preferably a composition whose viscosity is suppressed when water is retained when heated with water because the content of such a starch fraction with a relatively small molecular weight is relatively small. The principle is not clear, but these starches with a small molecular weight are easy to flow out of the composition when heated, which may cause viscosity when water is retained.

[0151] Amylose content:

[0152] It should be noted that, as described above, the ratio of the area under the curve where the molecular weight logarithm is 5.0 or more and less than 6.5 [value α] can be considered to be a value showing the ratio of starch degradation products derived from amylose and higher molecular weight starch in the starch degradation products obtained by decomposing the starch in the composition according to the above steps. Correspondingly, the ratio of the amylose content relative to the total starch contained in the composition of the present invention is usually 60% by mass or less, wherein it is desirable to be 55% by mass or less, further desirable to be 50% by mass or less, particularly desirable to be 45% by mass or less or 40% by mass or less, and particularly desirable to be 35% by mass or less. On the other hand, the lower limit of such a ratio is not particularly limited, and from the perspective of industrial productivity, it is usually 10% by mass or more, and further desirable to be 20% by mass or more. It should be noted that "water retention" in the present invention refers to a state in which the dry basis moisture content of the composition is 50% by mass or more.

[0153] [value β]:

[0154] One of the characteristics of the composition of the present invention is that the ratio of the area under the curve where the molecular weight logarithm is greater than 6.5 and less than 8.0 [value β] is greater than a specified value. Here, [value β] can be considered to be a value showing the total ratio of starch degradation products mainly derived from special amylopectin with a smaller molecular weight in amylopectin and starch with a higher molecular weight, among the starch degradation products obtained by decomposing the starch in the composition according to the above steps. Specifically, [value β] is usually 35% or more. Among them, it is desirable to be 40% or more, further desirable to be 45% or more, particularly desirable to be 50% or more or 55% or more, and particularly desirable to be 60% or more. On the other hand, the upper limit of such a ratio is not particularly limited, and from the perspective of industrial productivity, it is usually 90% or less, and further desirable to be 80% or less.

[0155] It should be noted that, in the molecular weight distribution curve, the composition of the present invention preferably has more than one peak, and more preferably only one peak, within the range of molecular weight logarithm of 6.5 or more and less than 8.0. Since it contains relatively more starch fractions with intermediate molecular weight, the composition of the present invention sometimes forms a composition with suppressed viscosity when heated with water, and is therefore preferred. The principle is not yet clear, but these starches with relatively intermediate molecular weight do not have a structure that causes viscosity that starches with higher molecular weight have, and may have a physical property of suppressed viscosity despite hydration.

[0156] Amylopectin content:

[0157] It should be noted that the ratio of the area under the curve where the molecular weight logarithm is 6.5 or more and less than 8.0 [value β] can be considered to be a value showing the ratio of special amylopectin with a smaller molecular weight mainly derived from amylopectin in the starch decomposition product obtained by decomposing the starch in the composition according to the above steps. Correspondingly, the amylopectin content relative to the total starch contained in the composition of the present invention is usually 35% by mass or more, wherein it is desired to be 40% by mass or more, further desired to be 45% by mass or more, particularly desired to be 50% by mass or more or 55% by mass or more, and particularly desired to be 60% by mass or more. On the other hand, the upper limit of such a ratio is not particularly limited, and from the viewpoint of industrial productivity, it is usually 90% by mass or less, and further desired to be 80% by mass or less.

[0158] The ratio of [value β] to [value α] (β / α):

[0159] The composition of the present invention is preferred because the ratio (β / α) of the above-mentioned [value β] to the [value α] is greater than the specified value, so the characteristics of the [value β] are further prominent, forming a composition with a better taste. Specifically, the ratio (β / α) of the above-mentioned [value β] to the [value α] is usually greater than 0.5, preferably greater than 0.6, more preferably greater than 0.7, particularly preferably greater than 0.8 or greater than 0.9, and particularly preferably greater than 1.0. On the other hand, the upper limit of such a ratio is not particularly limited. From the perspective of industrial productivity, the value α may be 0 mass % and the value β / value α cannot be calculated, further may be less than 5.0, further may be less than 4.0, and particularly may be less than 3.0.

[0160] [value γ]:

[0161] The composition of the present invention preferably has a ratio [value γ] of the area under the curve where the molecular weight logarithm is greater than 8.0 and less than 9.5, which is less than a specified value. Here, [value γ] can be considered to be a value of the ratio of high molecular weight branched starch that is characteristically visible mainly in rice starch, etc., in the starch degradation product obtained by decomposing the starch in the composition according to the above steps. Specifically, [value γ] is preferably 30% or less. Among them, it is desirable to be less than 25%, further desirable to be less than 20%, particularly desirable to be less than 15% or less than 10%, and particularly desirable to be less than 5%. On the other hand, the lower limit of such a ratio is not particularly limited, and from the perspective of industrial productivity, it is usually 0% or more.

[0162] In addition, the composition of the present invention preferably does not see a peak derived from high molecular weight amylopectin, which is characteristically seen in rice starch, etc., within the range of the molecular weight logarithm of 8.0 or more and less than 9.5. Since the composition of the present invention contains relatively little of such a starch fraction with a high molecular weight, the viscosity of the composition of the present invention may be suppressed when heated with water, so it is preferred. The principle is not clear, but these starches with a high molecular weight have a structure that causes viscosity, and since the ratio is high, it is possible to form a composition with high viscosity.

[0163] The ratio of [value β] to [value γ] (β / γ):

[0164] The composition of the present invention is further preferred because the ratio (β / γ) of the above-mentioned [value β] to the [value γ] is greater than the specified value, so the viscosity is further suppressed, and a composition with a better taste is formed. Specifically, the ratio (β / γ) of the above-mentioned [value β] to the [value γ] is usually greater than 10 or greater than 15, preferably greater than 20, more preferably greater than 25, particularly preferably greater than 30 or greater than 40, and particularly preferably greater than 50. On the other hand, the upper limit of such a ratio is not particularly limited. From the perspective of industrial productivity, the value γ may be 0 mass % and the value β / value γ cannot be calculated. It may be 1000 or less, further may be 900 or less, preferably 800 or less, preferably 700 or less, and particularly preferably 650 or less.

[0165] (Iodine staining)

[0166] The composition of the present invention is preferred because the iodine staining property of a specific molecular weight logarithmic fraction is below a specified value, so the elasticity reduction of the composition of the present invention during storage is suppressed. Specifically, the purified starch obtained by rapidly treating the composition in the above [step a] after adding the composition to 40 times the amount of water is separated and recovered under the above [condition A], and the separated fraction having a molecular weight logarithm of 5.0 or more and less than 6.5 is adjusted to pH 7.0, and the absorbance at 660 nm when 1 mass part of the sample is put into 9 mass parts of 0.25 mM iodine solution for staining is measured, and the absorbance at 660 nm of a 0.25 mM iodine solution as a blank (not containing the measurement sample) is subtracted from the absorbance to obtain a corrected value (which is appropriately referred to as "ABS"). 5.0-6.5 ”), the ABS 5.0-6.5 The value of is preferably below a specified value.

[0167] The ABS obtained by the composition of the present invention according to the following steps 5.0-6.5 The value of is usually 0.80 or less, preferably 0.75 or less, more preferably 0.70 or less, especially preferably 0.65 or less, or 0.60 or less, or 0.55 or less, or 0.50 or less, or 0.45 or less, or 0.40 or less, or 0.35 or less, and especially preferably 0.30 or less. On the other hand, the lower limit of such a value is not particularly limited, but is usually -0.20 or more, further -0.10 or more, and preferably 0.00 or more, or 0.10 or more, or 0.20 or more. The principle is not clear, but it is presumed that this is because the ABS 5.0-6.5A composition with a high value of is likely to contain a large amount of starch degradation products derived from starch fractions with a larger molecular weight (it is believed that this is mainly due to thermal decomposition of branched starch contained in the fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 due to overheating to form degradation products with a molecular weight logarithm of 5.0 or more and less than 6.5). Such starch degradation products sometimes have the characteristic that their elasticity is easily reduced when water is added.

[0168] It should be noted that the above ABS 5.0-6.5 The detailed determination method of the value is as follows. First, after the composition is added to 40 times the amount of water, it is quickly (that is, not subjected to a constant temperature treatment at 90°C for 15 minutes) treated by the above [step a] to obtain purified starch. Next, the purified starch is separated under the above [condition A] to recover a separation fraction having a molecular weight logarithm of greater than 5.0 and less than 6.5. The details of the above [step a] and the above [condition A] are as described above. Next, after the obtained separation fraction is adjusted to pH 7.0, 1 mass part of the sample is put into 9 mass parts of 0.25 mM iodine solution, and after standing at room temperature (20°C) for 3 minutes, it is subjected to absorbance measurement. When measuring absorbance, the iodine solution before adding the sample (control) and the iodine solution after adding the composition are respectively measured for absorbance (660 nm) using a conventional spectrophotometer (e.g., UV-1800 manufactured by Shimadzu Corporation) using a square colorimetric cell with an optical path length of 10 mm, and the absorbance difference between the two (absorbance of the iodine solution after adding the sample - absorbance of the iodine solution before adding the sample) is calculated, and the difference is obtained as ABS 5.0-6.5 That's it.

[0169] In addition, the composition of the present invention preferably has a larger molecular weight, and the separated fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 has higher iodine staining than the separated fraction with a molecular weight logarithm of 5.0 or more and less than 6.5. Specifically, the purified starch obtained by quickly treating the composition in 40 times the amount of water by the above [step a] is separated and recovered under the above [condition A], and the separated fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 is adjusted to pH 7.0, and the absorbance at 660 nm when 1 mass part of the sample is put into 9 mass parts of 0.25 mM iodine solution for staining is measured, and the absorbance at 660 nm of the 0.25 mM iodine solution as a blank (not containing the measured sample) is subtracted from the absorbance to obtain a corrected value (which is appropriately referred to as "ABS"). 6.5-8.0 ”), it is preferred that the ABS 6.5-8.0 With the above ABS 5.0-6.5 The value of the ratio (ABS 6.5-8.0 / ABS 5.0.-6.5 ) is above the specified value.

[0170] The ABS obtained by the composition of the present invention according to the following steps 6.5-8.0 / ABS 5.0-6.5 The value of is usually more than 0.003, wherein it is desired to be more than 0.005, further desired to be more than 0.007, especially desired to be more than 0.009, or more than 0.010, or more than 0.020, or more than 0.030, or more than 0.040, or more than 0.050, or more than 0.060, and particularly desired to be more than 0.070. On the other hand, the upper limit of such a value is not particularly limited, and is usually less than 1.000, and further less than 0.9000. Its principle is not yet clear, but it is speculated that because the proportion of starch decomposed by heat in the process is relatively less relative to the starch before decomposition, the ratio increases, and finally forms a composition of good quality.

[0171] It should be noted that ABS 6.5-8.0 The details of the determination method of ABS are as follows except that the separated fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 is used. 5.0-6.5 The details of the measurement method are the same.

[0172] (Amylolytic enzyme activity)

[0173] The composition of the present invention is preferably because the amylolytic enzyme activity contained is below a certain degree, and the hydration power of the composition can be maintained. Its principle is not yet clear, but it is believed that by making the decomposition enzyme act on the starch in the composition under water-containing conditions, the high molecular weight starch with high hydration power is decomposed and reduced. Specifically, the amylolytic enzyme activity of the composition is usually below 30.0U / g in terms of dry mass conversion, wherein it is desired to be below 25.0U / g, or below 22.0U / g, or below 20.0U / g, further desired to be below 18.0U / g, especially desired to be below 16.0U / g, or below 14.0U / g, or below 12.0U / g, or below 10.0U / g, or below 8.0U / g, or below 6.0U / g, especially desired to be below 4.0U / g. On the other hand, the lower limit of such a ratio is not particularly limited, and is usually more than 0.0U / g.

[0174] It should be noted that the amylolytic enzyme activity is not limited and can be measured, for example, by the following method.

[0175] Preparation of enzyme solution:

[0176] 10 mL of 0.5% NaCl / 10 mM acetate buffer (pH 5) was added to 1 g of the crushed test sample, and the mixture was allowed to stand at 4°C for 16 hours. The mixture was then broken into a paste using a homogenizer NS52 (manufactured by Microtech Nichion) at 25,000 rpm for 30 seconds. The mixture was further allowed to stand at 4°C for 16 hours, and the filtrate obtained by filtering with filter paper (manufactured by ADVANTEC, qualitative filter paper No. 2) was used as the enzyme solution.

[0177] Activity assay:

[0178] 2 mL of 0.05% soluble starch (Fujifilm Wako Pure Chemical Industries, Ltd., starch (soluble) CAS9005-25-8, product code 195-03961) was placed in a test tube, and after standing at 37°C for 10 minutes, 0.25 mL of the above enzyme solution was added and mixed. After the mixture was allowed to stand at 37°C for 30 minutes, 0.25 mL of 1M HCl was added and mixed. Then, 0.25 mL of iodine-potassium iodide solution containing 0.05 mol / L iodine (0.05 mol / L iodine solution: Fujifilm Wako Pure Chemical Industries, Ltd. (product code 091-00475)) was added and mixed, and 11.5 mL of water was added for dilution, and the absorbance (absorbance A) at a wavelength of 660 nm was measured using a spectrophotometer. In addition, as a control, 2 mL of 0.05% soluble starch was placed in a test tube and allowed to stand at 37°C for 40 minutes. Then, 0.25 mL of 1M HCl was added and mixed. Then, 0.25 mL of enzyme solution and 0.25 mL of 0.05 mol / L iodine solution were added and mixed in that order. After dilution with 11.5 mL of water, the absorbance at a wavelength of 660 nm was measured using a spectrophotometer (absorbance B). The iodine solution in the present invention refers to a diluent of an iodine-potassium iodide solution (sometimes referred to as "0.05 mol / L iodine solution" or "0.05 mol / L iodine solution" in the present invention) containing 0.05 mol / L iodine. Unless otherwise specified, a mixed iodine-potassium iodide solution ("0.05 mol / L iodine solution (product code 091-00475)" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) containing 93.7 mass % of water, 0.24 mol / L (4.0 mass %) of potassium iodide, and 0.05 mol / L (1.3 mass %) of iodine is used after dilution. In addition, by diluting the "0.05 mol / L iodine solution" 200 times with water, a "0.25 mM iodine solution" can be obtained.

[0179] Enzyme activity unit (U / g):

[0180] The absorbance reduction rate C (%) at a wavelength of 660 nm measured by a spectrophotometer before and after the sample was subjected to an enzyme reaction for 30 minutes was determined by the absorbance reduction rate of the enzyme reaction area (absorbance A) relative to the comparison area (absorbance B) ({(absorbance B-absorbance A) / absorbance B}×100 (%)). The enzyme activity at which the absorbance decreases by 10% every 10 minutes is defined as 1 unit (U), and the enzyme activity per 1 g of the sample was determined by the following formula based on the absorbance reduction rate C (%) when the enzyme reaction was carried out for 30 minutes using 0.25 mL of the enzyme solution (sample content 0.025 g).

[0181] [Mathematical formula 1]

[0182] Enzyme activity unit (U / g) = {C × (10 / 30) × (1 / 10)} / 0.025

[0183] (protein)

[0184] The composition of the present invention preferably contains protein. The lower limit of the protein content in the composition of the present invention is usually 3.0% by mass or more in terms of dry mass, wherein, preferably 3.5% by mass or more, more preferably 4.0% by mass or more, particularly preferably 4.5% by mass or more, or 5% by mass or more, wherein, preferably 6% by mass or more, more preferably 7% by mass or more, particularly preferably 8% by mass or more, or 9% by mass or more, or 10% by mass or more, or 11% by mass or more, or 12% by mass or more, or 13% by mass or more, or 14% by mass or more, or 15% by mass or more, or 16% by mass or more, or 17% by mass or more, or 18% by mass or more, or 19% by mass or more, or 20% by mass or more, or 21% by mass or more, particularly preferably 22% by mass or more. On the other hand, the upper limit of the protein content in the composition of the present invention is not particularly limited, but is usually 85% by mass or less, preferably 80% by mass or less, more preferably 75% by mass or less, more preferably 70% by mass or less, more preferably 65% ​​by mass or less, and more preferably 60% by mass or less, in terms of dry mass.

[0185] The source of protein in the composition of the present invention is not particularly limited. As an example, plant-derived protein or animal-derived protein can be cited, preferably protein derived from beans. Specifically, the ratio of the protein content derived from beans relative to the total protein content of the entire composition is usually 10% by mass or more, wherein, preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 40% by mass or more, or 50% by mass or more, or 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more, particularly preferably 100% by mass. As a protein derived from beans, a protein derived from peas is particularly preferred, and a protein derived from yellow peas is most preferred.

[0186] The protein in the composition of the present invention can be blended into the composition as an isolated pure product, and is preferably blended into the composition in a state contained in beans. Specifically, the ratio of the protein content blended in a state contained in beans relative to the total protein content of the entire composition is usually 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 40% by mass or more, or 50% by mass or more, or 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more, and particularly preferably 100% by mass.

[0187] It should be noted that in the present invention, the protein content in the composition is determined by multiplying the total nitrogen ratio measured by the combustion method (modified Dumas method) specified in the food labeling method ("About Food Labeling Standards" (Digestive Table No. 139 of March 30, 2011)) by a "nitrogen-protein conversion coefficient".

[0188] (PDI of protein)

[0189] The protein contained in the composition of the present invention can give a chewy feeling to the composition due to its reduced solubility, and give a mouthfeel that is easy to chew, and is therefore more preferred. Its principle is not yet clear, but it is considered that insoluble protein has an impact on the mouthfeel of starch. Specifically, the PDI (protein dispersibility index) value of the composition of the present invention is preferably less than 55 mass %. Wherein, it is desired to be less than 50 mass %, further to be less than 45 mass %, particularly to be less than 40 mass %, or less than 35 mass %, or less than 30 mass %, or less than 25 mass %, or less than 20 mass %, or less than 15 mass %, particularly to be less than 10 mass %. On the other hand, the lower limit of such a ratio is not particularly limited, and is generally more than 0 mass %, further more than 2 mass %, wherein more than 4 mass %.

[0190] It should be noted that the PDI (protein dispersibility index) value is an index indicating the solubility of protein, and can be obtained as a percentage of the water-soluble nitrogen ratio relative to the total nitrogen ratio of the entire composition according to a conventional method (water-soluble nitrogen ratio / total nitrogen ratio of the entire composition × 100 (%)). Specifically, 20 times the amount of water is added to the test sample, and a crushing treatment is performed (using a homogenizer NS-310E3 manufactured by Microtech Nichion to crush the sample at 8500 rpm for 10 minutes), and the total nitrogen ratio of the crushed liquid obtained is multiplied by 20 to obtain a value as the total nitrogen ratio of the entire composition. Then, the crushed liquid is centrifuged (at 3000G for 10 minutes), and the total nitrogen ratio of the supernatant obtained is multiplied by 20 to obtain a value as the water-soluble nitrogen ratio, thereby calculating the PDI value of the composition. The total nitrogen ratio is measured by the combustion method (modified Dumas method) specified in the Food Labeling Method ("About Food Labeling Standards" (Digestion Table No. 139, March 30, 2011)).

[0191] (Insoluble dietary fiber content)

[0192] The composition of the present invention contains insoluble dietary fiber. In the present invention, "insoluble dietary fiber" refers to a water-insoluble substance in the indigestible components of food that cannot be digested by human digestive enzymes. Its quantitative determination is carried out according to the Japanese Food Standard Composition Table 2015 edition (seventh edition) using the modified Prosky method. Even if the composition of the present invention has a large content of insoluble dietary fiber, it will not form a composition with a dry mouthfeel, so it is useful. The reason is not yet clear, but through high temperature, high pressure and high mixing treatment, the dietary fiber in the composition interacts with starch and protein to form a network structure, thereby potentially improving the mouthfeel of the insoluble dietary fiber.

[0193] The lower limit of the content of the insoluble dietary fiber in the composition of the present invention is usually preferably more than 2.0 mass % with dry mass conversion. Wherein, preferably more than 3 mass %, more preferably more than 4 mass %, especially preferably more than 5 mass %, or more than 6 mass %, or more than 7 mass %, or more than 8 mass %, or more than 9 mass %, particularly preferably more than 10 mass %. By making the content of insoluble dietary fiber more than the above-mentioned lower limit, the composition of the present invention can make insoluble dietary fiber be evenly dispersed in the starch diffused into a matrix with an appropriate size, and it is easy to have a structure of starch matrix distribution, so as to easily improve the mouthfeel like rubber. Here, in the present invention, "dry mass" represents the mass of the remainder after removing the moisture content calculated by the following "moisture content (dry basis moisture content)" from the overall mass of the composition, and "converted with dry mass" represents the ratio of each component calculated as the denominator and the content of each component as the numerator.

[0194] The upper limit of the insoluble dietary fiber content in the composition of the present invention is not particularly limited, but is generally 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less, in terms of dry mass, from the viewpoint of industrial production efficiency.

[0195] The source of the insoluble dietary fiber contained in the composition of the present invention is not particularly limited, and can be the insoluble dietary fiber derived from various natural materials containing insoluble dietary fiber, or can be synthetic insoluble dietary fiber. When derived from natural materials, the insoluble dietary fiber contained in various materials can be separated, purified and used, or the material containing such insoluble dietary fiber can be directly used. For example, the insoluble dietary fiber derived from cereals, the insoluble dietary fiber derived from beans, the insoluble dietary fiber derived from taro, the insoluble dietary fiber derived from vegetables, the insoluble dietary fiber derived from seeds, the insoluble dietary fiber derived from fruits, etc. can be used, from the viewpoint of the texture of the composition, more preferably the insoluble dietary fiber derived from cereals, the insoluble dietary fiber derived from beans, further preferably the insoluble dietary fiber derived from beans, particularly preferably the insoluble dietary fiber derived from peas, most preferably the insoluble dietary fiber derived from yellow peas. When the beans are derived from beans, they may be used with or without the seed coat. However, beans with the seed coat are preferably used because they contain a larger amount of dietary fiber.

[0196] In addition, the insoluble dietary fiber in the composition of the present invention can be blended in the composition as the pure product of separation, preferably blended in the composition with the state contained in beans.Specifically, the ratio of the insoluble dietary fiber content blended with the state contained in beans relative to the total insoluble dietary fiber content of the entire composition is usually more than 10 mass %, wherein, preferably more than 20 mass %, more preferably more than 30 mass %, especially preferably more than 40 mass %, or more than 50 mass %, or more than 60 mass %, or more than 70 mass %, or more than 80 mass %, or more than 90 mass %, especially preferably 100 mass %.

[0197] The composition of the insoluble dietary fiber contained in the composition of the present invention is not particularly limited. However, if the ratio of lignin (especially acid-soluble lignin) in the overall insoluble dietary fiber is above a certain value, it is easy to obtain a more significant effect of improving the mouthfeel. Specifically, the ratio of lignin (especially acid-soluble lignin) in the overall insoluble dietary fiber is usually more than 5% by mass in terms of dry mass conversion, wherein, preferably more than 10% by mass, more preferably more than 30% by mass.

[0198] (Particle size distribution of insoluble dietary fiber)

[0199] The particle size of the insoluble dietary fiber preferably contained in the composition of the present invention is below a certain degree. If the particle size of the insoluble dietary fiber is too large, the composition sometimes forms a dry and bad mouthfeel. The reason is not clear, but it is believed that it is because the thick insoluble dietary fiber hinders the matrix structure formation of starch, etc., so as to be difficult to exert the effect of the present invention. Here, the possibility that the insoluble dietary fiber size in the bean powder that is usually broken blindly exceeds 450 μm is high (this is because the shape of the insoluble dietary fiber contained in the beans is usually rod-shaped, and a large value can be obtained in the laser diffraction type particle size distribution measurement of the present invention). Particularly in the case of using the beans with seed coat and other foods containing hard tissues in the raw material, the insoluble dietary fiber of its seed coat part is thick, and it is difficult to break compared with the edible part, so in the case of using such foods in the present invention, the insoluble dietary fiber contained in such foods is preferably subjected to specific crushing treatment in advance, and its size is the insoluble dietary fiber of a specific range.

[0200] In the present invention, in order to evaluate the particle size of the insoluble dietary fiber in the composition, the following method is used: for the starch-protein decomposition treatment composition obtained by treating the aqueous suspension of the composition with protease and amylase, and decomposing starch and protein with enzymes, a laser diffraction particle size distribution measuring device is used to measure the particle size distribution after ultrasonic treatment. Specifically, after starch-protein decomposition treatment is implemented by treating a 6% aqueous suspension of the composition with 0.4% by volume of protease and 0.02% by mass of α-amylase at 20°C for 3 days (appropriately as "[step b]"), the treated composition is subjected to ultrasonic treatment and the particle size distribution is measured.

[0201] Specifically, the particle size d in the particle size distribution of the insoluble dietary fiber of the composition of the present invention measured by the above-mentioned steps is 90 Preferably, the particle size d of the insoluble dietary fiber is less than 450 μm, more preferably less than 400 μm, more preferably less than 350 μm, more preferably less than 300 μm, more preferably less than 250 μm, more preferably less than 200 μm, more preferably less than 150 μm, more preferably less than 100 μm, more preferably less than 80 μm, more preferably less than 60 μm, and more preferably less than 50 μm. 90 The lower limit of is not particularly limited, but is usually 1 μm or more, and more preferably 3 μm or more.

[0202] Similarly, the particle size d in the particle size distribution of the insoluble dietary fiber of the composition of the present invention measured by the above-mentioned steps is 50Preferably, the particle size d of the insoluble dietary fiber is less than 450 μm, more preferably less than 400 μm, more preferably less than 350 μm, more preferably less than 300 μm, more preferably less than 250 μm, more preferably less than 200 μm, more preferably less than 150 μm, more preferably less than 100 μm, more preferably less than 80 μm, more preferably less than 60 μm, and more preferably less than 50 μm. 50 The lower limit of is not particularly limited, but is usually 1 μm or more, and more preferably 3 μm or more.

[0203] As a more specific step for measuring the particle size distribution of the insoluble dietary fiber in the composition, for example, as follows. 300mg of the composition is put into a plastic tube together with 5mL of water, and after swelling it for about 1 hour at 20°C, a small Hiscotron (Microtech Nichion homogenizer NS-310E3) is used to process it to a porridge-like physical property (about 15 seconds at 10000rpm). Then, 2.5mL of the processed sample is divided, 10μL of protease (Takara Bio system, Proteinase K), 0.5mg of α-amylase (Sigma company system, α-Amylase from Bacillus subtilis) are added, and it is reacted for 3 days at 20°C. After the reaction ends, the obtained protease and amylase are processed and the composition is subjected to ultrasonic treatment, and then its particle size distribution is measured.

[0204] The determination of the particle size distribution after ultrasonic treatment of protease, amylase treatment composition, bean powder, green composition suspension, etc. uses a laser diffraction particle size distribution measuring device, according to the following conditions. First, the solvent used during the determination is ethanol that is difficult to affect the structure in the composition. As the laser diffraction particle size distribution measuring device used for determination, there is no particular restriction, for example, the Microtrac MT3300EXII system of Microtrac Bell Inc. can be used. As the determination application software, there is no particular restriction, for example, DMS2 (Data Management System version2, Microtrac Bell Inc.) can be used. In the case of using the above-mentioned measuring device and software, when measuring, after pressing the cleaning button of the software to implement cleaning, press the zero (Set zero) button of the software to implement zeroing, and directly put the sample into the sample by sample loading until the concentration of the sample enters the appropriate range. The measurement sample can be put into a sample that has been ultrasonically treated in advance, or it can be ultrasonically treated using the above-mentioned measuring device after the sample is put into the sample, and then measured. In the latter case, a sample that has not been ultrasonically treated is put into, and after the concentration is adjusted to an appropriate range by sample loading, the ultrasonic treatment button of the software is pressed for ultrasonic treatment. Then, after degassing treatment three times, the sample loading treatment is performed again. After confirming that the concentration is still within the appropriate range, laser diffraction is quickly performed at a flow rate of 60% for a measurement time of 10 seconds, and the obtained result is used as the measurement value. As the parameters during the measurement, for example, the distribution representation is set as: volume, particle refractive index: 1.60, solvent refractive index: 1.36, measurement upper limit (μm) = 2000.00μm, and measurement lower limit (μm) = 0.021μm.

[0205] It should be noted that in the present invention, "particle size d 90 ” (or “particle size d 50 ") is defined as a particle size distribution of the object to be measured being measured on a volume basis, and when a certain particle size is divided into two parts, the ratio of the cumulative value of the frequency % of the particles on the larger side to the cumulative value of the frequency % of the particles on the smaller side is 10:90 (or 50:50). In addition, in the present invention, "ultrasonic treatment" means treatment with an ultrasonic wave having a frequency of 40 kHz and an output power of 40 W for 3 minutes unless otherwise specified.

[0206] (Total fat content)

[0207] The total fat component content in the composition of the present invention is not limited, and is converted with dry mass, usually less than 17% by mass, wherein, it is preferably set to be less than 15% by mass, further preferably set to be less than 13% by mass, especially preferably set to be less than 10% by mass, or less than 8% by mass, or less than 7% by mass, or less than 6% by mass, or less than 5% by mass, or less than 4% by mass, or less than 3% by mass, or less than 2% by mass, or less than 1% by mass, and particularly preferably set to be less than 0.8% by mass. On the other hand, the lower limit of such total fat component content is not particularly limited, and is converted with dry mass, and is usually preferably more than 0.01% by mass. It should be noted that in the present invention, the total fat component content in the composition is measured according to the Japanese Food Standard Composition Table 2015 edition (the seventh edition) by the Soxhlet extraction method utilizing ether.

[0208] The source of the oil component in the composition of the present invention is not particularly limited. As an example, an oil component derived from a plant or an oil component derived from an animal can be listed, preferably an oil component derived from a plant. Specifically, the ratio of the oil component content derived from a plant (particularly beans) relative to the total oil component content of the entire composition is usually 50% by mass or more, wherein, preferably 60% by mass or more, more preferably 70% by mass or more, especially preferably 80% by mass or more or 90% by mass or more, particularly preferably 100% by mass. As an example of an oil component derived from a plant, an oil component derived from cereals, an oil component derived from beans, an oil component derived from taro, an oil component derived from vegetables, an oil component derived from seeds, an oil component derived from fruits, etc. can be listed, from the viewpoint of realizing the molecular weight distribution of the above-mentioned preferred starch, it is more preferred to use an oil component derived from beans, particularly preferably an oil component derived from peas, and most preferably an oil component derived from yellow peas.

[0209] The oil component in the composition of the present invention may be derived from various food raw materials of the composition, and may also be added as a separated pure product, preferably mixed into the composition in a state contained in an edible plant (particularly beans). Specifically, the ratio of the content of the oil component mixed in a state contained in an edible plant relative to the total oil component content of the entire composition is usually 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, or 90% by mass or more, and particularly preferably 100% by mass.

[0210] It should be noted that, generally 50% or more by mass, preferably 60% or more by mass, more preferably 70% or more by mass, particularly preferably 80% or more by mass, or 90% or more by mass, and particularly preferably 100% by mass of the fat components in the composition of the present invention are all derived from beans, more preferably from beans of the same type, and further preferably from beans of the same individual. In addition, generally 50% or more by mass, preferably 60% or more by mass, more preferably 70% or more by mass, particularly preferably 80% or more by mass, or 90% or more by mass, and particularly preferably 100% by mass of the fat components in the composition of the present invention are blended in a state contained in edible plants.

[0211] (Dry basis moisture content)

[0212] The composition of the present invention preferably has a dry basis moisture content below a specified value. Specifically, the dry basis moisture content in the composition of the present invention is not limited, for example, 60% by mass or less, or 55% by mass or less, wherein it can be 50% by mass or less, or 45% by mass or less, or 40% by mass or less, or 35% by mass or less, or 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. On the other hand, the lower limit of the dry basis moisture content in the composition of the present invention is not limited, and from the viewpoint of industrial production efficiency, for example, it can be set to more than 0.5% by mass, or more than 1% by mass, or more than 2% by mass. It should be noted that the dry basis moisture content in the composition of the present invention can be derived from the various components of the composition, and can also be derived from the water added. In addition, in the case where the dry basis moisture content contained in the green composition before processing is high, a process adjusted to the above-mentioned numerical value by adopting a drying process or the like can be adopted.

[0213] In the present invention, "dry basis moisture content" refers to the ratio of the total amount of moisture derived from the raw materials of the composition of the present invention and the amount of water added to the total amount of solid components. This value is measured by heating to 90°C by reduced pressure heating drying method according to the Japanese Food Standard Composition Table 2015 Edition (Seventh Edition). Specifically, an appropriate amount of sample is collected and weighed (W1) in a weighing container (W0) with constant weight in advance, and is placed in a reduced pressure electric constant temperature dryer adjusted to a specified temperature (more specifically, 90°C) under normal pressure with the lid or opening of the weighing container removed, the door is closed, the vacuum pump is operated, and the weighing container is dried for a certain period of time at a specified reduced pressure, the vacuum pump is stopped, the dry air is transported to return to normal pressure, the weighing container is taken out, the lid is covered, and the weight is weighed after cooling in the dryer. Drying, cooling, and weighing (W2) are repeated until constant weight is reached, and the moisture content (dry basis moisture content) (mass %) is obtained by the following calculation formula.

[0214] [Mathematical formula 2]

[0215] Water content (drying basis moisture content) (mass %) = (W1-W2) / (W2-W0)×100

[0216] [Wherein, W0 represents the mass of the constant-weight weighing container (g), W1 represents the mass of the weighing container containing the sample before drying (g), and W2 represents the mass of the weighing container containing the sample after drying (g)]

[0217] (raw material)

[0218] The raw materials of the composition of the present invention are not particularly limited as long as they can achieve the various component compositions and physical properties specified in the present invention. However, as raw materials, it is preferred to use one or more edible plants, and as edible plants, it is preferred to contain at least beans.

[0219] Beans:

[0220] In the case of using beans in the composition of the present invention, the kind of beans used is not limited, as an example, preferably selected from more than one beans of pea, Phaseolus, Pigeon, Vigna, Vicia, Garbanzo, Glycine max and Lentil. As a specific example, pea (particularly yellow pea, white pea, etc.), kidney bean (kidney bean), kidney bean, red kidney bean, white kidney bean, black bean, pinto bean, tiger bean, cotton bean, dick bean, pigeon bean, mung bean, cowpea, adzuki bean, broad bean, soybean, chickpea, Lentil, blue bean, purple bean, lentil, peanut, lupine, Lathyrus, carob (carob tree), stink bean, African locust bean, coffee bean, cocoa bean, Mexican jumping bean, etc., but are not limited to these. The classification of other unexemplified food materials, as long as it is a technician in the field of processing the food materials or the processed products of food materials, certainly can be understood. Specifically, it can be clearly understood by referring to the food group classification recorded in the Japanese Standard Food Composition Table 2015 Edition (Seventh Edition) which is also widely used in the daily life of ordinary families (page 249, Table 1). It should be noted that these beans can be used alone or in any combination of two or more.

[0221] It should be noted that, when beans are used in the composition of the present invention, in the starch contained in the composition, due to the increase in the proportion of the intermediate molecular weight fraction (molecular weight logarithm of 6.5 or more and less than 8.0), it is preferred to use mature beans instead of immature seeds (e.g., green peas as immature seeds of peas or edamame as immature seeds of soybeans). In addition, for the same reason, beans in a state where the dry basis moisture content is below a specified value as they mature are preferred. Specifically, the dry basis moisture content of the beans used in the composition of the present invention is generally less than 15% by mass, preferably less than 13% by mass, and more preferably less than 11% by mass or less than 10% by mass. On the other hand, the lower limit of the dry basis moisture content of such beans is not particularly limited, and is generally preferably 0.01% by mass or more.

[0222] When beans are used in the composition of the present invention, the content of beans in the composition of the present invention is not limited, and is usually 50% by mass or more in terms of dry mass, preferably 55% by mass or more, more preferably 60% by mass or more, or 65% by mass or more, or 70% by mass or more, or 75% by mass or more, or 80% by mass or more, or 85% by mass or more, or 90% by mass or more, and particularly preferably 95% by mass or more. The upper limit is not particularly limited, but is usually 100% by mass or less.

[0223] When beans are used in the composition of the present invention, it is preferred to use powdered beans. Specifically, it is preferred to use the following bean powder, wherein the bean powder has a particle size d after ultrasonic treatment measured by a laser diffraction particle size distribution measuring device: 90 and / or 50 That is, the particle size d of the bean powder after ultrasonic treatment is 90 Preferably, the particle size of the bean powder after ultrasonic treatment is less than 500 μm, more preferably less than 450 μm, more preferably less than 400 μm, or less than 350 μm, or less than 300 μm, or less than 250 μm, or less than 200 μm, or less than 150 μm, or less than 100 μm, or less than 90 μm, or less than 80 μm, or less than 70 μm, or less than 60 μm, or less than 50 μm. In addition, similarly, the particle size d of the bean powder after ultrasonic treatment is less than 500 μm, more preferably less than 450 μm, or less than 400 μm, or less than 350 μm, or less than 300 μm, or less than 250 μm, or less than 200 μm, or less than 150 μm, or less than 1 50 The particle size after ultrasonic treatment is preferably less than 500 μm, more preferably less than 450 μm, more preferably less than 400 μm, or less than 350 μm, or less than 300 μm, or less than 250 μm, or less than 200 μm, or less than 150 μm, or less than 100 μm, or less than 90 μm, or less than 80 μm, or less than 70 μm, or less than 60 μm, or less than 50 μm. 90 and d 50The lower limit of is not particularly limited, and is usually 0.3 μm or more, or 1 μm or more, or 5 μm or more, or 10 μm or more. In particular, if the composition is larger than a certain size during extrusion molding, the composition is prone to microvibration during molding, productivity deteriorates, and the surface of the composition sometimes becomes uneven, so it is preferred to use powdered beans with a size below a certain size.

[0224] Other ingredients:

[0225] The composition of the present invention may contain any one or more other food materials. Examples of such food materials include plant food materials (vegetables, taro, mushrooms, fruits, algae, cereals, seeds, etc.), animal food materials (fish, meat, eggs, milk, etc.), microbial foods, etc. The content of these food materials can be appropriately set within the range that does not damage the purpose of the present invention.

[0226] Flavoring agents, food additives, etc.:

[0227] The composition of the present invention may contain any one or more flavoring agents, food additives, etc. Examples of flavoring agents, food additives, etc. include soy sauce, miso, alcohols, sugars (e.g., glucose, sucrose, fructose, glucose-fructose syrup, fructose-glucose syrup, etc.), sugar alcohols (e.g., xylitol, erythritol, maltitol, etc.), artificial sweeteners (e.g., sucralose, aspartame, saccharin, acesulfame K, etc.), minerals (e.g., calcium, potassium, sodium, iron, zinc, magnesium, etc., and salts thereof, etc.), flavoring agents, pH adjusters (e.g., sodium hydroxide, potassium hydroxide, lactic acid, citric acid, tartaric acid, malic acid, acetic acid, etc.), cyclodextrins, antioxidants (e.g., Vitamin E, vitamin C, tea extract, green coffee bean extract, chlorogenic acid, spice extract, caffeic acid, rosemary extract, vitamin C palmitate, rutin, quercetin, bayberry extract, sesame extract, etc.), emulsifiers (as examples, glycerol fatty acid esters, acetic acid monoglyceride, lactic acid monoglyceride, citric acid monoglyceride, diacetyl tartaric acid monoglyceride, succinic acid monoglyceride, polyglycerol fatty acid ester, polyglycerol condensed ricinoleate, soap bark tree extract, soybean saponin, tea seed saponin, sucrose fatty acid ester, lecithin, etc.), colorants, thickening stabilizers, etc.

[0228] However, due to the recent increase in natural awareness, the composition of the present invention preferably does not contain any one selected from so-called emulsifiers, colorants, and thickeners and stabilizers (for example, substances listed as "colorants", "thickeners and stabilizers", and "emulsifiers" in the "Table of Names of Food Additive Substances Used for Indication" of the Food Additive Labeling Handbook (Heisei 2014 edition)), more preferably does not contain any two of them, and further preferably does not contain all three of them.

[0229] Non-expanded materials:

[0230] The composition of the present invention can be an expanded food or a non-expanded food, preferably not an expanded food (especially an expanded food with a density ratio lower than 1.0 due to expansion), but a non-expanded food. As described below, the extruder (extruder) used in the preferred method for preparing the composition of the present invention is used to make an expanded product represented by puffs, and their manufacturing conditions are usually set to the cooling conditions of stage (iii) exceeding the conditions of the puffing temperature of the composition, so it cannot be applied to the manufacturing method of the composition without expansion as in the present invention. This is because, since the internal temperature of the extruder changes continuously, if, for example, only the heating conditions during mixing are adopted, the outlet temperature setting is adjusted to a suitable low temperature, then due to the influence of reducing the outlet temperature setting, the temperature during mixing is represented, and the internal temperature is reduced as a whole, becoming a completely different condition, which is not an adjustment that can be properly made by a person skilled in the art. In addition, when making an expanded product represented by puffs, in order to make it expand rapidly during decompression, it is a technical common sense for a person skilled in the art to reduce the proportion of water in its total mass flow rate, and there is no motivation to increase the content of water in the total mass flow rate as in the composition without expansion as in the present invention. In producing the composition of the present invention, after kneading at high temperature and high pressure, the temperature is usually lowered while pressure is applied to prevent expansion, and then the pressure is reduced to about atmospheric pressure to obtain the composition of the present invention.

[0231] [II. Method for producing solid composition containing starch]

[0232] Another aspect of the present invention relates to a method for producing the composition of the present invention (hereinafter, sometimes also referred to as “the production method of the present invention”).

[0233] (1) Summary:

[0234] There is no restriction on the method for modulating the composition of the present invention, and any method can be used as long as a composition satisfying the above-mentioned various requirements can be obtained. Specifically, as long as the raw materials of the composition of the present invention, such as beans, are mixed with other raw materials, flavoring agents and other ingredients used arbitrarily. Treatments such as heating or molding can be applied as needed. Among them, by using a specific method (hereinafter appropriately referred to as "the manufacturing method of the present invention"), the composition of the present invention can be effectively manufactured, and the method is a method of mixing the green composition of the above-mentioned materials in a manner satisfying the above-mentioned composition under a specified high temperature and pressurized condition, and then cooling it in a non-expanded manner.

[0235] Specifically, the production method of the present invention is characterized by comprising the following steps (i) and (ii), and more preferably comprising the following steps (iii) and / or (iv).

[0236] (i) A stage of preparing a composition having a starch content of 10.0% by mass or more on a wet basis and a moisture content of more than 40% by mass on a dry basis.

[0237] (ii) The composition is kneaded at a temperature of 100° C. to 190° C. at a SME value of 400 kJ / kg or more until all of the following conditions (1) to (4) are satisfied.

[0238] (1) The composition satisfies the following (a) and / or (b).

[0239] (a) The above-mentioned starch granule structure of the composition is 300 granules / mm 2 the following.

[0240] (b) The gelatinization peak temperature measured by heating a 14 mass % aqueous slurry of the pulverized composition from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer was lower than 120°C.

[0241] (2) The degree of gelatinization of the composition is 50% or more.

[0242] (3) The above-mentioned [value α] of the composition is 60% or less.

[0243] (4) The above-mentioned [value β] of the composition is 35% or more.

[0244] (iii) A step of cooling the kneaded composition in step (ii) to below 100°C.

[0245] (iv) A stage in which the dry basis moisture content of the composition is reduced to less than 25% by mass. Preferably, after the above stage (ii), the time required from the temperature of the composition being reduced to less than 80°C until the dry basis moisture content of the composition is reduced to less than 25% by mass is adjusted to 5 minutes or more.

[0246] Hereinafter, such a production method of the present invention will be described in detail.

[0247] (2) Stage (i): Preparation of green body composition

[0248] In this stage (i), the composition (appropriately referred to as "green composition") that is the basis of the composition of the present invention is prepared by mixing the raw materials of the composition of the present invention, such as beans, and any other ingredients used. It should be noted that the properties of the green composition (sometimes referred to as "green" or "paste green composition") can be liquid, sol, gel, or solid as long as the food is partially or completely integrated with water. In addition, for example, it can be a plastic property like bread green, or it can be a non-plastic property like fish floss. There is no particular limitation on the method of preparing such a green composition. The raw materials of the composition of the present invention, such as one or more edible plants (preferably at least one or more beans and any other one or more edible plants) and any one or more other raw materials can be mixed and used as a green composition.

[0249] In addition, as described below, in the case of kneading using an extruder, the preparation of the green composition can be a method of preparing the composition of stage (i) by adding water to the raw materials before feeding into the extruder (that is, a method of pre-preparing the green composition of stage (i) and then feeding it into the feeder), or a method of preparing the composition of stage (i) by adding water to the raw materials in the extruder (that is, feeding the raw materials (beans, etc.) in a state with a dry basis moisture content of less than 25 mass% (for example, a powder state) into the feeder, and adding water while conveying in the first screw flight portion, thereby preparing the green composition of stage (i)), or a method of combining them. In addition, as described below, in a method in which kneading is performed using an extruder, and water is added to the raw materials in the extruder to prepare the composition in step (i), the raw materials in the extruder are not exposed to a high temperature of 90° C. or more (or 95° C., or 100° C.) in a state where the dry basis moisture content is less than 25% by mass (or less than 30% by mass, or less than 35% by mass, or less than 40% by mass), so the starch is less likely to be thermally decomposed, which is preferred.

[0250] ·Ingredients of green body composition:

[0251] Here, the green composition is preferably prepared so as to satisfy the various component compositions described below.

[0252] The starch content of the green composition is based on the wet mass standard, usually set to 10.0% by mass or more, wherein, preferably set to 15% by mass or more, further preferably set to 20% by mass or more, especially preferably set to 25% by mass or more, or 30% by mass or more, or 35% by mass or more, or 40% by mass or more, or 45% by mass or more, and particularly preferably set to 50% by mass or more. Here, in the present invention, "wet mass" means the mass of the whole composition including the water content, and "wet mass reference ratio" means the ratio of each component calculated with the wet mass of the composition as the denominator and the content of each component as the numerator. The upper limit is not particularly limited, for example, it can usually be set to 80% by mass or less, or 75% by mass or less, or 70% by mass or less.

[0253] The dry basis moisture content of the green composition is usually set to more than 40% by mass, preferably more than 45% by mass, more preferably more than 50% by mass, particularly preferably more than 55% by mass, or more than 60% by mass, or more than 65% by mass, or more than 70% by mass, or more than 75% by mass, and particularly preferably more than 80% by mass. The upper limit is not particularly limited, for example, it can usually be set to 200% by mass or less, or 175% by mass or less, or 150% by mass or less.

[0254] The moistening mass reference ratio of the insoluble dietary fiber of the green composition is usually set to more than 1.5 mass %, wherein, preferably set to more than 2.0 mass %, further preferably set to more than 3 mass %, especially preferably set to more than 4 mass %, or more than 5 mass %, or more than 6 mass %, or more than 7 mass %, or more than 8 mass %, or more than 9 mass %, especially preferably set to more than 10 mass %. The upper limit is not particularly limited, for example, can usually be set to less than 40 mass % or less than 30 mass %.

[0255] The wet mass reference ratio of protein in the green composition is usually set to 3.0% by mass or more, preferably 4.0% by mass or more, more preferably 5.0% by mass or more, and particularly preferably 6.0% by mass or more, or 7.0% by mass or more, or 8.0% by mass or more, or 9.0% by mass or more, or 10% by mass or more, or 11% by mass or more, or 12% by mass or more, or 13% by mass or more, or 14% by mass or more, or 15% by mass or more, or 16% by mass or more, or 17% by mass or more, or 18% by mass or more. The upper limit is not particularly limited, and for example, it can be usually set to 40% by mass or less, or 30% by mass or less.

[0256] Here, the content of insoluble dietary fiber, starch and protein in the raw material composition is a wet mass reference ratio calculated with the mass of the entire raw material composition in a water-containing state as the denominator and the content of each component as the numerator, and can be adjusted in such a way that each component derived from edible plants (such as beans) as raw materials is above a specified value.

[0257] In addition, when edible plants (such as beans) are used as raw materials for the green composition, the wet mass basis ratio of such edible plants (such as beans) is set to 30 mass% or more, preferably 40 mass% or more, more preferably 50 mass% or more, and particularly preferably 60 mass% or more, or 70 mass% or more, or 80 mass% or more, or 90 mass% or more, or 100 mass%. The upper limit is not particularly limited, and can usually be set to 100 mass% or less.

[0258] In addition, the source of the total starch content and / or total protein content in the composition of the present invention is not particularly limited, and may be derived from various food raw materials of the composition, or may be derived from a separated pure product. In particular, when edible plants (e.g., beans) are used as raw materials for the green composition, the ratio of the starch content and / or protein content derived from edible plants (e.g., beans, especially the following heat-treated beans) relative to the total starch content and / or total protein content of the green composition is preferably a specified value or more. Specifically, the ratio of the starch content derived from edible plants (e.g., beans, especially the following heat-treated beans) relative to the total starch content of the green composition is set to 30% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, particularly preferably 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more, or 100% by mass. The upper limit is not particularly limited, and can usually be set to 100% by mass or less. In addition, the ratio of the protein content derived from edible plants (e.g., beans, particularly the heat-treated beans described below) to the total protein content of the green composition is usually 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, and particularly preferably 100% by mass. As the protein derived from beans, pea-derived protein is particularly preferred, and yellow pea-derived protein is most preferred.

[0259] ·Degree of gelatinization of starch:

[0260] The starch as the raw material of the green composition is preferably used in advance, because the gelatinization process (stage (ii) below) becomes easy. Specifically, the degree of starch gelatinization in the composition in the stage (stage (i)) before the gelatinization process is preferably more than a certain degree. Specifically, it is 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, or 30% by mass or more, or 40% by mass or more, or 50% by mass or more, or 60% by mass or more, or 70% by mass or more, or 80% by mass or more, or 90% by mass or more. The upper limit is not particularly limited, and is usually 100% by mass or less.

[0261] In addition, for the same reason, the starch in the composition in the stage before the gelatinization process (stage (i)) is preferably starch preheated at a temperature above a certain degree. Specifically, it is above 80°C, preferably above 90°C, more preferably above 100°C, or above 110°C, or above 120°C. There is no particular upper limit, but it is usually below 200°C, and further below 180°C. In addition, starch that has been heated at a high temperature in a state where the dry basis moisture content is lower than a certain degree during the heating has the characteristic of low processability due to thermal decomposition, so it is further preferably starch that has been heated at a dry basis moisture content above a certain degree. Specifically, preferably, the heat-treated starch is heat-treated at a dry basis moisture content of more than 25% by mass, more than 30% by mass, more than 35% by mass, more than 40% by mass, more than 45% by mass, more than 50% by mass, more than 55% by mass, more than 60% by mass, more than 65% by mass, more than 70% by mass, more than 75% by mass, more than 80% by mass, more than a predetermined temperature (specifically, for example, more than 80°C, more than 90°C, more than 100°C, more than 110°C, or more than 120°C. The upper limit is not particularly limited, for example, less than 200°C, more than 180°C.). The upper limit of the dry basis moisture content during heat treatment is not particularly limited, and can usually be set to less than 200% by mass, or less than 175% by mass, or less than 150% by mass.

[0262] Amylolytic enzyme activity of raw materials:

[0263] In addition, as the composition of the present invention, in order to obtain the above-mentioned composition having an amylolytic enzyme activity below a specified value, as the raw material of the green composition in this stage (i), it is preferred to use a starch or an edible plant (e.g., legume) containing the starch processed in a manner lower than the specified value in terms of amylolytic enzyme activity. Specifically, the amylolytic enzyme activity of the green composition containing starch or an edible plant (e.g., legume) containing the starch can be converted to 100 U / g or less in terms of dry mass. Among them, 90.0 U / g or less, or 80.0 U / g or less, or 70.0 U / g or less, or 60.0 U / g or less, or 50.0 U / g or less, or 40.0 U / g or less, or 30.0 U / g or less can be used. On the other hand, the lower limit of such a ratio is not particularly limited, and is usually 0.0U / g or more, or 5.0U / g or more, or 10.0U / g or more, or 20.0U / g or more, or 30.0U / g or more, or 35.0U / g or more. Since the heat resistance of the amylolytic enzyme in edible plants (such as beans) is very strong, as a processing method for obtaining edible plants with low amylolytic enzyme activity, it is preferably heated at a prescribed temperature or more in an environment where the dry basis moisture content is 50% by mass or more. Specifically, it is preferably above 100°C. Among them, it is desired to be above 110°C, and it is particularly desired to be above 120°C. On the other hand, the upper limit of such a temperature is not particularly limited, and is usually lower than 200°C. Regarding the heating time, it can be arbitrarily set until the amylolytic enzyme activity is adjusted to a prescribed value, usually 0.1 minutes or more.

[0264] In addition, in the present invention, since the above-mentioned amylolytic enzyme activity (U / g) decreases by 20% or more before and after stage (ii) (that is, the reduction ratio specified by "{(amylolytic enzyme activity (U / g) in the composition before stage (ii))-(amylolytic enzyme activity (U / g) after stage (ii))} / (amylolytic enzyme activity (U / g) in the composition before stage (ii))" is a numerical value above a certain degree), the effect of the present invention can be well exerted, and thus it is preferred. Among them, it is preferably set to 25% or more, more preferably to 30% or more, especially preferably to 35% or more, or 40% or more, or 45% or more, or 50% or more, or 55% or more, or 60% or more, and particularly preferably to 65% or more. The term "the ratio is above a certain degree" also includes the case where the amylolytic enzyme activity (U / g) in the composition before stage (ii) is 0.0U / g and the ratio diverges infinitely. When the amylolytic enzyme activity (U / g) in the composition before stage (ii) is a value exceeding 0.0, the upper limit of the ratio is not particularly limited, and can usually be, for example, 100% or less, or 95% or less.

[0265] PDI of raw materials:

[0266] In addition, as the composition of the present invention, in order to obtain a composition having a PDI value lower than a specified value, as the raw material of the green composition in this stage (i), it is preferred to use a protein processed in a manner where the PDI value is lower than the specified value or an edible plant (e.g., beans) containing the protein. Specifically, the PDI value of the protein or edible plant (e.g., beans) containing the protein used as the raw material of the green composition is preferably less than 90% by mass. Among them, it is desirable to be less than 85% by mass, further desirable to be less than 80% by mass, particularly desirable to be less than 75% by mass, or less than 70% by mass, or less than 65% by mass, or less than 60% by mass, or less than 55% by mass, or less than 50% by mass, or less than 45% by mass, or less than 40% by mass, or less than 35% by mass, or less than 30% by mass, or less than 25% by mass, or less than 20% by mass, or less than 15% by mass, particularly desirable to be less than 10% by mass. On the other hand, the lower limit of such a ratio is not particularly limited, and is usually 0% by mass or more, further 2% by mass or more, and 4% by mass or more. In addition, since the ratio of the protein content blended in a state contained in an edible plant (such as beans) relative to the total protein content in the above-mentioned composition is above a specified value, and the PDI value is below a specified value, the taste improvement effect of the composition can be more significantly exerted, and thus it is more preferred. As a processing method for obtaining a protein with a low PDI value, a protein in a state contained in an edible plant (such as beans), it is preferred to heat treat at a specified temperature or above in an environment where the dry basis moisture content is 30% by mass or more. Specifically, it is preferably above 80°C. Among them, it is desired to be above 90°C, further desired to be above 100°C, and particularly desired to be above 110°C. On the other hand, the upper limit of such a temperature is not particularly limited, and is usually below 200°C. Regarding the heating time, it can be arbitrarily set until the PDI value is adjusted to a specified value, usually for more than 0.1 minutes.

[0267] · Particle size of insoluble dietary fiber of raw materials:

[0268] In addition, when using edible plants (such as beans) as the raw material of green body composition, since the shape of insoluble dietary fiber does not change greatly in the mixing process, it is preferred that the insoluble dietary fiber derived from such edible plants (such as beans) has a specified size. Here, the possibility that the insoluble dietary fiber size in the bean powder that is usually broken blindly exceeds 450 μm is high (this is because the shape of the insoluble dietary fiber contained in the beans is usually rod-shaped, and a large value can be obtained in the laser diffraction particle size distribution measurement of the present invention). Therefore, the insoluble dietary fiber contained in the food materials used in the present invention (especially the food materials containing hard tissues such as beans with seed coat) is preferably subjected to specific crushing treatment in advance, and the insoluble dietary fiber with a size of a specific range is used. Specifically, for the insoluble dietary fiber contained in the composition, in the same manner as above, the following method is adopted: the aqueous suspension of edible plants (such as beans) is subjected to protease and amylase treatment, and for the composition obtained by using enzymes to decompose starch and protein and starch-protein decomposition treatment, the particle size distribution after applying ultrasonic treatment is determined. Specifically, a 6% aqueous suspension of edible plant powder was treated with 0.4% by volume of protease and 0.02% by mass of α-amylase at 20° C. for 3 days (the above [step b]) to decompose starch-protein, and then the obtained treated product was subjected to ultrasonic treatment and the particle size distribution was measured as the particle size (d 90 and / or 50 By such treatment, starch and protein are decomposed in the components of edible plants, and it is believed that the particle size distribution of the obtained decomposition product reflects the particle size distribution of the structure mainly composed of insoluble dietary fiber.

[0269] Specifically, the particle size d of the insoluble dietary fiber in the edible plant (such as beans) obtained according to the above steps is 90 Preferably, the particle size d of the insoluble dietary fiber in the edible plant (e.g., beans) obtained according to the above steps is 450 μm or less, more preferably 400 μm or less, more preferably 350 μm or less, more preferably 300 μm or less, more preferably 250 μm or less, more preferably 200 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, and more preferably 50 μm or less. 50It is preferably 450 μm or less, more preferably 400 μm or less, more preferably 350 μm or less, more preferably 300 μm or less, more preferably 250 μm or less, more preferably 200 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, and more preferably 50 μm or less. If the particle size d of the insoluble dietary fiber contained in the edible plant is 90 and / or particle size d 50 If the particle size exceeds the above range, it is sometimes difficult to exert the effect of the present invention. The reason is not clear, but it is believed that the coarse insoluble dietary fiber hinders the formation of the matrix structure of starch, etc., making it difficult to exert the effect of the present invention. On the other hand, the particle size d of the insoluble dietary fiber contained in the edible plant is 90 and / or particle size d 50 The lower limit of is not particularly limited, but is usually preferably 1 μm or more, more preferably 3 μm or more.

[0270] ·The dyed part of the raw material CFW:

[0271] In addition, when using edible plants (such as beans) as the raw material of the green composition, since the shape of the dietary fiber does not change greatly during the mixing process, it is preferred that the insoluble dietary fiber contained in such edible plants (such as beans) has a specified shape. Specifically, for the insoluble dietary fiber contained in the composition, in the same manner as above, the aqueous suspension of edible plants (such as beans) is treated with protease and amylase, and the starch-protein decomposition processed product obtained by enzymolysis of starch and protein (specifically, the processed product that starch-protein decomposition processing is implemented by the above-mentioned [step b]) is CFW (Calcofluor White) dyed, and when observing under a fluorescent microscope, it is preferred that the longest diameter average value and / or the aspect ratio average value of the CFW dyed position are respectively below the specified value. The CFW dyed position obtained in this way is considered to have the structure of the insoluble dietary fiber body. Specifically, the arithmetic mean of the longest diameter of the CFW stained part of the edible plant (such as beans) measured according to the above steps is usually 450 μm or less, preferably 400 μm or less, or 350 μm or less, or 300 μm or less, or 250 μm or less, or 200 μm or less, or 150 μm or less, or 100 μm or less, or 80 μm or less, more preferably 60 μm or less, and particularly preferably 50 μm or less. If the average value of the longest diameter of such a CFW stained part exceeds the above range, it is sometimes difficult to exert the effect of the present invention. The reason is not clear, but it is believed that it is because the insoluble dietary fiber with a large longest diameter hinders the formation of the matrix structure of starch, etc., making it difficult to exert the effect of the present invention. On the other hand, the lower limit of the arithmetic mean of the longest diameter of such a CFW stained part is not particularly limited, and is generally preferably 2 μm or more, and more preferably 3 μm or more. It should be noted that the average value (sometimes also referred to as the average or arithmetic mean) in the present invention refers to the arithmetic mean unless otherwise specified.

[0272] In addition, since the shape of dietary fiber does not produce a large change in the mixing process of the subsequent stage (ii), as an edible plant (such as beans) containing insoluble dietary fiber, it is preferred to use a powdered edible plant processed in a manner that the insoluble dietary fiber contained therein is an aspect ratio of less than a certain degree. Here, the aspect ratio of the above-mentioned CFW of the insoluble dietary fiber in the edible plant (such as beans) powder that is usually broken blindly is a high possibility of a numerical value exceeding 5.0 (especially because the shape of the insoluble dietary fiber contained in the beans is usually rod-shaped). In addition, if edible plant (such as beans) powder is subjected to wind sorting, etc., the edible plant powder of a specific shape can be removed, and the aspect ratio of the CFW of the insoluble dietary fiber is too high or too low. Therefore, as an edible plant (such as beans) powder, it is preferred to use a powder that performs a specific crushing process in advance, and the arithmetic mean of the aspect ratio of the CFW of the insoluble dietary fiber is a specific range. Specifically, the arithmetic mean of the aspect ratio of the CFW dyed part in the edible plant (e.g., bean) powder measured according to the above steps is usually 5.0 or less, preferably 4.5 or less, or 4.0 or less, or 3.5 or less, or 3.0 or less, or 2.5 or less, and particularly preferably 2.0 or less. If the average value of the aspect ratio of such CFW dyed parts exceeds the above range, it is sometimes difficult to exert the effect of the present invention. The reason is not clear, but it is believed that it is because insoluble dietary fiber with a large aspect ratio hinders the formation of matrix structures such as starch, making it difficult to exert the effect of the present invention. On the other hand, the lower limit of the arithmetic mean of the aspect ratio of such CFW dyed parts is not particularly limited, and is generally preferably above 1.1, and more preferably above 1.3.

[0273] It should be noted that the determination methods of various parameters related to insoluble dietary fiber in edible plants (such as beans) as raw materials of the green composition, namely, amylase and protease treatment, ultrasonic treatment, particle size distribution (particle size d 90 and d 50 ) determination, CFW staining, fluorescence microscopy observation, etc., are carried out according to the determination method of various parameters related to the insoluble dietary fiber in the above-mentioned composition.

[0274] · Micronization / Powderization of Raw Materials:

[0275] In the present invention, when edible plants (such as beans) are used as raw materials for green body compositions, such edible plants are preferably micronized / powdered edible plants. The method or conditions for micronization / powderization are not particularly limited. Specifically, the temperature during micronization / powderization is not particularly limited, but if the powder is exposed to high temperature, the elasticity of the composition of the present invention is easily reduced, so it is preferably dried at a temperature below 200°C, for example. However, in the case of using beans as edible plants, if the method is to crush the beans after heating, the heat load can be reduced, so the temperature is not particularly limited. In addition, the pressure during micronization / powderization is also not limited, and it can be any of high-pressure crushing, normal pressure crushing, and low-pressure crushing. As examples of devices for such micronization, equipment such as mixers, mixers, mills, kneaders, pulverizers, crushers, and grinders can be listed, but are not limited to these. Specifically, for example, a dry sand mill, a media stirring mill such as a ball mill (rotational type, vibration type, etc.), a fluid energy mill, a high-speed rotary impact mill (pin mill, etc.), a roll mill, a hammer mill, etc. can be used.

[0276] Heating and water treatment of raw materials:

[0277] In the present invention, when edible plants containing starch and / or protein (e.g., beans) are used as raw materials for the green composition, such edible plants may be pre-heated in the presence of water as a pre-treatment. In particular, it is preferred that edible plants are heated in an environment where the dry basis moisture content is above a certain value (moist heating) because the structure in the final paste composition for cooking by heating is sometimes easily formed.

[0278] Specifically, the dry basis moisture content of the edible plant during heating is not limited, and is usually set to 25% by mass or more, preferably 30% by mass or more, or 40% by mass or more, and particularly preferably 50% by mass or more. The upper limit of the dry basis moisture content is not particularly limited, for example, it can usually be set to 200% by mass or less, and can be set to 175% by mass or less. The heating temperature of the edible plant is not limited, and is usually set to 80°C or more, preferably 90°C or more, and more preferably 100°C or more. In addition, it is usually set to 200°C or less, and preferably 190°C or less.

[0279] It should be noted that in the present invention, it is more preferred to pre-heat the edible plants containing starch and the edible plants containing protein with water before use, and it is further preferred to pre-heat the edible plants containing both starch and protein before use. It should be noted that the heating of the edible plants with water can be, for example, heated by steam heating).

[0280] On the other hand, especially in the case of powdered (e.g.90 and / or 50 When starch-containing edible plants (e.g., beans) with a surface area of ​​less than 1000 μm) are heated for use, if the edible plants are heated in a dry environment with a dry basis moisture content of less than 25% by mass (e.g., 90° C. or above), the starch is locally heated and overheated, which promotes the thermal decomposition of the amylopectin in its structure, and the composition becomes sticky, which is sometimes not preferred.

[0281] Iodine staining of green body composition

[0282] The green composition prepared in this step (i) preferably has an ABS value measured by the same method as the composition of the present invention described above. 5.0-6.5 Specifically, for the green composition, the ABS obtained according to the above steps is 5.0-6.5 The value of is usually below 0.80, wherein it is desired to be below 0.75, further desired to be below 0.70, particularly desired to be below 0.65, or below 0.60, or below 0.55, or below 0.50, or below 0.45, or below 0.40, or below 0.35, particularly desired to be below 0.30. On the other hand, the lower limit of such a value is not particularly limited, and is usually above 0.00, further above 0.10, wherein it is above 0.20. Its principle is not yet clear, but it is speculated that it is because the composition with high dyeability of the separated fraction is likely to contain a large amount of starch degradation products derived from starch fractions with larger molecular weight (it is believed that the branched starch contained in the fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 is formed by thermal decomposition of molecular weight logarithm of 5.0 or more and less than 6.5 due to overheating), and such starch degradation products sometimes have the characteristic that elasticity is easily reduced when water is added.

[0283] The green composition prepared in this step (i) preferably has an ABS value measured by the same method as that of the composition of the present invention. 6.5-8.0 / ABS 5.0-6.5 Specifically, for the green composition, the ABS obtained according to the above steps is 6.5-8.0 / ABS 5.0-6.5The value of is usually 0.003 or more, wherein it is desired to be 0.005 or more, further desired to be 0.007 or more, particularly desired to be 0.009 or more, or 0.010 or more, or 0.020 or more, or 0.030 or more, or 0.040 or more, or 0.050 or more, or 0.060 or more, particularly desired to be 0.070 or more. On the other hand, the upper limit of such a value is not particularly limited, and is usually 1.000 or less, and further 0.9000 or less. Its principle is not yet clear, but it is possible that the proportion of the starch decomposed by heat is less than the starch before decomposition, thus becoming a good quality. In particular, the starch in the raw material that is powdered in a state with less dry basis moisture content and kneaded at high temperature significantly promotes thermal decomposition compared with the starch in the raw material that is not powdered and directly exposed to high temperature, and the ratio is a value lower than 0.003. The possibility is high (Test Example 43). Specifically, for the green composition in an overheated state that was heated to 80°C and kneaded in a powder state as in Test Example 21, in the "Temperature conditions of each barrel part" (2), in the extruder, at the end of the kneading process at 80°C, the ratio of the green composition was measured and the result was 0.001.

[0284] It should be noted that in the manufacturing method of the present invention, it is preferred that not only the green composition of the present stage (i) and the finally manufactured composition of the present invention, but also the composition being manufactured during the entire manufacturing process be treated with the ABS obtained according to the above steps. 5.0-6.5 Value and ABS 6.5-8.0 / ABS 5.0-6.5 The thermal history of starch is managed in a manner that satisfies the above-mentioned values ​​(i.e., while providing the heat required to increase the intermediate molecular weight fraction in the composition of the present invention, overheating to the extent of starch decomposition must be avoided), and the manufacturing process is carried out simultaneously.

[0285] ·Particle size of green composition

[0286] The particle size of the green composition as a whole is preferably the same size as the above-mentioned edible plant (e.g., bean) powder preferably used as a raw material. Specifically, when measuring the particle size of the green composition as a whole, a composition sample block of about 1 cm square is immersed in 50 ml of a particle size distribution measurement solvent (e.g., ethanol) at 80°C, and allowed to stand for about 5 minutes. Then, it is crushed with a spatula while being stirred thoroughly to suspend it in the liquid. The solution (sometimes referred to as a suspension) that passes through an 8-mesh sieve with a mesh size of 2.36 mm and a wire diameter (WireDia.) of 1.0 mm is used for measurement, and the particle size after ultrasonic treatment is measured using a laser diffraction particle size distribution measuring device. The particle size d after ultrasonic treatment 90The particle size after ultrasonic treatment is usually 500 μm or less, and more preferably 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. 50 It is usually 500 μm or less, and more preferably 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. 90 and d 50 The lower limit of is not particularly limited, but is usually 0.3 μm or more, or 1 μm or more.

[0287] It should be noted that the "mesh" in the present invention is a unit representing the density of holes in a metal mesh / sieve / filter, etc., and represents the number of mesh holes per 1 inch. That is, for example, "passing 8 meshes" refers to the fraction passing through a sieve with a mesh size of 2.36 mm. Specifically, the thickness of the metal wire on the sieve and the spacing of the holes can be the values ​​specified in USA Standard Testing Sieves ASTM Specifications E 11-04 (for example, 8 meshes corresponds to the Nominal Dimensions in the same document, "No. 8" specified in "Alternative" in Permissible Variation for Wire Cloth of Standard Testing Sieves (USA) Standard Series) or a value based on it, unless otherwise specified.

[0288] (3) Stage (ii): Mixing under high temperature conditions

[0289] The green composition obtained in the above-mentioned stage (i) is kneaded at a certain intensity or above under prescribed high temperature conditions. By performing strong kneading under high temperature conditions in this way, the molecular weight distribution of the above-mentioned preferred starch is formed, and it is believed that the effect of the present invention can be exerted. In particular, by performing kneading under certain high temperature and pressure conditions, the effect of preventing such insoluble components from flowing out can be improved, and thus it is more preferred. The reason is not yet clear, but by treating under certain high temperature conditions, preferably under high temperature and pressure conditions, the protein, starch and insoluble dietary fiber in the green form a composite structure on the surface of the composition, and it is particularly possible to inhibit the outflow of insoluble components. On the other hand, since conventional cold noodles using purified starch as raw materials contain only a very small amount of dietary fiber, in particular, a structure such as the composition of the present invention is not properly developed, and it is believed that the effect of the present invention cannot be exerted.

[0290] For the specific conditions during mixing, the SME (specific mechanical energy) value sought to be obtained by the following formula I is made to be more than the specified value, thus fully destroying starch granules, sometimes showing the property as a matrix, thus preferably. Specifically, preferably, mixing is carried out under the condition that the SME value is usually more than 400kJ / kg, wherein preferably more than 450kJ / kg, further more than 500kJ / kg, or more than 550kJ / kg, or more than 600kJ / kg, or more than 700kJ / kg, particularly more than 800kJ / kg. In addition, when using an extruder, it is preferred that the number of revolutions of the screw is usually made to exceed 150rpm, wherein preferably more than 200rpm, further preferably more than 250rpm.

[0291] [Mathematical formula 3]

[0292]

[0293] N: Screw speed during mixing (rpm)

[0294] N max :Maximum screw speed (rpm)

[0295] τ: Torque during mixing / maximum torque (%)

[0296] τ empty :Idling torque / maximum torque (%)

[0297] Q: Total mass flow rate (kg / hour)

[0298] P max :Maximum power of mixer (such as extruder) (kW)

[0299] In addition, by performing the above-mentioned kneading at a high temperature, for example, usually above 100°C, especially above 110°C, and further above 120°C, the starch granule structure is easily destroyed, so it is more preferred. In addition, for example, when an extruder is used in kneading, it is preferred that the above-mentioned high temperature and high SME value treatment is carried out in a region of usually 3% or more, especially 5% or more, or 8% or more, or 10% or more, or 15% or more, and especially 20% or more of the total length of the barrel. In particular, the starch granule structure derived from beans is more solid in structure, so the above-mentioned high temperature and high SME value treatment is more useful. On the other hand, the upper limit of the treatment temperature is usually below 200°C. Among them, it is preferably below 190°C, more preferably below 180°C, or below 170°C, and particularly preferably below 160°C. If the temperature at this stage exceeds the above-mentioned upper limit, for example, when an extruder is used in kneading, the temperature when the composition is extruded from the die head of the extruder is not sufficiently reduced.

[0300] In addition, in the case of carrying out the above-mentioned mixing under the pressurized conditions relative to atmospheric pressure, it is more preferred to mix under the conditions of applying a higher pressure than usual. In the case of using an extruder, the pressure during mixing can be measured by measuring its outlet pressure. In the case of mixing under the pressurized conditions relative to atmospheric pressure, the lower limit of the pressure that should be further applied on the basis of atmospheric pressure is usually set to more than 0.01MPa, wherein, it is preferably set to more than 0.03MPa, more preferably set to more than 0.05MPa, or more than 0.1MPa, or more than 0.2MPa, particularly preferably set to more than 0.3MPa, more than 0.5MPa, more preferably set to more than 1.0MPa, more preferably set to more than 2.0MPa, and more preferably set to more than 3.0MPa. On the other hand, the upper limit of the pressure that should be further applied on the basis of atmospheric pressure is not particularly limited, for example, it can be set to less than 50MPa or less than 40MPa. In addition, by arranging a flow delay structure near the end point of the front end side of the mixing section (preferably after the end point of the front end side of the mixing section), the pressure of the mixing section can be increased, so it is preferred.

[0301] The kneading time can be appropriately determined according to the kneading temperature and pressure, the size of the kneading container, etc. In particular, since the amount of heat applied to the composition varies greatly depending on the characteristics of the device used, it is preferred to perform processing in a manner that adjusts the physical properties of the composition before and after the treatment to a predetermined range.

[0302] The mixing time is not limited, and is generally as follows. That is, the lower limit of the mixing time is, for example, usually set to more than 0.1 minutes, wherein, preferably set to more than 0.2 minutes, further preferably set to more than 0.3 minutes, or more than 0.4 minutes, or more than 0.5 minutes, or more than 0.8 minutes, or more than 1 minute, and particularly preferably set to more than 2 minutes. The upper limit of the mixing time is not limited, and for example, can usually be set to within 60 minutes, wherein, can be set to within 30 minutes, and further can be set to within 15 minutes.

[0303] By kneading the green composition under such harsh conditions of high temperature and high pressure, a composite structure of protein, starch, insoluble dietary fiber, etc. is formed, and the mouthfeel of the composition is improved, thereby inhibiting the outflow of insoluble or soluble components of the composition. This is an amazing insight that was completely unknown before.

[0304] The kneading treatment in stage (ii) is preferably carried out until the number of starch granule structures in the composition is less than a specified value. The principle is not clear, but it is believed that the composition is processed under the following high temperature, high pressure and strong kneading conditions in a state where the starch granule structure is destroyed, so that the starch is diffused into the entire composition in a matrix state, and the branched starch in the starch forms a structure that is easy to show elasticity when retaining water. Specifically, it is preferred to carry out the kneading treatment until the composition satisfies the following (a) and / or (b), and it is further preferred to carry out the kneading treatment until both (a) and (b) are satisfied.

[0305] (a) When a 6% suspension of the pulverized product of the composition is observed, the starch granule structure visible is 300 granules / mm 2 the following.

[0306] (b) The gelatinization peak temperature measured by heating a 14 mass % aqueous slurry of the pulverized composition from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer was lower than 120°C.

[0307] Regarding the above (a), the number of starch granule structures in the composition observed under the above conditions is usually 300 / mm due to the kneading treatment in the stage (ii). 2 Below, preferably 250 pieces / mm 2 Below, more preferably 200 pieces / mm 2 Below, especially preferably 150 pieces / mm 2 Below, or 100 pieces / mm 2 Below, or 50 pieces / mm 2 Below, or 30 pieces / mm 2 Below, or 10 / mm 2 Below, particularly preferably 0 pieces / mm 2It should be noted that the details of the starch granule structure are related to the composition of the present invention, as described above.

[0308] Regarding (b), the gelatinization peak temperature of the composition measured under the above conditions by the kneading treatment in step (ii) is usually lower than 120° C., preferably lower than 115° C. The details of the gelatinization peak temperature are as described above in relation to the composition of the present invention.

[0309] From the viewpoint of suppressing the shape destruction during heating cooking, the starch gelatinization degree in the composition after mixing of the preferred stage (ii) is more than the specified value. Specifically, the starch gelatinization degree in the composition after mixing of the stage (ii) is usually more than 50% by mass, wherein, preferably more than 55% by mass, more preferably more than 60% by mass, especially preferably more than 65% by mass, or more than 70% by mass, or more than 75% by mass, and particularly preferably more than 80% by mass. The upper limit of the gelatinization degree is not particularly limited. If it is too high, the starch decomposes and the composition sometimes becomes a sticky bad quality. Therefore, the upper limit of the gelatinization degree is preferably less than 100% by mass, less than 99% by mass, wherein, preferably less than 95% by mass, more preferably less than 90% by mass.

[0310] The kneading treatment in stage (ii) is preferably carried out until the ratio of the area under the curve in the range where the molecular weight logarithm is 5.0 or more and less than 6.5 [value α] is usually 60% or less, and more preferably 55% or less, or 50% or less, or 45% or less, or 40% or less, or 35% or less. It should be noted that the details of this [value α] are related to the composition of the present invention, as described above.

[0311] The composition of the present invention is preferably implemented until the ratio of the area under the curve where the molecular weight logarithm is 6.5 or more and less than 8.0 [value β] is usually 35% or more, and particularly 40% or more, or 45% or more, or 50% or more, or 55% or more, or 60% or more. It should be noted that the details of this [value β] are related to the composition of the present invention, as described above.

[0312] In the present invention, it is preferred to treat in such a way that the number of starch granule structures before and after stage (ii) is reduced. The principle is not clear, but it is believed that by processing the composition under the following high temperature, high pressure and strong mixing conditions in a state where the starch granule structure is destroyed, the starch is diffused into the entire composition in a matrix form, and the branched starch in the starch forms a structure that is easy to show elasticity when retaining water. Specifically, the composition of the present invention preferably satisfies the following (c) and / or (d), and more preferably satisfies (c) and (d) at the same time.

[0313] (c) when a 6% suspension of the pulverized product of the composition is observed, the structure of the starch granules visible before and after stage (ii) is reduced by more than 5%;

[0314] (d) When a 14 mass % aqueous slurry of the pulverized composition is heated from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer, the gelatinization peak temperature decreases by 1°C or more before and after stage (ii).

[0315] In the present invention, the starch granule structure visible when observing a 6% suspension of the crushed material of the composition as specified in (c) is preferably reduced by 5% or more before and after stage (ii) (that is, the reduction ratio specified by "{(the number of starch granule structures in the composition before stage (ii))-(the number of starch granule structures in the composition after stage (ii))} / the number of starch granule structures in the composition before stage (ii)" is a numerical value above a certain degree). Among them, it is preferably set to 10% or more, more preferably to 15% or more, particularly preferably to 20% or more, or 25% or more, or 30% or more, or 35% or more, or 40% or more, or 45% or more, and particularly preferably to 50% or more. There is no particular limitation on the upper limit, for example, it can usually be set to 100% or less, or 95% or less. In particular, when observing a 6% suspension of the crushed material of the green composition of stage (i), the number of visible starch granule structures exceeds 100, or exceeds 200, or exceeds 300, it is preferred to carry out the treatment of stage (ii) in a manner that achieves the above-mentioned starch granule structure reduction rate before and after stage (ii).

[0316] In the present invention, the gelatinization peak temperature when measured by heating a 14% by mass composition pulverized product water slurry from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer as specified in (d) is preferably reduced by 1°C or more before and after stage (ii) (i.e., the temperature reduction difference specified by "(gelatinization peak temperature of the composition before stage (ii)) - (gelatinization peak temperature of the composition after stage (ii))" is a value of a certain degree or more). Among them, it is preferably set to 2°C or more, more preferably to 3°C or more, particularly preferably to 4°C or more, or 5°C or more, or 6°C or more, or 7°C or more, or 8°C or more, or 9°C or more, and particularly preferably to 10°C or more. The upper limit is not particularly limited, and for example, it can be usually set to 70°C or less, or 65°C or less, or 60°C or less, or 55°C or less, or 40°C or less, or 35°C or less. In particular, when the gelatinization peak temperature measured by heating a 14 mass % aqueous slurry of the pulverized composition from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer in stage (i) exceeds 100°C, exceeds 110°C, or exceeds 120°C, it is preferred to carry out the treatment in stage (ii) so as to achieve the above-mentioned temperature drop difference before and after stage (ii).

[0317] (4) Stage (iii): Cooling and mixing

[0318] If the composition is decompressed without cooling after the above-mentioned stage (ii), the water in the composition evaporates rapidly and the composition swells, which is not preferred. Therefore, it is preferred that after the kneading treatment under high temperature conditions, the temperature of the composition is cooled to generally below 100°C, below 97°C, further below 95°C, and particularly below 92°C in a manner that the composition does not swell. It is particularly preferred to perform the cooling treatment under certain pressurized conditions. In this case, the pressurized conditions during cooling are not particularly limited as long as they can prevent the expansion of the composition, and are preferably the same as the pressure during the kneading treatment. Specifically, the lower limit of the pressure to be further applied on the basis of atmospheric pressure during cooling is generally set to 0.01MPa or more, wherein it is preferably set to 0.03MPa or more, further preferably set to 0.05MPa or more, or 0.1MPa or more, or 0.2MPa or more, and particularly preferably set to 0.3MPa or more. On the other hand, the upper limit of the pressure to be further applied on the basis of atmospheric pressure during cooling is not limited, for example, it can be set to 5MPa or less.

[0319] In addition, by further reducing the outlet temperature setting of the extruder while maintaining the total mass flow rate above a certain degree, the pressure during mixing (ii) is increased, and the structure formation in the composition is promoted, which is more preferred. For example, in the case of using an extruder, these conditions can be appropriately adjusted as long as the outlet pressure is above a certain degree, generally as shown below. That is, the upper limit of the outlet temperature of the extruder is usually set to less than 95°C, preferably less than 90°C, more preferably less than 85°C, or less than 80°C, or less than 75°C, or less than 70°C, or less than 65°C, or less than 60°C, or less than 55°C, or less than 50°C, or less than 45°C, and particularly preferably less than 40°C. On the other hand, the lower limit of the temperature is not particularly limited, for example, it can usually be set to more than 0°C, or more than 4°C. In addition, the total mass flow rate is also not limited, for example, it can usually be set to more than 0.5kg / hour, wherein it can be set to more than 0.7kg / hour, and further can be set to more than 1.0kg / hour.

[0320] In addition, the temperature difference between the maximum heating temperature during kneading in stage (ii) and the cooling temperature in stage (iii) is preferably greater than a specified value. Specifically, the temperature difference between the maximum heating temperature during kneading in stage (ii) (the temperature of the highest heating portion when an extruder is used) and the cooling temperature in stage (iii) (the outlet temperature when an extruder is used) is usually greater than 15°C, preferably greater than 20°C, more preferably greater than 25°C, and particularly preferably greater than 30°C. By making the temperature difference greater than the lower limit, the outflow of insoluble components and soluble components from the resulting composition is suppressed, thereby suppressing the cohesiveness of the composition, and a composition having more excellent properties while maintaining elasticity can be obtained, which is therefore preferred.

[0321] It should be noted that, as described above, the solid composition containing starch of the present invention can be a composition with expansion (expanded composition), or a composition without expansion (non-expanded composition), preferably a non-expanded composition. In the past, extruders were mostly used to make expanded products represented by puffs, but their manufacturing conditions were usually set to the cooling conditions of stage (iii) exceeding the conditions of the expansion temperature of the composition, so it is particularly difficult to apply to the manufacturing method of the composition without expansion. This is because, since the internal temperature of the extruder changes continuously, if, for example, only the heating conditions during mixing are used, the outlet temperature setting is adjusted to a suitable low temperature, then due to the influence of reducing the outlet temperature setting, the temperature during mixing is represented, and the internal temperature is reduced as a whole, becoming a completely different condition, which is not an adjustment that can be properly made by a person skilled in the art. In addition, when making an expanded product represented by a puff, in order to make it expand rapidly during decompression, it is a technical common sense of a person skilled in the art to reduce the proportion of water in its total mass flow rate, and there is no motivation to increase the content of water in the total mass flow rate as in a composition without expansion.

[0322] In addition, the composition after stage (iii) can also be placed on a conveyor belt for transportation. In this case, there is no restriction on the type of conveyor belt, and preferably a mesh conveyor belt with ventilation (preferably ventilation and water / liquid permeability) on a part or all of the loading surface. By adopting such a mesh conveyor belt, various treatments such as the following water retention treatment, moisture content adjustment treatment, and drying treatment can be easily implemented for the composition being transported. It should be noted that the details of these treatments when using the mesh conveyor belt will be described later.

[0323] (5) Stage (iv): Water retention treatment

[0324] The composition obtained through the above-mentioned stages (i) to (ii) or (i) to (iii) can be directly used as the composition of the present invention, and a stage (iv) can be further provided to make the dry basis moisture content of the composition lower than 25% by mass. It should be noted that part or all of such stage (iv) can be achieved in one or more stages of the above-mentioned stages (i) to (iii), or a separate stage can be provided after the above-mentioned stages (i) to (iii). Among them, in the manufacturing method of the present invention, in the stage after stage (ii), a structure in which the time required from the temperature of the composition being reduced to less than 80°C to the dry basis moisture content of the composition being less than 25% by mass is greater than a prescribed value is adopted, which is preferred because it is a good quality that makes it difficult for the compositions to adhere to each other. Specifically, in the stage after stage (ii), from the temperature of the composition is reduced to less than 80 ° C, with a dry basis moisture content of 25% by mass or more, it is usually maintained for more than 10 minutes, preferably for more than 15 minutes, more preferably for more than 20 minutes, or more than 30 minutes, or more than 40 minutes, or more than 50 minutes, and particularly preferably for more than 60 minutes. The reason is not clear, but it is believed that the starch in the gelatinized composition in the process (ii) is aged, thereby producing a composition property that is difficult to bond to each other. The upper limit of the time is not particularly limited, for example, it can usually be set to less than 2400 minutes or less than 1800 minutes.

[0325] The temperature of the composition in stage (iv) is not limited, and is usually set to 90°C or less, preferably 80°C or less, more preferably 70°C or less, and particularly preferably 60°C or less. The lower limit of the temperature of the composition is not particularly limited, for example, it can usually be set to more than 0°C, or more than 4°C. The pressure conditions in stage (iv) are not limited, for example, it can be set to normal pressure. In addition, in the case of a stage (drying treatment, etc.) in which the moisture content of the composition is reduced, a water retention treatment may be performed before the moisture content is reduced, a water retention treatment may be performed while the moisture content is reduced, or a moistening treatment may be performed after the moisture content is reduced. It should be noted that a water retention treatment before the moisture content is reduced can more significantly exert the effect of the present invention, and is therefore preferred.

[0326] The degree of starch gelatinization in the composition after the water retention treatment in stage (iv) is not particularly specified, and is generally 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 40% by mass or more, particularly preferably 50% by mass or more, and generally 98% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, particularly preferably 85% by mass or less, and particularly preferably 80% by mass or less. In addition, it is preferred that the degree of gelatinization before and after the water retention treatment is reduced by a predetermined ratio or more (that is, the difference in the degree of gelatinization reduction calculated by "(the degree of gelatinization of the composition before the water retention treatment) - (the degree of gelatinization of the composition after the water retention treatment)" is a certain degree or more). Specifically, the water retention treatment is performed until the difference in the degree of gelatinization reduction of the composition is reduced by 1% by mass or more by the water retention treatment in stage (iv) provided after stage (ii), preferably by 2% by mass or more, more preferably by 3% by mass or more, particularly preferably by 4% by mass or more, and particularly preferably by 5% by mass or more. The upper limit is not particularly limited, and for example, it can generally be set to 50% by mass or less.

[0327] (6) Adjustment of the water content of the composition

[0328] It should be noted that, as an example of a method for promoting the above-mentioned aging, it is preferred that water is added to the composition in any of the above-mentioned stages (i) to (iii) to adjust the dry basis moisture content of the green composition to exceed the specified value, and it is preferred that water is added to the composition in stage (i) to adjust the dry basis moisture content of the green composition to exceed the specified value. Specifically, the dry basis moisture content of the composition is usually more than 40% by mass, preferably more than 45% by mass, more preferably more than 50% by mass, particularly preferably more than 55% by mass, or more than 60% by mass, or more than 65% by mass, or more than 70% by mass, or more than 75% by mass, and particularly preferably more than 80% by mass. The upper limit of the dry basis moisture content of the composition is not particularly limited, and for example, it can usually be set to less than 200% by mass, or less than 175% by mass, or less than 150% by mass.

[0329] As a specific method for adjusting the moisture content of the composition in this way, there is no limitation, and it includes a method of adding water to a part or all of the water mixed during the production in one or more stages among stage (i), stage (ii), stage (iii) and stage (iv). Among them, it is preferred that after the composition is adjusted to a dry basis moisture content exceeding a certain degree in stage (i), after stage (i), more specifically, in one or more stages among stage (ii), stage (iii) and stage (iv), the remaining amount of water mixed during the production is added with water. Specifically, in stage (i), the dry basis moisture content of the composition is usually more than 25% by mass, preferably more than 30% by mass, more preferably more than 35% by mass, particularly preferably more than 40% by mass, or more than 45% by mass, or more than 50% by mass, or more than 55% by mass, or more than 60% by mass, or more than 65% by mass, or more than 70% by mass, or more than 75% by mass, and particularly preferably more than 80% by mass. The upper limit of the dry basis moisture content of the composition in stage (i) is not particularly limited, and can be, for example, generally set to 200% by mass or less, or 175% by mass or less, or 150% by mass or less. In addition, when preparing the green composition of the above-mentioned stage (i), it is preferred to add water in a predetermined ratio of the water mixed during its production (especially the water mixed in stages (i) and (ii)). Specifically, it is preferred that when preparing the green composition of stage (i), generally 50% or more, 55% or more, further 60% or more, or 75% or more, or 80% or more, or 85% or more, or 90% or more, and particularly 100% of the water mixed during production (especially the water mixed in stages (i) and (ii)) is mixed with other raw materials.

[0330] Water can be added in the form of water or steam, preferably in the form of water. In addition, when an extruder is used, water can be added to the raw materials before being put into the extruder, or water can be added to the raw materials in the extruder after the raw materials are put into the extruder. It should be noted that when the raw materials are kneaded using an extruder, it also includes a method in which the composition of stage (i) is prepared in the extruder by adding water to the raw materials put in from the feeder, and then the stage (ii) is continuously carried out. It is preferred that when the green composition of the above stage (i) is prepared, water is added in advance to a predetermined ratio (usually 50% or more, particularly 55% or more, further 60% or more, or 75% or more, or 80% or more, or 85% or more, or 90% or more, particularly 100%) of the water mixed during its production (especially the water mixed in stage (i) and stage (ii)). In addition, water may be added arbitrarily to the extent that the dry basis moisture content of the raw material fed from the feeder is less than 40% by mass, and then the remaining amount (or all) of the water mixed during the production is injected from the water injection structure provided in the extruder barrel, thereby preparing the composition of stage (i) in the extruder, and then continuously performing stage (ii). In the case of adopting such a method, the composition may easily contain bubbles, so it is preferred to deaerate at any stage before the die head, specifically, it is preferred to deaerate in the deaeration structure of the feeder part and / or deaerate in the venting part provided in the barrel of the extruder described below. In addition, in the case of adopting a structure in which the water mixed during the production is injected from the water injection structure provided in the barrel of the extruder, it is preferred to use a twin-screw extruder.

[0331] In addition, by mixing the water mixed during the production with other raw materials at a predetermined ratio or more before the temperature in the extruder reaches a predetermined temperature or more, it is sometimes possible to suppress the change of the properties of the starch due to overheating, so it is preferred. Specifically, it is more preferred that the temperature in the extruder when mixing the water at a predetermined ratio or more with other raw materials usually reaches 90°C or more, or 85°C or more, or 80°C or more. The proportion of water mixed with other raw materials before reaching a predetermined temperature or more in the extruder is preferably 50% by mass or more of the water mixed during the production (especially the water mixed in stage (i) and stage (ii)) or more, wherein 60% by mass or more, further 70% by mass or more, or 80% by mass or more, or 90% by mass or more, and especially 100% by mass is mixed with other raw materials. When mixing water with other raw materials, it is preferred to pre-mix the water in the above ratio before the raw materials are put into the extruder. It is particularly preferred that 60% by mass or more of the water added during the production (particularly the water added in stages (i) and (ii)) be mixed with other raw materials before the temperature in the extruder reaches 80° C. or more. It is further preferred that 60% by mass or more of the water added during the production (particularly the water added in stages (i) and (ii)) be mixed with other raw materials before the temperature in the extruder is heated to 20° C. or more from the outside temperature.

[0332] Generally speaking, if the purpose is only to gelatinize starch, a dry basis moisture content of 40% or less by mass in the green composition is sufficient. If the subsequent drying process is considered, it can be said that there is not only no motivation to add more water, but also an obstacle. Therefore, if there is no idea of ​​aging the temporarily gelatinized starch, as in this stage (iv), it is difficult to think of increasing the dry basis moisture content in the green composition. In addition, even if the dry basis moisture content in the green composition is only increased, if there is no idea of ​​maintaining moisture, as in this stage (iv), which is contrary to the idea of ​​drying the water in the composition thereafter, it is believed that it is impossible to adopt the structure described above, especially after stage (iii), which ensures that the time required from lowering the temperature of the composition to below 80°C until the dry basis moisture content of the composition is below 25% by mass is above the specified value.

[0333] Alternatively, water may be added in the stage after stage (iii) (particularly in the case of using an extruder, to the extruded composition) so that the time until the dry basis moisture content of the composition reaches 25% by mass is longer than a predetermined time. Water may be added in the form of water or steam, preferably in the form of water, for example, by spraying water in a mist state, because this method is preferred because it can reduce the amount of water used in the manufacturing process and produce a composition of good quality. Alternatively, water may be added by directly placing the composition in water, thereby utilizing the water absorption of the composition.

[0334] In addition, for the composition to which water is added in the stage after stage (iii) (especially in the case of using an extruder, for the composition after extrusion), by adopting a method of making the water evaporate quickly after adding water, the temperature of the composition can be rapidly reduced by utilizing the heat of vaporization, and thus it is preferred. It is particularly preferred to perform the treatment while modulating in a manner such that the dry basis moisture content in the volatilized composition is less than 25% by mass. More specifically, for example, as described above, there can be cited a method of implementing a water retention treatment by conveying the composition after stage (iii) using a mesh conveyor belt having ventilation (preferably ventilation and water / liquid permeability) on a part or all of the carrying surface, while adding water to the composition before and after being placed on the conveyor belt (i.e., before or during transportation). Thus, the transportation of the composition and the above-mentioned treatment can be performed simultaneously, and thus it is preferred. In addition, it is also possible to perform a water retention treatment by spraying mist-like moisture on the composition after conveying with a conveyor belt.

[0335] As one mode of such water retention treatment, there is a mode in which the composition extruded by the extruder is placed on a conveyor, each of the compositions of the conveyor is immersed in water (i.e., a step of temporarily immersing the composition in a water tank during conveyance by the conveyor is provided), and then air is blown to the composition while conveying the composition by the conveyor. In addition, as another mode of water retention treatment, there is a mode in which water in a mist state is sprayed on the composition extruded by the extruder at any stage before or after being placed on the conveyor, the composition is placed on the conveyor, and air is blown to the composition while conveying the composition by the conveyor. In either case, by forming a mesh structure having ventilation properties (for example, when air is blown to the mesh from a vertical direction, 1% or more, or 3% or more of the air flow rate is passed through) on a part or the whole of the conveyor surface, the water added is easily volatilized during conveyance, the temperature of the composition can be effectively lowered by vaporization heat, and the time until the dry basis moisture content reaches 25% by mass can be adjusted. Therefore, it is preferred that air is blown from the upper part and / or the lower part of the mesh conveyor, especially in the mode in which air is blown to the composition while conveying the composition by the conveyor. The mesh size of the mesh structure is not particularly limited. Specifically, for example, the average mesh size is preferably 1 mm. 2 or more (specifically, 1 mm x 1 mm or more), or 3 mm 2 or more (specifically 3mm×1mm or more), or 10mm 2 On the other hand, the upper limit of the average mesh area is not particularly limited, and can be, for example, 2500 mm 2 less (specifically less than 50mm×50mm), or 1500mm 2 less (specifically less than 50 mm × 30 mm), or 500 mm2 or less (specifically, 20 mm×25 mm or less).

[0336] In addition, it is preferred that the gelatinization degree decreases by a predetermined ratio or more before and after the air supply treatment in which air is supplied from the upper part and / or the lower part of the mesh conveyor (i.e., the difference in gelatinization degree reduction calculated by "gelatinization degree of the composition before treatment - gelatinization degree of the composition after treatment" is a certain degree or more). Specifically, it is preferred that the water retention treatment is performed until the difference in gelatinization degree reduction decreases by 1% by mass or more, more preferably by 2% by mass or more, further by 3% by mass or more, particularly by 4% by mass or more, and particularly by 5% by mass or more. The upper limit is not particularly limited, but is generally 50% by mass or less.

[0337] In addition, even when the dry basis moisture content of the composition is temporarily 25% by mass or less, water can be added to the dry composition to increase the dry basis moisture content, thereby performing water retention treatment. When water is added to the dry composition, it is preferred that the retention time for more than half of the time thereafter is, for example, usually 60° C. or less, preferably 50° C. or less, and further 40° C. or less.

[0338] Alternatively, a method may be used in which the surrounding humidity is increased in the stage after stage (iii) (particularly when an extruder is used, for the composition after extrusion) so that the time until the dry basis moisture content reaches 25% by mass is longer than a predetermined time. This allows the starch near the surface of the composition, which normally loses water rapidly and is less susceptible to aging than the interior of the composition, to be locally aged. This is preferred in the case of preparing a composition to be eaten together with a plurality of compositions such as noodles, because the compositions are less likely to stick to each other and are easier to eat.

[0339] In addition, a method can also be used in which the temperature of the composition is rapidly reduced to a certain temperature or less in stage (iv) (especially in the case of using an extruder, for the composition after extrusion), so that the time until the dry basis moisture content reaches 25% by mass is longer than the prescribed time in the subsequent stage. More specifically, it is preferred that the temperature of the composition is generally reduced to 80°C or less, and more preferably to 70°C or less, or 60°C or less, or 50°C or less, or 40°C or less, at more than half of the time until the dry basis moisture content reaches 25% by mass. In addition, in the composition manufactured using an extruder, the temperature of the composition is generally preferably 80°C or less in the stage of extrusion from the outlet, and preferably 70°C or less, or 60°C or less, or 50°C or less, or 40°C or less, and it is more preferred to manufacture in a state where the outlet temperature is set to this temperature. The lower limit of the temperature is not particularly limited, and for example, it can generally be set to exceed 0°C or exceed 4°C.

[0340] For example, by providing a cooler capable of lowering the temperature of the composition at the flow path outlet of the die head to a predetermined temperature at the second screw flight portion and / or the die head of the barrel, the starch on the surface of the composition is more effectively aged, and the subsequent adhesion of the composition to each other is improved, which is preferred. In addition, by adopting a long-sized structure as the die head, the temperature of the composition is more easily reduced, which is preferred. In addition, it is preferred to adopt a method for rapidly volatilizing the water in the composition added with water in the stage after stage (iii) (especially in the case of an extruder, for the composition after extrusion) after the addition of water, and rapidly reducing the temperature of the composition by utilizing the heat of vaporization, thereby achieving the above conditions, and more preferably, the treatment is performed while adjusting the dry basis moisture content in the volatilized composition to be less than 25% by mass.

[0341] In addition, a method can also be adopted in which the internal temperature of the extruder (more specifically, after the kneading section) is lowered to a value lower than a prescribed value in stage (iii), thereby adjusting the time until the dry basis moisture content of the composition after extrusion from the inside of the extruder is lower than 25% by mass. Specifically, it is preferred that the internal temperature of the extruder (more specifically, after the kneading section) is usually adjusted to be lower than 95°C, and more preferably adjusted to be lower than 90°C, and further adjusted to be lower than 85°C, or lower than 80°C, or lower than 75°C, or lower than 70°C, or lower than 65°C, or lower than 60°C, or lower than 55°C, or lower than 50°C, or lower than 45°C, and particularly adjusted to be lower than 40°C. The lower limit is not particularly limited, and can usually be set to be higher than 0°C, or higher than 4°C. Thus, the time until the dry basis moisture content of the composition after extrusion from the inside of the extruder is less than 25% by mass is preferably adjusted to usually 10 minutes or more, wherein preferably adjusted to 15 minutes or more, further preferably adjusted to 20 minutes or more, or 30 minutes or more, or 40 minutes or more, or 50 minutes or more, particularly preferably adjusted to 60 minutes or more. The upper limit of such time is not particularly limited, for example, it can be usually set to 2400 minutes or less, and further can be set to 1800 minutes or less.

[0342] (7) Drying

[0343] In addition, if a stage (iii) or (iv) or the above-mentioned water retention treatment or surface aging treatment is further provided to adjust the dry basis moisture content to less than 25 mass % after the treatment, the dry basis moisture content of the composition is further provided to be less than a certain degree (so-called drying treatment), the starch aging in the composition is slowed down or no longer proceeds, and sometimes a composition of good quality is formed. In the case of providing such a stage, the dry basis moisture content in the final composition is adjusted to be generally less than 60 mass %, wherein less than 55 mass %, further less than 50 mass %, or less than 45 mass %, or less than 40 mass %, or less than 35 mass %, or less than 30 mass %, or less than 25 mass %, or less than 20 mass %, or less than 15 mass %. On the other hand, the lower limit of the dry basis moisture content in the composition is not limited, and from the viewpoint of industrial production efficiency, for example, it can be set to 0.5 mass % or more, or 1 mass % or more, or 2 mass % or more. The temperature of the composition during such drying treatment is not limited, but when the treatment is carried out under normal pressure, it is usually higher than 50°C, preferably higher than 60°C or higher than 70°C, and particularly preferably higher than 80°C. The upper limit is not particularly limited, but is lower than 100°C or lower than 98°C.

[0344] In addition, by adjusting the temperature of the composition in the drying treatment while slowly performing the drying treatment, the dry basis moisture content of the composition is reduced to less than 10% by mass in a relatively short time, and the composition after treatment (the dry basis moisture content of the composition is less than 10% by mass) is difficult to crack, and a composition of good quality is formed, which is preferred. Specifically, it is preferred to calculate the "relative humidity of the atmosphere obtained from the temperature of the composition at any time point" from the temperature of the composition in the treatment, and adjust the temperature of the composition in such a way that the average relative humidity of the entire treatment time is more than a certain proportion. That is, in the case where the moisture content of the composition is more than 10% by mass (for example, the dry basis moisture content is more than 25% by mass) in the treatment, by adjusting the temperature of the composition to a higher temperature within the range where the saturated water vapor content does not rise excessively, the absolute humidity in the atmosphere can be increased by evaporation of the moisture content of the composition, and the average relative humidity can be adjusted to more than a certain proportion. In addition, in the case where the moisture content in the composition is less (for example, the dry basis moisture content is less than 25% by mass), by adjusting the temperature of the composition to a lower temperature, the saturated water vapor content of the atmosphere can be reduced, and the average relative humidity can be adjusted to more than a certain proportion. More specifically, it is preferred that the average relative humidity in the treatment until the dry basis moisture content of the composition is below 10% by mass is usually 50RH% or more, wherein 55RH% or more, further 60RH% or more, or 65RH% or more, or 70RH% or more, or 75RH% or more, or 80RH% or more. In addition, it is preferred that the average relative humidity in the state where the dry basis moisture content of the composition is above 25% by mass and / or the average relative humidity when the dry basis moisture content of the composition is lower than 25% by mass and 10% by mass is above a certain proportion (above 50RH%, wherein 55RH% or more, further 60RH% or more, or 65RH% or more, or 70RH% or more, or 75RH% or more, or 80RH% or more), preferably at least the average relative humidity in the state where the dry basis moisture content of the composition is above 25% by mass is above a certain proportion, and particularly preferably all are above a certain proportion.

[0345] Furthermore, by adjusting the average relative humidity in the first half 40% of the time period from the start of the drying treatment until the dry basis moisture content of the composition reaches 10% by mass (a time period in which the moisture content of the composition is relatively high. More preferably, in this time period, for example, a time period in which the moisture content of the composition is 25% or more by mass), and / or the average relative humidity in the second half 60% of the time period from the start of the drying treatment until the dry basis moisture content of the composition reaches 10% by mass (a time period in which the moisture content of the composition is relatively low. More preferably, in this time period, for example, a time period in which the moisture content of the composition is less than 25% by mass) to a certain ratio or more, cracks are less likely to occur in the composition after the drying treatment (the dry basis moisture content of the composition is less than 10% by mass), and a composition of good quality is obtained. Therefore, it is preferred, particularly preferred that the average relative humidity in any time period is above a certain ratio. Specifically, it is preferred to carry out the treatment in a manner such that the average relative humidity in the first 40% of the time period before the start of the drying treatment and / or the average relative humidity in the second 60% of the time period after the start of the drying treatment is 50RH% or more, particularly 55RH% or more, further 60RH% or more, or 65RH% or more, or 70RH% or more, or 75RH% or more, or 80RH% or more.

[0346] When the drying treatment is performed under the above conditions, any method used for drying foods may be used to adjust the temperature of the composition. For example, it is preferred to adjust the temperature of the composition and / or the temperature of the atmosphere by air drying.

[0347] In addition, the pressure in the drying process is not particularly limited, and the drying process may be carried out under normal pressure or under reduced pressure. When the process is carried out under reduced pressure (e.g., less than 0.1 MPa), the temperature of the composition is preferably set to 80°C or less, preferably 70°C or less, or 60°C or less, and particularly preferably 50°C or less. The lower limit is not particularly limited, but is usually higher than 0°C or higher than 4°C.

[0348] As a drying method, any method generally used for food drying can be used. As examples, freeze drying, air drying (e.g., ventilation drying (hot air drying), fluidized bed drying, spray drying, drum drying, low temperature drying, sun drying, shade drying, etc.), pressurized drying, reduced pressure drying, microwave drying, oil heat drying, etc. can be listed. Among them, from the viewpoint that the degree of change of the color tone or flavor originally possessed by the food material is small and the aroma (burnt taste, etc.) other than the food can be controlled, microwave drying is preferred, and microwave drying under reduced pressure is further preferred. In addition, from the viewpoint of processing a large amount of compositions, air drying (e.g., hot air drying, fluidized bed drying, spray drying, drum drying, low temperature drying, sun drying, shade drying, etc.) is preferred, and ventilation drying (especially hot air drying with an atmosphere temperature within a certain range) is particularly preferred.

[0349] In addition, in the drying treatment stage, by treating the composition for a certain period of time or more in an environment where the atmospheric temperature exceeds a certain level, the time until the dry basis moisture content decreases by more than a specified proportion becomes shorter, which is preferred. Specifically, it is preferred to treat in an environment where the lower limit of the atmospheric temperature is usually more than 50°C, more than 60°C, further more than 70°C, or more than 80°C. There is no particular limit to the upper limit, which is usually 100°C or less. In order to form an environment where the atmospheric temperature exceeds a certain level, a method can be adopted in which the composition extruded from the die head is stored in a high temperature environment, or the atmospheric temperature is increased by maintaining the temperature of the extruded composition at a high temperature, or a method of using high temperature air for ventilation drying and the like to achieve a specified atmospheric temperature.

[0350] In addition, the treatment time under this atmosphere temperature can be adjusted to usually more than 0.1 hour as long as it is more than a certain time, wherein can be adjusted to more than 0.2 hour, or more than 0.3 hour, or more than 0.4 hour, or more than 0.5 hour, or more than 0.6 hour, or more than 0.7 hour, or more than 0.8 hour, or more than 0.9 hour, particularly can be adjusted to more than 1.0 hour.The upper limit of such time is not particularly limited, for example, can be set to less than 20 hours or less than 15 hours usually.

[0351] It should be noted that the dry basis moisture content in the composition of the present invention may be derived from various components of the composition or from further added water. In particular, by further including a step of reducing the dry basis moisture content to less than 25% by mass after the step (iv), a composition is formed in which the starch near the surface of the starch gelatinized in (ii) is locally aged. When a composition is prepared to be eaten together with a plurality of compositions such as noodles, the compositions may be less likely to stick to each other and may be easily eaten, which is preferred.

[0352] (8) Extruder

[0353] In the case of using an extruder (sometimes also referred to as an extruder) in the present invention, it is preferred to use an extruder having a screw rotated by a motor, a barrel surrounding the outer periphery of the screw, a feeder for feeding food raw materials installed on the base side of the barrel, and a die head installed on the front end side of the barrel. Among them, in the present invention, as the screw of the extruder, it is preferred to use a screw having the following structure: from the base side toward the front end side (that is, toward the extrusion direction), there is a first screw wing and a kneading section, and the barrel has a vent at a position corresponding to the front end side of the kneading section of the screw. According to one embodiment, as a barrel, a barrel having a structure in which the vent and the die head are set as one body can be used. In addition, according to other embodiments, as a screw, a screw having a structure having a second screw wing at the front end side of the kneading section in addition to the first screw wing and the kneading section can be used, and as a barrel, a barrel having a structure having a vent at a position corresponding to the starting point of the base side of the second screw wing of the screw (that is, a structure in which the die head is arranged immediately after the kneading section) can be used. Furthermore, when the barrel has a heater in the regions corresponding to the first flight section and the kneading section and optionally has a second flight section, it is preferred that a cooler be provided in the corresponding region.

[0354] In the screw used in the present invention, the first flight portion refers to an area on the outer peripheral surface where screw flights are formed and which exists on the base side (motor side) relative to most of the kneading section (preferably all of the kneading section) and all of the second flight portions, and the arbitrarily arranged second flight portion refers to an area on the outer peripheral surface where screw flights are formed and which exists on the front end side (extrusion side) relative to all of the first flight portions and most of the kneading section (preferably all of the kneading section).

[0355] In the present invention, the first screw flight portion has the function of heating the composition by using a heater while conveying the composition to the front end side as the screw rotates, so that the starch granules in the composition are swollen by adding water due to heating, and the arbitrarily arranged second screw flight portion has the function of conveying the composition conveyed from the kneading section to the die head on the front end side as the screw rotates under reduced pressure, homogenizing the composition with a destroyed starch granule structure in a manner that is difficult to generate heat to form a starch matrix structure, and rapidly cooling the composition, thereby causing local aging of the starch near the surface of the composition.

[0356] It should be noted that in the present invention, the screw flight structure that conveys the composition toward the front end side as the screw rotates is sometimes referred to as a "positive screw flight", and conversely, the screw flight structure that conveys the composition toward the base side is referred to as a "negative screw flight". In addition, in the first screw flight portion and the second screw flight portion, the area where the positive screw flight is provided is sometimes referred to as a "positive screw flight portion", and the area where the negative screw flight is provided is sometimes referred to as a "negative screw flight portion".

[0357] In the screw of the extruder using the screw and barrel having the second flight portion used in the present invention, the kneading section refers to a known structure for kneading in which most of it (preferably 70% or more, more preferably 90% or more, and particularly preferably 100%) exists between the first flight portion and the second flight portion (as specific examples, Maddock mixing section, Egan mixing section, foaming mixing section, needle mixing section, Dulmage mixing section, Saxon mixing section, pineapple-shaped mixing section, grooved screw mixing section (described below), cavity moving type mixing section, or a combination thereof, etc. can be cited). In addition, in the screw of the extruder using the screw and barrel without the second flight portion, the kneading section refers to a known structure for kneading in which most of it (preferably 70% or more, more preferably 90% or more, and particularly preferably 100%) exists on the front end side relative to the first flight portion. In the screw used in the present invention, the kneading section has the function of cutting off the composition flow for kneading in a manner that can damage starch granules by high-temperature strong kneading under pressure.

[0358] The length of the kneading section is not limited, and it is preferred that the length is more than a certain degree relative to the total length of the screw, because it is easy to damage the starch granules by high-temperature strong kneading under pressure. Specifically, the ratio of the length of the kneading section to the total length of the screw is usually 20% or more, preferably 25% or more, or 30% or more, or 35% or more, or 40% or more, or 45% or more, or 50% or more. On the other hand, there is no upper limit on the ratio of the length of the kneading section to the total length of the screw, and it is usually preferably set to less than 80%, or less than 70%, or less than 60% due to the balance with other parts.

[0359] In addition, in the kneading section, by providing one or more narrow structures on the screw to block the flow of the green body, the starch granules are easily damaged, so it is preferred. The "narrow structure" in the present invention is a structure in which the space between the screw and the inner wall of the barrel is roughly divided into the space on the base side and the front end side, and the green body is filled with the green body inside the divided base side space, and the internal pressure of the green body is increased by more than a specified proportion, thereby causing the green body passing through the narrow structure to produce an extension flow. The "extension flow" in the present invention is the flow of the stretched material, which is also called the elongation flow, and is typically generated by guiding the material to a flow path that is wide on the inlet side and narrow on the outlet side, in other words, a flow path in which the opening cross-sectional area is rapidly deformed along the flow direction. As an example of a narrow structure, a relatively raised structure (sometimes referred to as a convex structure) can be provided on the surface of the screw, and a structure in which the cross-sectional area of ​​the flow path from the base side to the front end side in any flow path is relatively reduced can also be provided, and a structure formed by combining them can also be provided. As a convex structure, it is preferred that, for example, a convex structure is provided on the surface of the screw in the kneading section, which bulges to near the inner wall of the barrel (specifically, more than 80% of the distance from the center of the screw to the inner wall of the barrel), and the space between the screw and the inner wall of the barrel is roughly divided into a structure of the space on the base side and the front end side by using the convex structure. In addition, by arranging two or more narrow structures roughly in series, a complex elongational flow is generated, which improves the effect of the present invention, and is therefore preferred. Specifically, the number of narrow structures arranged roughly in series is usually preferably more than 2, or more than 3, or more than 4. There is no particular upper limit, and it is usually less than 50. In addition, in the case of arranging more than two narrow structures roughly in series, it is preferred to include more than one convex structure.

[0360] When a vent is used in the present invention, as described above, the vent is attached to the barrel at a position corresponding to the front end of the kneading section and is configured to exhaust gas in the space between the barrel and the screw to adjust the pressure.

[0361] Specifically, in the case of using a screw and barrel having a second flight portion, the vent is preferably provided at a position of the barrel corresponding to the starting point on the base side of the second flight (i.e., near the boundary with the kneading section). In this way, when moving from the kneading section to the second flight, the pressure is rapidly reduced by using the vent, and while the composition in a state where the starch granule structure is destroyed is homogenized in a non-heat-generating manner to form a starch matrix structure, the starch near the surface of the composition can be locally aged by rapidly cooling the second flight immediately thereafter.

[0362] In addition, in the case of using a screw and barrel without a second screw flight portion, the vent is preferably provided integrally with the die head, and a structure that also functions as a vent is adopted by opening the composition under atmospheric pressure in the die head. In this way, by opening the composition under atmospheric pressure in the die head that functions as a vent, the pressure is rapidly reduced, thereby making a composition in a state where the starch granule structure is destroyed, and then by rapidly cooling the extruded composition (for example, by spraying a mist of water to volatilize a small amount of water, thereby using its vaporization heat to rapidly reduce the temperature of the composition, etc.), the starch near the surface of the composition can be locally aged.

[0363] The specific position of the vent is not limited. For example, when a screw and a barrel having a second flight portion are used, the vent is preferably arranged at the front half of the second flight portion of the screw, that is, at a position on the barrel within 50% of the total length of the second flight portion from the starting point on the base side of the second flight portion in the working state where the screw is arranged in the barrel, and is further preferably arranged at a position on the barrel within 20% of the total length of the second flight portion from the starting point of the second flight portion, and is most preferably arranged at a position on the barrel equivalent to the end portion on the base side (that is, near the boundary between the second flight portion and the kneading section). The reason is not clear, but it is presumed that the rapid pressure drop in the vent causes the starch granule structure in the composition to be destroyed, and the starch inside flows out to form a uniform matrix structure.

[0364] On the other hand, in the case of using a method of using a screw and a barrel without a second flight portion, that is, in the case of a method of using a structure that also functions as a vent by opening the composition under atmospheric pressure in the die head, the vent (also the die head) is preferably arranged at a position on the barrel equivalent to within 30% of the total length of the screw from the end point of the kneading section arranged at the front end side of the screw, preferably at a position on the barrel equivalent to within 20%, preferably at a position on the barrel equivalent to within 10%, preferably immediately after the end point of the kneading section arranged at the front end side (that is, a die head having the function of a vent is arranged immediately after the kneading section). In addition, it is preferred to provide a flow delay structure between the end point of the kneading section arranged at the front end side of the screw and the die head. In addition, it is also possible to locally age the starch near the surface of the composition by cooling the die head and / or the composition after extrusion without providing the second flight portion on the screw.

[0365] In addition, in the present invention, when using an extruder with a screw and a barrel having a second flight portion (sometimes referred to as the first mode), it is preferred to set a flow delay structure at a position between the end point of the front end side of the second flight portion and the die head, or when using an extruder with a screw and a barrel without a second flight portion (sometimes referred to as the second mode), it is preferred to set a flow delay structure at a position between the end point of the front end side of the kneading section and the die head. In particular, in an extruder having a second flight portion, by setting a flow delay structure, a composition that has increased viscosity due to aging in the second flight portion can be stably discharged, and thus it is preferred. In addition, even in an extruder without a second flight portion, by setting a flow delay structure, a stable extrusion effect can sometimes be obtained, and thus it is preferred. In addition, in any of the first and second modes, by setting a flow delay structure near the end point of the front end side of the kneading section (preferably immediately after the end point of the front end side of the kneading section), the pressure in the kneading section is increased, and the kneading efficiency is increased, and thus it is preferred. In the present invention, a "flow delay structure" is a structure that reduces the flow velocity of the contents relative to the average flow velocity of the contents in the flight portion before the structure. For example, in the first embodiment, the flow rate of the contents in the second screw flight section is reduced, and in the second embodiment, the flow rate of the contents in the first screw flight section is reduced. For example, the following structures may be used: a structure in which the flow rate is reduced by relatively increasing the screw groove depth or pitch width near the end point on the front end side of the second screw flight section, or a structure in which the flow rate is reduced by relatively increasing the inner diameter of the barrel near the end point on the front end side of the second screw flight section than before, or a structure independent of the second screw flight section, in which a flow delay structure is arranged at a position between the end point on the front end side of the second screw flight section in the first embodiment or the end point on the front end side of the kneading section in the second embodiment and the die head, a structure in which a hole is opened in a part of the forward screw flight section in the screw flight structure forming part, or a part of the forward screw flight section is defective or deformed (sometimes also referred to as a grooved screw structure), or a structure in which the flow rate is relatively reduced compared to the forward screw flight structure. A reverse spiral flight structure for increasing the flow rate, or a ring structure having a spiral angle that does not apply displacement to the molding material (for example, a structure in which one or more annular protrusions having a radius of more than 80% of the distance between the rotation center of the screw and the inner wall of the barrel are arranged on the surface of the screw, and a multiple ring structure in which the annular protrusions are arranged in series along the rotation axes of more than two screws) is adopted, which reduces the flow rate generated by the rotation of the screw compared to the forward spiral flight structure and reduces the flow rate. Preferably, a grooved screw structure or a reverse spiral flight structure or a multiple ring structure is arranged at a position between the front end side end of the second spiral flight portion in the first mode or the front end side end of the kneading portion in the second mode and the die head as a flow delay structure.In addition, when a multiple ring structure is adopted in which a ring-shaped protrusion structure having a radius of more than 80% of the distance between the rotation center of the screw and the inner wall of the barrel is formed on the surface of the screw, the flow speed in the flow delay structure can be easily adjusted by continuously arranging two or more protrusion structures, which is preferred.

[0366] The flow delay ratio in the flow delay structure (i.e., the ratio of the flow rate in the flow delay structure to the flow rate in the screw flight portion before the structure) can be less than 100%, and is usually preferably 97% or less, preferably 95% or less, and more preferably 93% or less, or 90% or less. The lower limit is not particularly limited, and is usually 10% or more, or 20% or more.

[0367] In addition, when a flow delay structure is adopted, if its size is too large, the size of the kneading section or the second screw flight section structure etc. becomes relatively small, so from the viewpoint of exerting the effect of the present invention, it is preferred that the size of the flow delay structure is below a certain degree. Specifically, the ratio of the length of the flow delay structure to the total length of the screw is usually preferably 20% or less, preferably 15% or less, more preferably 10% or less, or 8% or less, or 5% or less. The lower limit is not particularly limited, and is usually 0% or more, or 1% or more.

[0368] In addition, the vent can be a structure by opening under atmospheric pressure and the barrel interior is decompressed to atmospheric pressure, but by having a forced exhaust structure in the vent, a part of the moisture in the composition is forced to volatilize, while the composition is rapidly cooled, the bubble in the matrix structure is removed, thus a more solid matrix structure can be formed, thus more preferably, particularly in the case of adopting a single-screw extruder that is easy to bring bubbles into the composition interior as an extruder, owing to easily bringing bubbles into the matrix structure, so the structure is more useful. Known vacuum pumps etc. can be adopted when forced exhaust, for example, liquid-sealed pumps (water-sealed pumps) can be adopted.

[0369] As long as the structure (such as a vacuum pump, etc.) for forced exhaust has the ability to force a portion of the water in the composition to evaporate to the temperature of the composition in the venting portion to a certain extent, any structure can be adopted. In the case where a vent is configured at the front end of the kneading section, it can also be set as a structure that has the function of opening the composition at atmospheric pressure as a vent in the die head (i.e., a structure of configuring the die head immediately after the kneading section). In addition, according to one embodiment, it is preferred to have a cooling capacity in the vent, such as a temperature that is usually reduced by more than 1°C, wherein the temperature is reduced by more than 2°C. In addition, according to one embodiment, it is preferred to adopt a structure that forces exhaust under the conditions that the suction pressure in the vent is usually more than 0.04MPa, wherein it is more than 0.06MPa, and further more than 0.08MPa. The upper limit of the suction pressure in the vent is not particularly limited. If an overly powerful pump is used, the green body may sometimes be sucked in, so it is usually preferably less than 0.1MPa or less than 0.09MPa. In principle, an extruder for producing a puffed product needs to increase its internal pressure to at least atmospheric pressure and maintain the composition temperature at 100° C. or higher during extrusion, so it is difficult to adopt a structure like the present invention.

[0370] In the case of using an extruder in the manufacturing method of the present invention, by mixing a predetermined proportion or more of the water mixed in the composition during its manufacturing process with other raw materials before being heated to 20°C or more in the extruder, it is sometimes possible to suppress the change of the properties of the starch due to overheating, so it is preferred. Specifically, it is preferred that before being heated to 20°C or more in the extruder, generally 50% by mass or more, 60% by mass or more, further 70% by mass or more, or 80% by mass or more, or 90% by mass or more, and especially 100% by mass of the water mixed in the composition is mixed with other raw materials in advance, and / or before being heated to 20°C or more in the extruder, the dry basis moisture content exceeds 25% by mass, or exceeds 30% by mass, or exceeds 35% by mass, or exceeds 40% by mass. It should be noted that, when mixing water with other raw materials, it is preferred to pre-mix the water in the above proportion before the raw materials are put into the extruder.

[0371] In addition, if water is injected while the inside of the extruder is heated to a predetermined temperature or higher, the water may boil over and damage the composition structure. Therefore, it is preferred that the water in the above ratio (usually 50% by mass or more, particularly 60% by mass or more, further 70% by mass or more, or 80% by mass or more, or 90% by mass or more, particularly 100% by mass of the water mixed in the composition in step (i), and / or water is added until the dry basis moisture content of the green composition exceeds 25% by mass, exceeds 30% by mass, exceeds 35% by mass, exceeds 40% by mass, or is 200% by mass or less, or is 175% by mass or less, or is 150% by mass or less) is mixed with other raw materials in advance while the temperature inside the extruder is lower than the predetermined temperature. Specifically, it is preferred that the water in the above ratio is mixed with other raw materials in advance while the temperature inside the extruder is usually lower than 100°C, particularly lower than 90°C, further lower than 80°C, lower than 70°C, lower than 60°C, lower than 50°C, and particularly lower than 40°C. Furthermore, by using the green composition processed under the above conditions (for example, using an extruder) in step (i) to produce the composition of the present invention, a part of the high-temperature intensive kneading required for processing the composition can be performed in the green composition production step.

[0372] Especially for the composition that uses extruder to carry out strong mixing as the present invention, if the water addition of green body is increased, the viscosity of green body increases, and with it, the resistance during mixing increases, or the internal pressure rises, and if there is a stirrer with the same capacity, the mixing strength (SME value) tends to decrease. In addition, when using a heater with the same capacity, the heating process of the green body composition that can not fully increase the specific heat with the addition of water and the cooling process thereafter, etc., are produced, so the starch processing in the present invention is greatly affected. Therefore, in the prior art, the method of adding water in large quantities to the green body composition is generally not adopted, and even when adding water in advance, the proportion occupied in all the water additions is also limited.

[0373] When an extruder is used in the production method of the present invention, it is preferable to mix a predetermined proportion of the water content added to the composition during the production process (usually 50% by mass or more, particularly 60% by mass or more, further 70% by mass or more, or 80% by mass or more, or 90% by mass or more, particularly 100% by mass, and / or add water until the dry basis moisture content of the green composition exceeds 25% by mass, exceeds 30% by mass, exceeds 35% by mass, exceeds 40% by mass, or is 200% by mass or less, or is 175% by mass or less, or is 150% by mass or less of the water content added to the composition in the step (i)) with other raw materials before the extruder is pressurized (pressurized). This can sometimes suppress changes in the properties of the starch due to overheating. Specifically, it is preferred that 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, and particularly 100% of the water content added during the production process is mixed with other raw materials before the extruder is pressurized (pressurized). It should be noted that it is more preferred to mix the water content in these proportions with other raw materials before the inside of the extruder is heated and pressurized to 100° C. or more.

[0374] When an extruder is used in the manufacturing method of the present invention, its type is not limited, and it is preferred that an extruder that can implement each treatment of watering, strong mixing (minimum SME value is 400kJ / kg or more), heating, cooling, and extrusion molding in one unit. An extruder having a structure that can add water to the raw material before heating and pressurization is particularly preferred. Specifically, a uniaxial extruder or a biaxial extruder can be used, but compared with a general uniaxial extruder, a uniaxial extruder or a biaxial extruder that adopts the following special barrel to improve the mixing strength is preferably used. In particular, from the viewpoint of economy, a uniaxial extruder is preferred, and from the viewpoint of obtaining a higher mixing force, a biaxial extruder is preferred. On the other hand, an extruder using a common barrel, a screw extruder using a common screw (driving screw), or a common screw-propelled device is a device whose main purpose is to quickly deliver the contents, and the mixing force is insufficient, so it is sometimes not suitable for the manufacturing method of the present invention.

[0375] Generally speaking, in the devices called single-axis extruders or twin-axis extruders (especially in overseas devices called extruders and twin-screw extruders), there are also extrusion devices with only simple mixer and kneader functions, but such devices cannot obtain strong mixing for forming the composition structure of the present invention, and are therefore not preferred. In addition, in the case of using a composition raw material having a starch granule structure, its structure is strong, and in order to completely destroy the starch granule structure, the mixing force of an extruder using only a conventional spiral screw is insufficient, and it is further preferred to use a barrel portion with a kneading effect significantly more than usual. Specifically, by making the proportion of the spiral screw portion relative to the total length of the barrel in the extruder 95% or less, the composition is strongly mixed, and the formation of the characteristic structure of the composition of the present invention is promoted, and therefore it is preferred. The spiral screw portion is the most general shape of the barrel portion, which is also called a conveying element. If its proportion relative to the total length of the barrel is increased, the ability to extrude the green composition to the die head is improved, but the ability to mix the green composition to promote its reaction is reduced.

[0376] According to one embodiment of the manufacturing method of the present invention, the ratio of the spiral screw portion to the total length of the barrel of the extruder is usually preferably less than 95%, preferably less than 90%, and more preferably less than 85%. Generally speaking, when using an extruder to manufacture puffs such as puffs, it is necessary to forcefully extrude the composition under high pressure, so there is a motivation to increase the ratio of the spiral screw portion to the total length of the barrel. (Even when kneading is performed at a high SME value), the ratio of the spiral screw portion to the total length of the barrel is usually 95% to 100%.

[0377] According to one embodiment of the manufacturing method of the present invention, it is preferred that the barrel portion having a kneading effect is generally 5% or more, particularly 7% or more, further 10% or more, and particularly 12% or more of the total barrel length. Generally speaking, an extruder using a conventional barrel, a screw extruder using a conventional screw (driving screw), or a conventional screw-propelling device is a device whose main purpose is to quickly deliver the contents, and since strong kneading is not envisioned, the proportion of the screw portion relative to the total barrel length often does not satisfy the above range.

[0378] (9) Post-processing

[0379] The composition of the present invention can be obtained by passing through the above steps (i) to (iii) and, if necessary, the step (vi), and can be further subjected to post-treatment. Examples of the post-treatment include molding treatment and drying treatment.

[0380] As the shaping process, for example, there may be mentioned the process of shaping the composition of the present invention (for example, a solid paste composition) into a desired form (for example, the above-mentioned pasta, Chinese noodles, udon noodles, Inaniwa udon noodles, chakishimen noodles, fusilli, gnocchi soup, cold noodles, somen noodles, buckwheat noodles, hot buckwheat cakes, rice noodles, pho, cold noodles, vermicelli, cereals, couscous, cut burdock, tteok, dumpling wrappers, etc.). Such a shaping process can appropriately adopt methods generally known in the art. For example, in the case of making a slender composition such as pasta or Chinese noodles, as long as a device such as the above-mentioned extruder is used, the composition can be extruded and shaped into a slender shape. On the other hand, in the case of making a flat composition, as long as the composition is shaped into a flat shape. In addition, by extruding and shaping the composition, or cutting or die-cutting the composition shaped into a flat shape, compositions of any shape such as slender, granular, and flaky can also be obtained. In the present invention, the "paste composition" refers to a food composition manufactured by kneading food materials derived from edible plants, and is a concept including kneaded products or pasta (including substances not made from wheat). In addition, as a drying treatment method, any method generally used for food drying can be used.

[0381] [III: Pulverized product of the composition and its aggregate]

[0382] It should be noted that the composition of the present invention can be used after being pulverized. That is, in the above-mentioned manufacturing method of the present invention, after the temperature reduction in the above stage (iii), a stage (v) of pulverizing the above composition to make a pulverized composition can be further provided. The pulverized product of the composition of the present invention thus obtained (appropriately referred to as the "pulverized composition of the present invention") also becomes an object of the present invention. When the composition of the present invention is pulverized to make the pulverized composition of the present invention, the pulverization conditions are not particularly limited and can be arbitrary. For example, it is preferably pulverized in such a manner that the particle size d 50 and / or d 90 is about 50 μm or more and 1000 μm or less.

[0383] It should be noted that when manufacturing the pulverized composition of the present invention, by pulverizing the composition of the present invention with high water retention, it is sometimes possible to manufacture an aggregate having shape retention even in a state with a high dry basis moisture content, which is thus preferred. Specifically, according to a preferred embodiment of the present invention, even an aggregate of a pulverized composition with a high dry basis moisture content, for example, usually 50% by mass or more, among which 60% by mass or more, further 70% by mass or more, or 80% by mass or more, or 90% by mass or more, especially 100% by mass or more, can be made into an aggregate having shape retention. The upper limit is not particularly limited and can be set to 500% by mass or less, 400% by mass or less. By firing or kneading the aggregated composition added with water, an aggregated composition with excellent water retention can be made.

[0384] In addition, by using the pulverized composition of the present invention as a raw material, by implementing a high-temperature strong kneading treatment again using the above-mentioned production method of the present invention, or adding an appropriate amount of water for kneading, an agglomerate can be formed. In addition, by using the pulverized composition of the present invention containing more than 15% by mass of water (particularly preferably using a pulverized composition having a decrease in dry basis moisture content of 10% or less after stage (iii)) as a raw material for dough pressing, an agglomerate can also be formed, and more preferably, dough pressing is performed while heating to 70°C or above (or 80°C or above). That is, in the above-mentioned production method of the present invention, after the pulverization in the above-mentioned stage (v), a stage (vi) of agglomerating the above-mentioned pulverized composition to form a pulverized composition agglomerate can be further provided. The agglomerate of the pulverized composition of the present invention obtained in this way (which will be appropriately referred to as "the pulverized composition agglomerate of the present invention") can be used as the composition of the present invention, or appropriately used as the raw material in stage (i) of the present invention. Such a pulverized composition agglomerate of the present invention also becomes the object of the present invention. In the case where the composition of the present invention is pulverized to form the pulverized composition of the present invention, its production conditions are as described above.

[0385] In addition, by using a crushed composition and / or a crushed composition agglomerate as a raw material in a certain proportion as the raw material in stage (i) of the present invention, it can be used as a raw material that has been heat-treated in advance, and the adhesion between the compositions is improved, so it is preferred. That is, the crushed composition obtained in the above-mentioned stage (v) and / or the crushed composition agglomerate obtained in stage (vi) can be mixed in the composition of stage (i) in a manner that is converted to a certain proportion of dry mass. Its lower limit is not particularly limited, and is usually 5% by mass or more, wherein it is 10% by mass or more, and further 15% by mass or more, particularly 20% by mass or more. Its upper limit is not particularly limited, and is usually 100% by mass or less, or 90% by mass or less.

[0386] Example

[0387] Hereinafter, the present invention will be described in more detail based on Examples. However, these Examples are merely examples shown for convenience of description, and the present invention is not limited to these Examples in any sense.

[0388] [Preparation of a solid composition containing starch]

[0389] The dried bean powder that had been pre-treated (powdered / heated) as described in the "Dried bean powder" in Table 1 below was used, and water was appropriately added to prepare the green composition of each test area and comparison area. The obtained green composition of each test area and comparison area was used to produce the solid composition containing starch of each test area and comparison area according to the conditions described in the "Processing conditions" in Table 3 below. Specifically, the "type of equipment" described in the "equipment used" was used, and as the barrel used for kneading, a barrel with a "ratio of screw flight parts" was used, and the barrel was changed from the part described in the "kneading part" among the barrel parts ((1) to (9) in Table 3 below) to a barrel with a shape having a strong kneading ability, and the temperature of the part corresponding to the "temperature condition" was set to the value described in the table below ((1) in the table corresponds to the raw material input part, and (9) in the table corresponds to the outlet temperature).

[0390] It should be noted that, as a twin-shaft extruder, HAAKE Process 11 (screw diameter 11 mm × 2, screw length 41 cm, segmented, co-rotating screw) made by Thermo Fisher Scientific was used, and as a uniaxial extruder, a uniaxial extruder (screw diameter 70 mm × screw length 140 cm) made by NP Foods was used. In addition, water was added according to the method described in the "water injection method", and processing was performed according to the "barrel rotation speed", "mixing intensity (SME value)", and "internal pressure (pressure near the outlet)". After extrusion, it was placed on a mesh conveyor belt, and the post-treatment described in Table 3 was appropriately applied, the temperature of the composition was adjusted, and the time from the green body temperature being reduced to less than 80° C. to continuously reaching a dry basis moisture content of less than 25% was adjusted by spraying mist-like moisture, etc., thereby obtaining a solid composition containing starch.

[0391] In the "Water injection method" of Table 3, "A" means that the raw material powder and water (amount to reach the "dry basis moisture content" in the "measured value of green body composition" in Table 2-2) are mixed in (1) and added in the green body state, and "B" means that the raw material is added in the powder state in (1) and water (amount to reach the "dry basis moisture content" in the "measured value of green body composition" in Table 2-2) is injected in (3). In addition, in the "temperature condition of each barrel part" of Table 3, "-" means no heating.

[0392] [Measurement of various compositions and physical properties of green composition and solid composition containing starch]

[0393] For the green composition and the solid composition containing starch in each test area and comparison area, various composition values ​​and physical property values ​​were measured by the following methods. The results are shown in the following Table 2 "Green composition measurement values" and the following Tables 4 and 5 "Solid composition measurement values ​​containing starch".

[0394] [Determination of starch, protein, insoluble dietary fiber, and moisture content on dry basis]

[0395] For "starch", according to the Japanese Standard Table of Composition, 2015 (7th edition), the method of AOAC996.11 was used to remove soluble carbohydrates (glucose, maltose, maltodextrin, etc.) that affect the measured value by 80% ethanol extraction treatment. For "protein", according to the Japanese Standard Table of Composition, 2015 (7th edition), the method of multiplying the nitrogen amount quantified by the modified Kjeldahl method by the "nitrogen-protein conversion factor" was used to calculate the nitrogen. For "insoluble dietary fiber", according to the Japanese Standard Table of Composition, 2015 (7th edition), the modified Prosky method was used to measure the "dry basis moisture content", according to the Japanese Standard Table of Composition, 2015 (7th edition), the reduced pressure heating drying method was used to measure by heating to 90°C.

[0396] [Determination of Molecular Weight Distribution of Starch]

[0397] The molecular weight distribution of the composition of each test area and comparison area and the analysis of the relevant parameters (logarithm of the mass average molecular weight, [value α], [value β] and [value γ]) were carried out according to the following procedures.

[0398] First, the composition of each test area and comparison area is thermostated in 40 times the amount of water at 90°C for 15 minutes, and then as the following [step a], a 2.5% aqueous dispersion of the composition of each test area and comparison area is prepared, and it is pulverized together with the composition in the liquid, and after proteolytic enzyme treatment, an ethanol-insoluble and dimethyl sulfoxide-soluble component is obtained as purified starch. The pulverization treatment after the thermostat treatment is carried out by using a homogenizer NS52 (manufactured by Microtech Nichion) at 25000 rpm for 30 seconds. The proteolytic enzyme treatment is carried out by adding, for example, 0.5% by mass of proteolytic enzyme (Protease K manufactured by Takara Bio, product code 9034) to the composition subjected to the pulverization treatment and reacting it at 20°C for 16 hours.

[0399] Extraction of the ethanol-insoluble and dimethyl sulfoxide-soluble component was performed according to the following procedure. That is, (i) 240 times the amount of 99.5% ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the composition subjected to the pulverization treatment and the protease treatment based on the composition used initially, and after mixing, the mixture was centrifuged (at 10,000 rpm for 5 minutes) to obtain an ethanol-insoluble fraction. Next, (ii) 80 times the amount of dimethyl sulfoxide (CAS 67-68-5, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the obtained ethanol-insoluble fraction based on the composition used initially, and the mixture was treated at 90° C. for 10 minutes while stirring to dissolve the mixture, and the dissolved solution was centrifuged (at 10,000 rpm for 5 minutes), and the supernatant was recovered to obtain a dimethyl sulfoxide-soluble fraction. Next, (iii) 240 times the amount of 99.5% ethanol was added to the obtained dimethyl sulfoxide soluble fraction based on the composition used initially, and after mixing, the precipitate fraction was recovered by centrifugation (10000 rpm, 5 minutes). Then, the operation (iii) was repeated 3 times, and the finally obtained precipitate was dried under reduced pressure, thereby obtaining a component that was insoluble in ethanol and soluble in dimethyl sulfoxide as purified starch.

[0400] Next, as [Condition A], 0.10 mass % of the purified starch of each test area and comparison area obtained by the above steps was dissolved in a 1M sodium hydroxide aqueous solution, and after standing at 37°C for 30 minutes, an equal amount of water and an equal amount of eluent (0.05M NaOH / 0.2% NaCl) were added, and the filtrate was filtered through a 5μm filter to obtain a filtrate. 5 mL of the filtrate of each test area and comparison area obtained was subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm of 5.0 or more and less than 9.5.

[0401] As the gel filtration column of gel filtration chromatography, the following 4 columns are selected and used in series in a manner from large to small in order to exclude the limiting molecular weight from the upstream side of the analysis. By making such a structure, starch with a molecular weight logarithm (6.5 or more and less than 8.0) equivalent to the middle [value β], starch with a molecular weight logarithm (5.0 or more and less than 6.5) equivalent to a smaller [value α] and / or starch with a molecular weight logarithm (8.0 or more and less than 9.5) equivalent to a larger [value γ] can be separated, and each parameter can be appropriately measured.

[0402] TOYOPEARL HW-75S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 7.7 Da, average pore diameter of 100 nm or more, Φ2 cm×30 cm): 2 pieces.

[0403] TOYOPEARL HW-65S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 6.6 Da, average pore diameter 100 nm, Φ2 cm×30 cm); 1 piece.

[0404] TOYOPEARL HW-55S (manufactured by TOSOH CORPORATION, exclusion limit molecular weight (logarithm): 5.8 Da, average pore diameter 50 nm, Φ2 cm×30 cm): 1 piece.

[0405] Other gel filtration chromatography conditions are as follows. As the eluent, 0.05M NaOH / 0.2% NaCl was used, and separation was performed at a column oven temperature of 40°C and a flow rate of 1 mL / min, and the components in the eluent were detected every 0.5 seconds. As the detection device, an RI detector (RI-8021 manufactured by TOSOH CORPORATION) was used.

[0406] The data analysis of gel filtration chromatography was performed according to the following procedure. That is, among the measured values ​​obtained by the detection device, for the values ​​within the logarithmic range of the molecular weight of the measured object (5.0 or more and less than 9.5), after data correction was performed so that the lowest value was 0, each dissolution time was converted into a common logarithm of the molecular weight (logarithm of the molecular weight) using a calibration curve based on the peak dissolution time of a linear standard pullulan marker for size exclusion chromatography with a peak molecular weight of 1,660,000 and a peak molecular weight of 380,000 (e.g., P400 (DP2200, MW380,000) and P1600 (DP9650, MW1,660,000) manufactured by Showa Denko K.K.). In addition, when the total of the measured values ​​of the detection equipment for each dissolution time within the molecular weight logarithm range of the measurement object (5.0 or more and less than 9.5) is set to 100, the measured value of each dissolution time (logarithm of molecular weight) is expressed as a percentage, and the molecular weight distribution of the measurement sample is calculated (X-axis: logarithm of molecular weight, Y-axis: percentage (%) of the measured value at each molecular weight relative to the total of the measured values ​​of the RI detector in the entire measurement range) to prepare a molecular weight distribution curve.

[0407] The mass average molecular weight is calculated from the molecular weight distribution curve obtained according to the above steps according to the following steps. That is, for the values ​​within the molecular weight logarithm range (5.0 or more and less than 9.5) of the measurement object, each molecular weight converted from the dissolution time is multiplied by 1 / 100 of the value of the Y axis in the above molecular weight distribution (the percentage of the measured value at each molecular weight relative to the total of the RI detector measured values ​​in the entire measurement range) and the mass average molecular weight is obtained by accumulating the value, and then the mass average molecular weight logarithm is obtained by calculating its common logarithm value.

[0408] Furthermore, from the molecular weight distribution curve, the ratios of the areas under the curve in the following molecular weight logarithmic ranges were determined and designated as [value α], [value β], and [value γ], respectively.

[0409] [Value α] is the ratio of the area under the curve in the range where the molecular weight logarithm is 5.0 or more and less than 6.5 to the area under the curve obtained from the entire molecular weight distribution curve (molecular weight logarithm range is 5.0 or more and less than 9.5).

[0410] [Value β] is the ratio of the area under the curve in the range where the molecular weight logarithm is 6.5 or more and less than 8.0 to the area under the curve obtained from the entire molecular weight distribution curve (molecular weight logarithm range is 5.0 or more and less than 9.5).

[0411] [Value γ] is the ratio of the area under the curve in the range where the molecular weight logarithm is 8.0 or more and less than 9.5 to the area under the curve obtained from the entire molecular weight distribution curve (molecular weight logarithm range is 5.0 or more and less than 9.5).

[0412] (Determination of the number of starch granule structures in the field of view)

[0413] 3 mg of the composition of each test area and comparison area was crushed with a mill and the obtained composition powder passed through a 150 μm mesh was suspended in 50 μL of water to prepare a 6% aqueous suspension of the composition powder. Then, the suspension was dripped onto a glass slide, and then a cover glass was covered and gently pressed to prepare a microscope specimen. A phase contrast microscope (ECLIPSE80i, manufactured by Nikon) was used to observe the representative parts of the microscope specimen under polarization at a magnification of 200 times to grasp the number of starch granule structures in the field of view.

[0414] (Determination of Gelatinization Peak Temperature)

[0415] After pulverizing the composition sample of 3.5 g of the dry mass of each test area and the comparative area (pulverized until it passes through 100 mesh (mesh size 150 μm) and remains on 120 mesh (mesh size 125 μm)), the sample was measured into an aluminum cup for RVA measurement, and distilled water was added to make the total amount 28.5 g. The 14 mass% sample water slurry prepared in this way was subjected to the RVA viscosity measurement in the above [step a] to measure the gelatinization peak temperature. As a rapid viscosity analyzer (RVA), RVA4800 manufactured by Perten Co., Ltd., which can heat the measurement object to 140°C, was used. The measurement was started at 50°C, the number of revolutions from the start of the measurement to 10 seconds after the start of the measurement was set to 960 rpm, and the number of revolutions from 10 seconds after the start of the measurement to the end of the measurement was set to 160 rpm, and the gelatinization peak temperature (°C) was measured when the temperature was increased at a rate of 12.5°C / min within the range of 50°C to 140°C.

[0416] (Degree of gelatinization of starch)

[0417] The degree of gelatinization of the composition of each test plot and comparison plot was measured by the glucoamylase second method (based on the method of Japan Food Research Laboratories: https: / / www.jfrl.or.jp / storage / file / 221.pdf) which was a partial modification of the one reported by the Central Customs Analysis Institute.

[0418] (Amylolytic enzyme activity)

[0419] The starch decomposing enzyme activity of the composition of each test area and comparison area was measured according to the following steps. First, 10 mL of 0.5% NaCl / 10 mM acetate buffer (pH 5) was added to 1 g of the test sample obtained by crushing the composition of each test area and comparison area, and after standing at 4°C for 16 hours, it was crushed into a paste by treating it at 25000 rpm for 30 seconds using a homogenizer NS52 (made by Microtech Nichion), and after further standing at 4°C for 16 hours, the filtrate obtained by filtering with filter paper (made by ADVANTEC, qualitative filter paper No. 2) was used as an enzyme solution.

[0420] 2 mL of 0.05% soluble starch (Fujifilm Wako Pure Chemical Industries, Ltd., starch (soluble) CAS9005-25-8, product code 195-03961) was placed in a test tube, and after standing at 37°C for 10 minutes, 0.25 mL of enzyme solution was added and mixed. The mixture was allowed to stand at 37°C for 30 minutes. Then, 0.25 mL of 1M HCl was added and mixed, 0.25 mL of 0.05 mol / L iodine solution was added and mixed, 11.5 mL of water was added for dilution, and the absorbance (absorbance A) at a wavelength of 660 nm was measured using a spectrophotometer. In addition, as a control, 2 mL of 0.05% soluble starch was placed in a test tube, and after standing at 37°C for 40 minutes, 0.25 mL of 1M HCl was added and mixed, and then 0.25 mL of enzyme solution and 0.25 mL of 0.05 mol / L iodine solution were added in this order and mixed, and after dilution with 11.5 mL of water, the absorbance at a wavelength of 660 nm was measured using a spectrophotometer (absorbance B).

[0421] The absorbance reduction rate C (%) of each measurement sample at 30 minutes of enzyme reaction was obtained by the absorbance reduction rate of the enzyme reaction area (absorbance A) relative to the comparison area (absorbance B) ({(absorbance B-absorbance A) / absorbance B}×100 (%)). The enzyme activity that reduces the absorbance by 10% every 10 minutes is defined as 1 unit (U), and the enzyme activity per 1g dry mass of the measurement sample (U / g) was obtained by the following formula based on the absorbance reduction rate C (%) when the enzyme reaction was carried out for 30 minutes using 0.25mL of the enzyme solution (sample content 0.025g).

[0422] [Formula 4]

[0423] Enzyme activity unit (U / g) = {C × (10 / 30) × (1 / 10)} / 0.025

[0424] (Determination of iodine staining)

[0425] For the samples before and after processing of the composition of each test area and comparison area, after being put into 40 times the amount of water, they were quickly treated by the same steps as the above [step a] to obtain purified starch. The purified starch obtained was filtered under the same conditions as the above [condition A] and then subjected to gel filtration chromatography to separate fractions with molecular weight logarithms of 5.0 or more and less than 6.5 and 6.5 or more and less than 8.0. Each separated fraction obtained was adjusted to pH 7.0 with hydrochloric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., reagent special grade hydrochloric acid), stained with an iodine solution (0.25mM) obtained by diluting 0.05mol / L iodine solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product code 091-00475) 200 times, and the absorbance at 660nm was measured with a spectrophotometer.

[0426] (Determination of PDI value)

[0427] 20 times the amount of water was added to the composition of each test area and comparison area, and the mixture was crushed (using a homogenizer NS-310E3 manufactured by Microtech Nichion for crushing at 8500 rpm for 10 minutes). The total nitrogen ratio of the crushed liquid obtained was multiplied by 20 and the value obtained was measured as the total nitrogen ratio of the entire composition. Next, the crushed liquid was centrifuged (10 minutes at 3000G), and the total nitrogen ratio of the supernatant obtained was multiplied by 20 and the value obtained was measured as the water-soluble nitrogen ratio, thereby calculating the PDI value of the composition. It should be noted that the total nitrogen ratio was measured by the combustion method (modified Dumas method) specified in the Food Labeling Method ("About Food Labeling Standards" (Digestion Table No. 139, March 30, 2011)).

[0428] [Sensory evaluation of solid composition containing starch]

[0429] A sensory evaluation was performed on a sample obtained by heating and cooking 1 part by mass of the composition of each test area and comparison area prepared as described above in 9 parts by mass of water for 5 minutes at 90°C. Specifically, the composition after heating and cooking was placed on a paper plate, and 10 trained sensory inspectors observed and tasted the dish. The physical properties and taste when eaten were evaluated from the perspectives of "elasticity when retaining water", "viscosity when retaining water" and "comprehensive evaluation" according to the following standards. Then, the average of the scores of the 10 sensory inspectors was calculated, and the first decimal place was rounded off as the final score. It should be noted that as sensory inspectors for each sensory test, recognition training on the taste, texture or appearance of food was implemented in advance, and on this basis, inspectors with particularly excellent results, experience in product development, rich knowledge of the quality of food such as taste, texture or appearance, and who can make absolute evaluations of each sensory test item were selected. In addition, in any of the above evaluation items, all inspectors evaluated the standard sample in advance, standardized the scores of the evaluation criteria, and then conducted an objective sensory inspection.

[0430] Evaluation criteria for "elasticity when retaining water":

[0431] The elasticity of the composition was evaluated according to the following 5 levels.

[0432] 5: It feels very elastic, preferred.

[0433] 4: It feels elastic and is preferred.

[0434] 3: It feels slightly more elastic, which is preferred.

[0435] 2: The elasticity is slightly weak, not preferred.

[0436] 1: The elasticity is weak, which is not preferred.

[0437] Evaluation criteria for "viscosity when retaining water":

[0438] The viscosity of the composition was evaluated according to the following 5-level rating.

[0439] 5: No stickiness is observed on the surface of the composition, which is preferred.

[0440] 4: Almost no stickiness is observed on the surface of the composition, which is preferred.

[0441] 3: Stickiness on the composition surface is slightly observed, but is preferred.

[0442] 2: The stickiness of the composition surface is slightly noticeable, which is not preferred.

[0443] 1: The surface of the composition is noticeably sticky, which is not preferable.

[0444] Evaluation criteria for "comprehensive evaluation":

[0445] The balance between elasticity and viscosity of the composition was evaluated according to the following 5 levels.

[0446] 5: The balance between elasticity and viscosity of the composition is very good, which is preferred.

[0447] 4: The elasticity and viscosity of the composition are well balanced, which is preferred.

[0448] 3: The balance between elasticity and viscosity of the composition is slightly better, which is preferred.

[0449] 2: The balance between elasticity and viscosity of the composition is slightly poor, which is not preferable.

[0450] 1: The balance between elasticity and viscosity of the composition is poor, which is not preferable.

[0451] [result]

[0452] The production conditions, compositions, physical properties, and evaluation results of the compositions of each test plot and comparative plot are shown in Tables 1 to 5 below.

[0453] [Table 1-1]

[0454]

[0455] [Table 1-2]

[0456]

[0457]

[0458]

[0459]

[0460]

[0461]

[0462]

[0463]

[0464]

[0465]

[0466]

[0467]

[0468] Industrial Applicability

[0469] The present invention can be widely applied to the fields of food and the like using a solid composition containing starch as a main component, and has great utilization value.

Claims

1. A solid composition containing starch, the composition containing beans, satisfying all of the following (1) to (4) at the same time, and produced by a production method comprising the following steps (i) and (ii): (1) the content of starch in the composition is 20% by weight or more on a dry basis; (2) Satisfy the following (a) and / or (b): (a) When a 6% suspension of the pulverized product of the composition is observed, the starch granule structure visible is 300 granules / mm 2 the following, (b) the gelatinization peak temperature when a 14 mass % aqueous slurry of the pulverized composition is heated from 50° C. to 140° C. at a heating rate of 12.5° C. / min using a rapid viscosity analyzer is lower than 120° C.; (3) The degree of gelatinization of the starch in the composition is 50% by mass or more; (4) The following [value α] of the composition is 60% or less, and the following [value β] is 35% or more: [Value α] The ratio of the area under the curve of the interval where the molecular weight logarithm is 5.0 or more and less than 6.5 relative to the total area under the curve of the molecular weight distribution curve, wherein the molecular weight distribution curve is obtained by analyzing the purified starch under the following [Condition A], wherein the purified starch is obtained by isothermal treating the composition in 40 times the amount of water at 90° C. for 15 minutes and then treating it by the following [Step a]; [Value β] The ratio of the area under the curve of the interval where the logarithm of the molecular weight is 6.5 or more and less than 8.0 to the total area under the curve of the molecular weight distribution curve; [Step a] pulverizing a 2.5% aqueous dispersion of the composition and treating it with a proteolytic enzyme to obtain an ethanol-insoluble and dimethyl sulfoxide-soluble component as purified starch; [Condition A] 0.10 mass % of purified starch was dissolved in a 1M sodium hydroxide aqueous solution, and after standing at 37°C for 30 minutes, an equal amount of water and an equal amount of eluent were added, and 5 mL of the filtrate obtained by filtering through a 5 μm filter was subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm of 5.0 or more and less than 9.5; (i) a stage of preparing a composition containing beans and having a starch content of 10.0% by mass or more on a wet basis and a moisture content of more than 40% by mass on a dry basis, (ii) A step of kneading the composition prepared in the step (i) at a temperature of 100° C. to 190° C. under conditions where the SME value is 400 kJ / kg or more.

2. The composition according to claim 1, wherein The ratio (β / α) of the [value β] to the [value α] is 0.5 or more.

3. The composition according to claim 1 or 2, wherein The following [value γ] is 30% or less: [Value γ] is the ratio of the area under the curve in the region where the logarithm of the molecular weight is 8.0 or more and less than 9.5, relative to the total area under the curve of the molecular weight distribution curve.

4. The composition according to claim 1 or 2, wherein The ratio (β / γ) of the [value β] to the [value γ] is 10 or more.

5. The composition according to claim 1 or 2, wherein The logarithm of the mass average molecular weight obtained by analyzing the purified starch under the [Condition A] is 6.0 or more, and the purified starch is obtained by the treatment in the [Step a].

6. The composition according to claim 1 or 2, wherein The amylolytic enzyme activity of the composition is 30.0 U / g or less based on dry mass.

7. The composition according to claim 1 or 2, wherein When 1 mass part of the sample is stained with 9 mass parts of iodine solution (0.25 mM), the absorbance at 660 nm is less than 0.80, wherein the sample is obtained by adjusting the pH of the separated fraction having a molecular weight logarithm of greater than 5.0 and less than 6.5, obtained by adding the composition into 40 times the amount of water and then rapidly treating it through the [step a] to obtain purified starch separated and recovered under the [condition A], to 7.

0.

8. The composition according to claim 1 or 2, wherein The protein content of the composition is 3.0% by mass or more in terms of dry mass.

9. The composition according to claim 1 or 2, wherein The PDI (Protein Dispersibility Index) value of the composition is less than 55% by mass.

10. The composition according to claim 1 or 2, wherein After subjecting the composition to starch-protein decomposition treatment in the following [step b], the particle size distribution is measured after ultrasonic treatment. 50 and / or 90 Below 450μm: [Step b] A 6 mass % aqueous suspension of the composition was treated with 0.4 volume % of protease and 0.02 mass % of α-amylase at 20° C. for 3 days.

11. The composition according to claim 1 or 2, wherein The insoluble dietary fiber content of the composition is 2.0% by mass or more in terms of dry mass.

12. The composition according to claim 1 or 2, wherein The total fat and oil content of the composition is less than 17% by mass on a dry mass basis.

13. The composition according to claim 1 or 2, wherein The moisture content of the composition on a dry basis is 60% by mass or less.

14. The composition according to claim 1 or 2, wherein The beans have a moisture content of less than 15% by mass on a dry basis.

15. The composition according to claim 1 or 2, wherein Beans are mature legumes.

16. The composition according to claim 1 or 2, wherein The legumes are at least one legume selected from the group consisting of genus Pisum, genus Phaseolus, genus Pigeonpea, genus Vigna, genus Vicia, genus Garbanzo, genus Glycine max, and genus Lentil.

17. The composition according to claim 1 or 2, wherein The particle size of beans after ultrasonic treatment is d 90 Morphology of pulse powders below 500 μm.

18. The composition according to claim 1 or 2, wherein The content of beans is 50% by mass or more on a dry basis.

19. The composition according to claim 1 or 2, wherein The content ratio of the starch blended in a state of being contained in beans relative to the total starch content of the composition is 30% by mass or more.

20. The composition according to claim 1 or 2, wherein The content ratio of the protein blended in a state of being contained in beans relative to the total protein content of the composition is 10% by mass or more.

21. The composition of claim 1 or 2, which is not a puffed product.

22. A pulverized composition obtained by pulverizing the composition according to any one of claims 1 to 21.

23. A pulverized composition agglomerate, wherein the pulverized composition according to claim 22 is agglomerated.

24. A method for producing a solid starch-containing composition according to any one of claims 1 to 21, comprising the following steps (i) and (ii): (i) a stage of preparing a composition containing beans and having a starch content of 10.0% by mass or more on a wet basis and a moisture content of more than 40% by mass on a dry basis, (ii) kneading the composition prepared in step (i) at a temperature of 100° C. to 190° C. at a SME value of 400 kJ / kg or more until all of the following conditions (1) to (4) are satisfied: (1) The composition satisfies the following (a) and / or (b): (a) The starch granule structure of the composition is 300 granules / mm 2 the following, (b) the gelatinization peak temperature when a 14 mass % aqueous slurry of the pulverized composition is heated from 50° C. to 140° C. at a heating rate of 12.5° C. / min using a rapid viscosity analyzer is lower than 120° C.; (2) the gelatinization degree of the composition is 50% by mass or more; (3) the [value α] of the composition is 60% or less; (4) The [value β] of the composition is 35% or more.

25. The manufacturing method of claim 24, further comprising: (iii) A step of cooling the kneaded composition in step (ii) to below 100°C.

26. The manufacturing method according to claim 24 or 25, further comprising: (iv) A stage where the dry basis moisture content of the composition is reduced to less than 25% by mass.

27. The manufacturing method according to claim 26, wherein: After the stage (ii), the time required from when the temperature of the composition decreases to less than 80° C. until the dry basis moisture content of the composition decreases to less than 25% by mass is 10 minutes or more.

28. The production method according to claim 24 or 25, wherein By performing the water addition treatment in the stage after the stage (iii), the time required for the dry basis moisture content of the composition to be less than 25 mass % is adjusted.

29. The production method according to claim 24 or 25, wherein: The stage (ii) and thereafter include a stage where the difference in gelatinization degree reduction is 1% by mass or more.

30. The manufacturing method according to claim 24 or 25, further comprising: (v) A step of pulverizing the obtained composition after at least the above step (ii) to obtain a pulverized composition.

31. The manufacturing method of claim 30, further comprising: (vi) After the above step (v), the obtained pulverized composition is agglomerated to form an agglomerate of the pulverized composition.

32. The production method according to claim 24 or 25, wherein: Said stage (ii) is carried out using an extruder.

33. The manufacturing method according to claim 32, wherein: Preparation of the composition in stage (i) involves adding water to the raw materials before feeding them into the extruder.

34. The manufacturing method according to claim 32, wherein: The preparation of the composition in stage (i) includes adding water to the raw materials in the extruder after the raw materials are fed into the extruder.

35. The manufacturing method according to claim 34, wherein: In the stage (i), the raw materials in the extruder are not exposed to a high temperature of 90° C. or higher in a state where the moisture content on a dry basis is less than 25% by mass.

36. The manufacturing method according to claim 32, wherein: Before the internal temperature of the extruder rises to 90° C. or more, 50% by mass or more of the total amount of water blended in stages (i) and (ii) is mixed with other raw materials during production.

37. The manufacturing method according to claim 32, wherein: The composition after stage (iii) is placed on a mesh conveyor having a part or the whole of a placement surface having ventilation properties.

38. The manufacturing method according to claim 37, wherein: There is a step of adding water to the composition at any stage before or after the composition is placed on the mesh conveyor.

39. The manufacturing method of claim 37, comprising: The temperature of the composition is lowered by blowing air to the composition from the upper part and / or the lower part of the mesh conveyor.

40. The manufacturing method according to claim 39, wherein The difference in gelatinization degree reduction before and after air supply was 1% by mass.

41. The manufacturing method according to claim 32, wherein: The flight screw length is 95% or less relative to the total screw length of the extruder.

42. The production method according to claim 24 or 25, wherein In said stage (ii), (c) or (d) is also satisfied: (c) when a 6% suspension of the pulverized product of the composition is observed, the structure of the starch granules visible before and after stage (ii) is reduced by more than 5%; (d) When a 14 mass % aqueous slurry of the pulverized composition is heated from 50°C to 140°C at a heating rate of 12.5°C / min using a rapid viscosity analyzer, the gelatinization peak temperature decreases by 1°C or more before and after stage (ii).

43. The production method according to claim 24 or 25, wherein After the composition in the stage (i) is subjected to starch-protein decomposition treatment by the [step b], the particle size distribution is measured after ultrasonic treatment. 50 and / or 90 Less than 450μm.

44. The production method according to claim 24 or 25, wherein The content ratio of the starch blended in a state of being contained in the heat-treated beans relative to the total starch content of the composition in the step (i) is 30% by mass or more.

45. The production method according to claim 24 or 25, wherein The amylolytic enzyme activity (U / g) decreases by more than 20% before and after stage (ii).

46. ​​The production method according to claim 24 or 25, wherein When 1 part by mass of the sample is stained with 9 parts by mass of an iodine solution (0.25 mM), the absorbance at 660 nm is 0.80 or less, wherein the sample is obtained by adjusting the pH of the separated fraction having a molecular weight logarithm of 5.0 or more and less than 6.5, wherein the purified starch obtained by adding 40 times the amount of water in the stage (i) and then rapidly treating it through the [step a] is separated and recovered under the [condition A].

47. The production method according to claim 24 or 25, wherein The ratio of the absorbance (660 nm) when one mass part of the sample is stained with 9 mass parts of iodine solution (0.25 mM) to the absorbance (660 nm) when the separated fraction with a molecular weight logarithm of 6.5 or more and less than 8.0 is stained by the same method is 0.003 or more, wherein the sample is obtained by adjusting the pH of the separated fraction with a molecular weight logarithm of 5.0 or more and less than 6.5 to 7.0, after the purified starch obtained by adding the composition in the stage (i) to 40 times the amount of water and then rapidly treating it by the [step a] is separated and recovered under the [condition A].

48. The production method according to claim 24 or 25, wherein The PDI value of the composition in the stage (i) is less than 90% by mass.

49. A solid starch-containing composition, comprising beans, satisfying all of the following (1) to (4), and produced by a production method comprising the following steps (i) and (ii): (1) the content of starch in the composition is 20% by weight or more on a dry basis; (2) Satisfy the following (a) and / or (b): (a) When a 6% suspension of the pulverized product of the composition is observed, the starch granule structure visible is 300 granules / mm 2 the following, (b) the gelatinization peak temperature when a 14 mass % aqueous slurry of the pulverized composition is heated from 50° C. to 140° C. at a heating rate of 12.5° C. / min using a rapid viscosity analyzer is lower than 120° C.; (3) The degree of gelatinization of the starch in the composition is 50% by mass or more; (4) The composition has the following [value α] of 60% or less, the ratio of the following [value β] to the following [value α] (β / α) of 0.5 or more, and the following [value γ] of 30% or less: [Value α] The ratio of the area under the curve of the interval where the molecular weight logarithm is 5.0 or more and less than 6.5 relative to the total area under the curve of the molecular weight distribution curve, wherein the molecular weight distribution curve is obtained by analyzing the purified starch under the following [Condition A], wherein the purified starch is obtained by isothermal treating the composition in 40 times the amount of water at 90° C. for 15 minutes and then treating it by the following [Step a]; [Value β] The ratio of the area under the curve of the interval where the logarithm of the molecular weight is 6.5 or more and less than 8.0 to the total area under the curve of the molecular weight distribution curve; [Value γ] The ratio of the area under the curve of the region where the logarithm of the molecular weight is 8.0 or more and less than 9.5 to the total area under the curve of the molecular weight distribution curve; [Step a] pulverizing a 2.5% aqueous dispersion of the composition and treating it with a proteolytic enzyme to obtain an ethanol-insoluble and dimethyl sulfoxide-soluble component as purified starch; [Condition A] 0.10 mass % of purified starch was dissolved in a 1M sodium hydroxide aqueous solution, and after standing at 37°C for 30 minutes, an equal amount of water and an equal amount of eluent were added, and 5 mL of the filtrate obtained by filtering through a 5 μm filter was subjected to gel filtration chromatography to measure the molecular weight distribution in the range of molecular weight logarithm of 5.0 or more and less than 9.5; (i) a stage of preparing a composition containing beans and having a starch content of 10.0% by mass or more on a wet basis and a moisture content of more than 40% by mass on a dry basis, (ii) A step of kneading the composition prepared in the step (i) at a temperature of 100° C. to 190° C. under conditions where the SME value is 400 kJ / kg or more.

Citation Information

Patent Citations

  • Noodle quality improving agent and method for producing noodle

    JP2004215543A

  • Pulse-based pasta and process for manufacturing the same

    US20180360079A1

  • Production of legume pasta products by a high temperature extrusion process

    US5989620A